Effects of sampling strategy, geographical origin, and soil on stable isotopes and multi-elements for the traceability of Chinese PGI oranges - Jiahui Wu; Hao Deng; Guang Wu; Hanyi Mei; Karyne M. Rogers; Yurong Huang; Shengzhi Shao; Chunlin Li; Ping Wang; Jing Nie; Yuwei Yuan; Yongzhi Zhang (Food Control, 2026)

Clear water but contaminated sediment: Heavy metal risks in suspended sediments of the Three Gorges Reservoir, China - Bingyan Li; Jie Wei; Xiubin He; Yuhai Bao; Qiang Tang; Ping Huang; Shengjun Wu; Jinlin Li (Ecohydrology & Hydrobiology, 2026)

Deep neural network-based prediction of sauce-flavor Baijiu fermentation process and regulation of flavor compound synthesis - Shiyuan Ma; Wei Cheng; Zhongfu Duan; Dan Huang; Ping Huang; Qiuxia Li; Siyuan Zeng; Rongqing Zhou; Yadong Zhang; Jiao Niu; Chongde Wu; Yi Shen (Bioresource Technology, 2026)

Piperlongumine inhibits the proliferation and migration of non-small cell lung cancer cells through the EGFR/FAK/STAT3 pathway - Qianwen Huang; Wen Chen; Xin Xu; Jiaxin Hua; Lehui Li; Ping Hu; Wei Zhang; Longhua Sun (Molecular Biology Reports, 2026)

Lipid-lowering activity of mulberry seed unsaturated fatty acids: integrating network pharmacology and experimental validation - Yue Zhang; Haoran Huang; Jianglong He; Yuqi Li; Xueping Jiang; Ping Wu; Syed Asim Shah Bacha; Ran Zhang; Hao Li; Gaiqun Huang; Zhongzheng Gui (Functional & Integrative Genomics, 2026)

Distinct soil microbial community composition and structure: evidence from soil inside and outside the cattle farm - Qi Ding; Jiayi Li; Fengling Xue; Wenjun Cui; Shiguang Hu; Lingfeng Yu; Wanyue Huang; Lin Li; Ping Cheng (Brazilian Journal of Microbiology, 2026)

Integrating grazing intensity regulation and livestock mobility restoration: A practical test for China’s next-generation rangeland policies - Jianguo Xue; Zunlan Luo; Zhang Chen; Ping Ge; Junchen Lv; Jianhui Huang; Ang Li (Agriculture, Ecosystems & Environment, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

COX-2 inhibitors from Laportea bulbifera: Structure-activity relationship, kinetic investigation, and molecular docking - Linlan Tao; Yanan Li; Zipeng Gong; Feng Zhang; Jue Yang; Lei Huang; Ting Xiao; Ping Yi; Xiaojiang Hao; Chunmao Yuan (Phytochemistry, 2026)

Multi-inlet stepped hydrocyclone for precise classification of sandy alumina precursor - Shiqi Zhang; Qingshan Huang; Zhenzhen Wang; Yifan Bu; Hang Xiao; Haidong Zhang; Yan Liu; Aqiang Chen; Ping Li (Minerals Engineering, 2026)

Delta dynamics: Insights from high-density OSL chronology in the Han River Delta, Northern South China Sea - Ping Lai; Gui Long; Tiantian Huang; Guanjun Xu; Zibin Fang; Ziyuan Wu; Yuexin Liu; Penghui Lin; Xiwen Nong; Xiaojian Zeng; Hongwei Li; Zhongping Lai (Geomorphology, 2026)

Microneedle patches at the bio-agricultural Interface: Toward precision, resilience, and sustainability - Fangzheng Zhou; Xiaochen Huang; Yaqi Teng; Ping Yu; Boqiang Li; Haowen Sun; Yixin Gao; Ruikun He; Wei Sun; Bei Fan; Xiaoxue Jia; Long Li; et al. (Food Research International, 2026)

Co-application of biochar and organic fertilizer shifts bacterial community assembly toward deterministic processes and enhances carbon sequestration in subtropical coniferous plantations - Lixin Liang; Changwu Li; Xiaoyue Liu; Ping Zhong; Danxing Yang; Xinhao Huang (Forest Ecology and Management, 2026)

Assessing present-day tectonic stability, sea-level change, and tsunami hazards from a coastal multi-hazard GNSS station in the southern South China Sea - Qiang Qiu; Linlin Li; Mai Ye; Hongqiang Yang; Xingyu Song; Jian Ping Yin; Tingting Zheng; Jinghe Cao; Peitao Wang; Zhanying Chen; Zhiwen Zhang; Kuilin Xiao; et al. (Engineering Geology, 2026)

Biomass-derived Fe3C@CNT catalyst for catalytic ozonation through confinement-enhanced electron transfer and ozone activation - Tian He; Shaosong Huang; Ping Chen; Guangzheng Zhuang; Bing Tang; Ping Li; Liying Bin; Yunqiang Yi; Weirui Chen; Laisheng Li (Chemical Engineering Journal, 2026)

Antibiotics affect the water purification performance and greenhouse gases emission mode in modular moving bed constructed wetland - Ping Deng; Hongyun Ma; Zhihao Luo; Lingwei Kong; Lei Zhou; Xueqi Zhang; Jianshi Huang; Yiqian Chen; Yiyang Li; Yuefang He; Shaole Yu; Shuiping Cheng (Chemical Engineering Journal, 2026)

Discovery and engineering of a formate dehydrogenase with enhanced bicarbonate reduction activity - Feng Lu; Runxin Liang; Yimiao Chen; Xiao Li; Ruolin Yang; Yuhong Huang; Wangtao Jiang; Yongtong Feng; Ping Gui; Xuefeng Wang; Fuqiang Ma (Bioresource Technology, 2026)

AIE-active photoresponsive Ir(III) complex as an oxidase mimic for ratiometric ascorbic acid detection - Qianghui Zheng; Ping Huang; Ying Peng; Mei-Jin Li; Fengfu Fu (Analytica Chimica Acta, 2026)

Historical and future changes in Tibetan Plateau aridity and their scenario-dependent climatic controls - Libin Huang; Ping Li; Jiajia Zhang; Yanjin Mao; Xianchun Chen; Xiaoyu Hu; Xiaorui Niu (Climate Dynamics, 2026)

Revisiting the behavior–emissions link: A multiplicative modeling approach with large-scale mobile data - Yusi Luo; Dong Zhang; Ping Huang; Yongqi Hou; Pengjun Zhao; Ling Li (Travel Behaviour and Society, 2026)

CvbZIP81 contributes to selenium accumulation by regulating sulfate transports in Cardamine violifolia - Luxin Feng; Jiarui Zheng; Sirui Zeng; Ge Li; Sisi Wang; Ping Yun; Zexiong Chen; Renhua Huang; Qiangwen Chen; Sergey Shabala; Feng Xu (Plant Science, 2026)

Reactive oxygen species–mediated enhancement of cadmium phytoextraction in ramie (Boehmeria nivea L) by pyrite: Linking rhizosphere chemistry to plant metabolism - Tangshan Wu; Xiaofei Tan; Ping Chen; Chuang Li; Gaobin Chen; Zhenhong Huang; Genying Zeng; Yaqian Yang; Meijuan Zhang (Journal of Environmental Chemical Engineering, 2026)

Erosion rates in the northern coast of Southern China Sea: Insights from granitic cosmogenic nuclide depth profiles - Hao Liang; Ying Xu; Ziye Zhou; Zhen Chen; Yongjie Tang; Cong Chen; Ke Zhang; Ping Huang; Zhigang Li; Gege Hui; Yipeng Zhang; Qingying Tian; et al. (Geomorphology, 2026)

Metagenomics-based insights into the microbial community succession and metabolic potential of flavor in Qingke high-temperature Daqu - Yuqin Tong; Yang Wei; Yang Yang; Minghui Jiang; Shu Li; Xiaotong Liu; Songtao Wang; He Huang; Miao Liu; Ping Song (Food Research International, 2026)

Rhamnolipids: from biosynthesis to applications - Ai-Ping Pang; Zhiqing Zhang; Guo-Zhao Li; Yun Wang; Kun Yang; Junping Zhou; Lianggang Huang; Li-Qun Jin; Zhi-Qiang Liu; Yu-Guo Zheng (Food Chemistry, 2026)

Integrated analysis of lipid remodeling and volatile evolution during refining of Antarctic krill oil - Xinya Huang; Meiyu Zheng; Jin Zhang; Jinglun Zhou; Qingyang Zhang; Zhengting Zhu; Ping Kong; Shu Wang; Bin Li; Zhigang Hu; Kangyu Zhao; Dongping He; et al. (Food Chemistry, 2026)

Antibacterial mechanisms of magnolol against Streptococcus agalactiae and immunomodulatory effects in Schizothorax prenanti - Yilin Wang; Kun Peng; Longjun Deng; Yihao Wang; Qibin Jiang; Tiancai Li; Ping Ouyang; Defang Chen; Xiaoli Huang; Yi Geng (Fish & Shellfish Immunology, 2026)

Corrigendum to “Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system” [Estuar. Coast Shelf Sci. 340 (2026) 110113] - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Aging and photodegradation of polycyclic aromatic compounds (PACs) emitted from biomass burning under sunlight and ultraviolet radiation - Ya-Jing Li; Zhen-Shan Huang; Yu-Ping Chen; Zhi-Hui Su; Yi-Huan Chen; Yuan Zeng; Yu-Qi Huang; Yu-Feng Guan; She-Jun Chen (Atmospheric Environment, 2026)

Fipronil and its metabolites in a tropical estuary: multi-compartment distribution, trophic transfer, and risk assessment - Yu-Han Xie; Can Huo; Zhi-Yan Wang; Shan-Shan Yao; Heng-Xiang Li; Yu Zhong; Xiao-Ping Huang; Xiang-Rong Xu (Marine Environmental Research, 2026)

Shortened sludge retention time orchestrates the synergistic integration of shortcut nitrogen elimination and enhanced phosphorus removal in an A2O process integrating return sludge side-stream fermentation - Yawen Xing; Feiyi Yuan; Jiaxuan Huang; Xuyang Chen; Qian Ping; Lin Wang; Yongmei Li (Journal of Water Process Engineering, 2026)

Trace element sources, migration and health risks associated with river-groundwater interaction: Insights from isotopes, fluorescence spectroscopy and Monte Carlo simulation - Xu Yang; Muhan Li; Yiying Miao; Fuyang Huang; Zeyuan Liu; Hongli Ma; Ping Miao; Jigang Shi; Zengbao Zhang; Shen Qu; Ruihong Yu (Journal of Hydrology, 2026)

Incorporating variable source areas into rainfall-runoff pollutant export modeling for rural residential catchment - Xuan Huang; Xu Yang; Yuhang Zhang; Man Lang; Ping Li; Kebing Chen; Dongli She; Yongqiu Xia (Journal of Hydrology, 2026)

Effects of dietary rosemary extract on meat quality, antioxidant capacity, fatty acid and amino acid compositions, and proteomic profile of duck breast muscle - Yang Liu; Xuan Huang; Chuang Li; Ping Deng; Xu Zhang; Yan Hu; Qiuzhong Dai (Food Chemistry, 2026)

Scalable and recyclable copper-loaded aminated polyacrylonitrile fibers for humidity-enhanced hydrogen sulfide capture - Ke-Jiang Zhao; Kai Jiang; Guo-ping Li; Chao-Jun Wu; Gui-Zhou Xu; Zuo-Hua Huang; Zhen-Bang Tian (Chemical Engineering Journal, 2026)

Dual-functional nanotherapeutics: A novel approach to siRNA-mediated TNF-α silencing in inflammatory bowel disease - Li Qiao; Xue-Tian Qian; Yi-Gang Zhang; Xia-Feng Peng; Qi Liu; Shi-Qi Chang; Chang Cui; Feng Zhang; Shu-Kui Wang; Ning-Ping Huang (Chemical Engineering Journal, 2026)

Soil compaction alters soil aeration and promotes arsenic accumulation in wheat at the seedling stage in a clay loam Alfisol - Xin-Jun Huang; Lan-Ting Liu; Li-Ping Li; Yong-Qiang Yang; Ya-Li Wang; Rainer Horn; Stephan Peth (Plant and Soil, 2026)

Correction: New 1,2,3-triazole-linked (±)-agrimonolide derivatives as anti-ulcerative colitis agents inhibiting JAK1/STAT3 pathways - Xiao Zhang; Ming-Qian Ju; Heng-Li Yang; Chun-Fei Zhang; Mao-Kui Huang; Yan-Ping Li; Chun-Ping Wan; Ze-Wei Mao (Molecular Diversity, 2026)

Bioactive prenylated acylphloroglucinols from Hypericum scabrum - Li-Ping Teng; Jie-Lian Huang; Shui-Qing Guan; Chen-Xi Xin; Zi-Yin Mai; Yik-Ling Chew; Zhong-Bo Zhou; Gencheng Liang (Natural Product Research, 2026)

Chloride ions-assisted high-efficiency natural seawater splitting enabled by noble-metal-free MnOx(OH)y/GaN nanowires - Yumeng Li; Liang Qiu; Xiantong Zheng; Lin Yao; Muhammad Salman Nasir; Zijian Huang; Ying Li; Yixin Li; Ding Wang; Wenxing Yang; Jianyang Zang; Ping Wang; et al. (Science Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Human contributions to atmospheric reactive nitrogen emissions in polluted regions - Xue-Yan Liu; Yu-Ping Dong; Hao Huang; Zhi-Li Chen; Wei Song (Science Bulletin, 2026)

Research on the slamming characteristics and structural safety of floating wind turbines based on the CFD–FEM method - Yinzhi Zhao; Ran Shen; Fali Huo; Ping Luo; Mingyang Li; Yunke Huang (Ocean Engineering, 2026)

Dual-functional Z‑scheme heterojunction nanozymes with surface encapsulation of porphyrin-based metal-organic framework on covalent organic framework for integrated detection and removal of aflatoxin B1 in foods - Birou Wang; Xiang Li; Xi Huang; Shucong Mo; Jia Yin; Bowen Chen; Yun Huang; Ping Du; Sufang He (Journal of Hazardous Materials, 2026)

Synergistic H2S production and CO2 capture from copper smelting neutralized gypsum slag: Process optimization, reaction mechanism and CaCO3 crystal regulation - Yuwen Deng; Jiyao Shi; Sisi Chen; Huidong Tang; Xiaofeng Huang; Xin Sun; Kai Li; Lei Shi; Ping Ning (Journal of Environmental Management, 2026)

Eccentric coaxial wet-spun magnetic composite actuators with decoupled magneto-pneumatic shape-morphing for biomedical applications - Ping-an Yang; Yixuan Han; Chunyan Mo; Mengjie Shou; Rui Li; Yi Lu; Decheng Wu; Qiao Chen; Zhiwei Huang (Chemical Engineering Journal, 2026)

The impact of atmospheric aging processes on the ice nucleation activity of Asian dust: A perspective from online continuous flow diffusion chamber observations - Jiayun Li; Xinyuan Chang; Dantong Chen; Kai Bi; Yunbo Chen; Xincheng Ma; Ruijie Li; Ping Tian; Mengyu Huang; Xiaoyu Ren; Shuai Wang; Zhaoze Deng; et al. (Atmospheric Pollution Research, 2026)

Source-specific oxidative potential and health risks of PM2.5-bound toxic elements in Xiamen Port: Insights into ship emission contributions - Si-Min Zhao; Qi-Yu Miao; Jia-Min Li; Xin-Ye Wu; Bing-Qi Jiang; Li-Xiong He; Yi-Jing Liu; Zhi Huang; Chung-Shin Yuan; Shui-Ping Wu (Atmospheric Pollution Research, 2026)

Methane production in the stems of living trees in subtropical forests - Zhi-Ping Wang; Josep Barba; Jian-Guo Xue; Xiang-Cheng Mi; Ang Li; Zhen-Ying Huang; Shi-Jie Han (Planta, 2026)

Early Miocene Populus L. Fossils Reveal the Northwestward Expansion of the East Asian Summer Monsoon Into Eastern Qaidam - Zhen‐Dong Cao; San‐Ping Xie; Jing‐Nan Huang; Yun‐Zhe Zhang; Zi‐Yi Li; Si‐Hang Zhang; De‐Fei Yan (Journal of Biogeography, 2026)
Aim The evolution of the East Asian Summer Monsoon (EASM) is critical for understanding Asian biodiversity and ecosystem stability. While models and geological records suggest the EASM reached the Qaidam Basin during the Miocene, macrofossil evidence remains scarce. We aimed to test the hypothesis of a northwestward monsoon expansion using newly discovered Populus fossils as bioclimatic indicators. Location Wulan Basin, northeastern Tibetan Plateau, Qinghai Province, China. Taxon Angiosperms (Salicaceae: Populus L.). Methods We conducted morphological analyses on leaf fossils and identified their Nearest Living Relative (NLR). By establishing correlations between the leaf traits of the NLR and modern climatic factors, we reconstructed the paleoclimate of the Wulan Basin. Furthermore, we employed Species Distribution Modelling (MaxEnt) to simulate the potential range of this lineage under Early Miocene conditions to explore monsoon‐driven habitat shifts. Results The late Early Miocene fossils from the Wulan Basin are morphologically most similar to the extant Populus davidiana , a species characteristic of temperate, semi‐humid environments. The presence of this lineage indicates that the Wulan Basin—currently an arid region—experienced significantly higher precipitation and a temperate semi‐humid climate during the Early Miocene. MaxEnt modelling reveals that the suitable bioclimatic envelope for this Populus group extended much further northwest than its modern range, providing a potential biological signal of enhanced moisture transport into the interior of East Asia. Main Conclusions The occurrence of Populus fossils in the Wulan Basin provides a preliminary biological indicator for the northwestward expansion of the EASM into the northeastern Tibetan Plateau during the late Early Miocene, although corroboration from additional proxy records and localities is still needed. This climatic shift, likely driven by the phased uplift of the Tibetan Plateau, transformed the regional hydrological cycle and facilitated the migration of mesic woody taxa into Asia's interior. Our findings highlight the profound impact of tectonic‐monsoon interactions on historical plant distributions.

Four new cytotoxic triterpenoids from Euphorbia fischeriana - Yuan-Biao He; Yan-Ni Ma; Yu-Ping Huang; Wen-Na Li; Ting-Xiang Shi; Jing Yang; Yong Zhao (Natural Product Research, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Unraveling antibiotic fate in a highly urbanized estuary: Spatiotemporal patterns, multi-media partitioning, and contaminant prioritization - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Xiao-Ping Huang (Marine Pollution Bulletin, 2026)

A universal geometric model of egg shape with sine-based deformation - Ching-Wei Cheng; Chia-Chun Lai; Ping-Kun Tsai; Ko-Jung Huang; Cheng-Han Li (Biosystems Engineering, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

n-butanol treatment alleviates chilling injury of mango fruit by regulating membrane lipid metabolism - Hao Dong; Ping Yi; Lihong Xie; Qi Wei; Yuhan Long; Min Huang; Ting Gan; Qiuyu Cheng; Lan Zhang; Li Li; Jian Sun (Postharvest Biology and Technology, 2026)

Tolypaxillines A–J: indole diterpenoids with neuroprotective activities from a soil-derived fungus Tolypocladium album DWS131 - Yu-Fen Tan; Xing-Yi Chen; Chao Wang; Ai-Lin Liang; Wen-Yu Lu; Le-Meng Feng; Qi Huang; Yue-Ping Jiang; Shao Liu; Xiao-Bo Xia; Jing Li; Wen-Xuan Wang (Phytochemistry, 2026)

Migration and transformation of nanoplastics and microcystin during Chlamydomonas reinhardtii processing: From the environment to product - Chenxu Wang; Chenyu Chen; Ping Ding; Yonghua Xiong; Xiaolin Huang; Xiaoyang Li (Journal of Hazardous Materials, 2026)

Temporal dynamics and synergistic pollution of microplastics and heavy metal(loid)s in subtropical mangrove sediments - Shuting Qin; Li Shang; Jiawei Liao; Ismail Khan; Xingyun Huang; Yingwen Li; Lulu Zhang; Faming Wang; Bi Zou; Ping Zhuang (Gondwana Research, 2026)

Lactiplantibacillus plantarum 5.1 attenuates ovarian fibrosis by modulating the gut microbiota and ovarian metabolism in a rat model of letrozole-induced polycystic ovary syndrome (PCOS) - Qiu-Ping Huang; Li-Ying Huang; Gui-Lian Liao; Chun-Xiang Huang; Ke-Ying Wang; Jie-Jing Xu; Hao-Ran Sun; Tie-Min Jiang; Jia-Le Song (Food Bioscience, 2026)

First-trimester profiling of maternal plasma metals and vitamins in relation to gestational hypertension - Ting Wu; Tao Li; Xuan-Ping Wang; Yi-Cong Meng; Yan-Ting Wu; He-Feng Huang (Environmental Research, 2026)

GPD1-mediated neuronal lipotoxicity drives aconitine-induced mitochondrial collapse and lethality - Chen Jiang; Wen Hu; Sangyang Deng; Yongjie Huang; Linbo Wang; Zhenyu Yang; Yufei Li; Ping Li; Haiying Wu (Chemico-Biological Interactions, 2026)

Preparation of C and Co co-doped TiO2 Nanomaterials for Visible-Light Photocatalytic Antibacterial Activity - Chunhui Meng; Yuena Li; Qitong He; Yue Hao; Wenjun Yin; Huang Zhou; Ping Li (Water, Air, & Soil Pollution, 2026)

Limosilactobacillus reuteri LR-99 Modulates Gut Microbiota and Core Symptoms in Children with Autism Spectrum Disorder: A Single-arm Pilot Study - Kai Gong; Ziying Xie; Ping Zhang; Jing Xu; Jiangfeng Huang; Xingyu Li; Lihong Huang (Probiotics and Antimicrobial Proteins, 2026)

Integrating microbial functional traits to evaluate responses of soil quality to organic amendments in newly reclaimed farmland - Luotong Wang; Hanqin Yin; Chunlei Huang; Guifang Li; Cheng Zhu; Ping Li (Plant and Soil, 2026)

Magnetically recoverable N-doped graphene/ZnFe-LDO composite for synergistic adsorption-photocatalytic removal of tetracycline in water - Le You; Tianqi Wang; Boya Zeng; Wu Zhang; Yuqing Huang; Zhanli Chen; Ping Zhang; Yujie Li; Bo Zeng (Applied Clay Science, 2026)

Effects of dietary Portulaca oleracea L. aqueous extract on growth performance, intestinal health and intestinal microflora of common carp (Cyprinus carpio) - Jing-Tong Huang; Cong-Fu Liu; Yu-Shi Cai; Li-Fang Li; Hai-Tao Zhao; Yan-Ping Yang; Rui-Fang Wang (Animal Feed Science and Technology, 2026)

The morphological-hydrodynamic resilience mechanisms against the highest storm tide level in a Bay-Inlet-Channel system - Haichen Liu; Xianzhao He; Xiangyuan Li; Yingyi Huang; Xiaohe Zhang; Ping Zhang; Qingshu Yang (Frontiers in Marine Science, 2026)
Extreme storm tide levels, arising from nonlinear cross−scale interactions among surge, astronomical tide, and fluvial flood, threaten estuarine stability and cause major economic losses. The Bay-Inlet-Channel (BIC) system, pivotal to the Greater Bay Area, was severely impacted by Typhoon Hato, which produced record−breaking winds and severe inundation. To quantify the morphological-hydrodynamic resilience of the BIC system against the highest storm tide level (HSTL), the Delft3D model was employed to reproduce characteristics of Hato. Simulation results indicate that HSTL exhibited a sharp gradient along the Bay, with a relative increase of 63.84%, and a more moderate one in the Channel (37.00%), associated with the Channel’s higher resilience ( R G = 0.87). Under a hypothetical “Triple Coincidence” scenario involving a stronger flood discharge, the robustness of the BIC system decreased, with a more pronounced decline for the Channel (Δ R G = −0.23) than for the Bay. Contribution analysis identified surge as the dominant driver of HSTL during Hato (52–75%), followed by astronomical tide (25–51%), nonlinear interactions (−7–6%), and flood (<2%). Surge dominance diminished under “Triple Coincidence” as nonlinear interactions intensified. Momentum and energy analyses showed that lateral HSTL differences were primarily governed by direct wind stress, while longitudinal variations were modulated by morphological heterogeneity. Stronger floods amplified HSTL unevenly, mainly through enhanced nonlinear convection. These discoveries advanced the understanding of the morphological-hydrodynamic resilience and its mechanism regulating HSTL in estuarine systems, providing insights for storm tide risk management.

In vitro nephroprotective indolizidine alkaloids from marine-derived Streptomyces sp. KIB629 - Xiaowei Guo; Lei Wang; Xin He; Bing-Yi Xu; Jun-Jie Zhang; Jian-Ping Huang; Wei Li; Sheng-Xiong Huang; Jing Yang; Ya-Tuan Ma (Natural Product Research, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

First fossil fruit of Spatholobus (Papilionoideae, Fabaceae) from East Asia - Yi-Shan Zhao; Zhen-Dong Cao; Jing-Nan Huang; Zi-Yi Li; Torsten Wappler; Zhen-Xian Zhang; Shu-mei Xiao; Wei-Yu-Dong Deng; San-Ping Xie (Review of Palaeobotany and Palynology, 2026)

Effects of affordable housing transition on residents' activity-travel behavior in Shenzhen: Evidence from longitudinal mobile phone data - Ling Li; Ping Huang; Yusi Luo; Pengjun Zhao (Journal of Transport Geography, 2026)

Metabolic reconstruction and microbial network assembly immobilised heavy metals during soil function recovery in coal gangue - Pan Wang; Cheng Chen; Yubo Zhang; Chaosheng Liao; Lin Li; Xiaolong Tang; Mingjie Zhang; Guangrou Lu; Xiaokang Huang; Ping Li; Chao Chen (Journal of Hazardous Materials, 2026)

Biochar derived from shell waste: Adsorption of phosphorus from aqueous solutions and potential application as slow-release fertilizer - Shanshan Zhu; Yuting Lu; Tao Li; Yine Li; Pengfei Liu; Jiangfeng Teng; Chao Huang; Yuxin Jiang; Ping Wang (Journal of Environmental Chemical Engineering, 2026)

Different land use types around megacities contribute contrasting heavy metal pollution and health risks in soil-leaf vegetable systems - Ling Huang; Wen-Fei Chen; Yue-E Guan; Yan-Ping Pang; Sheng-Gong Yu; Lin Li; Qi Zou; Meng-Qiang Sun; Hang Wei; Zhi-Liang Chen (Environmental Research, 2026)

Mutual activation of g-C3N4 and persulfate synchronizes rapid visible-light-triggered fabrication of multifunctional hydrogels - Mingming Deng; Dagang Zhou; Lin Luo; Boyi Fu; Ping Li; Qi Liu; Chi Huang (Chemical Engineering Journal, 2026)

Corrigendum to: “Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury” [Chem. Eng. J. 524 (2025) 169698] - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2026)

Geomorphological controls on elevational differentiation of sediment 210Pbₑₓ and 137Cs activities in a water-level fluctuation zone - Jinlin Li; Xiubin He; Jie Wei; Qiang Tang; Yuhai Bao; Ping Huang; Shengjun Wu; Xin Gao; Ziqiang Mao (CATENA, 2026)

Corrigendum to “Quercetin attenuates cisplatin-induced mitochondrial apoptosis via PI3K/Akt mediated inhibition of oxidative stress in pericytes and improves the blood labyrinth barrier permeability” [Chemico-Biological Interactions 393 (2024) 110939] - Tian-lan Huang; Wen-jun Jiang; Zan Zhou; Tian-feng Shi; Miao Yu; Meng Yu; Jun-qiang Si; Yan-ping Wang; Li Li (Chemico-Biological Interactions, 2026)

Chemical constituents with chemotaxonomic significance from the whole plants of Chloranthus sessilifolius K.F.Wu - Xin-Yu Chen; Meng-Li He; Wan-Wan Yu; Yang Liu; Yong-Ming Luo; Ling-Ying Huang; Zhi-Ping Li; Fang-You Chen (Biochemical Systematics and Ecology, 2026)

Hematopoiesis could be improved by correcting aberrant bone marrow macrophages polarization in aplastic anemia patients - Chen-Yuan Li; Dan-Dan Chen; Xin-Yan Zhang; Shu-Qian Tang; Meng-Zhu Shen; Ya-Ting Yu; Zhi-Wei Zhang; Zheng-Li Xu; Yuan-Yuan Zhang; Jin-Song Jia; Lan-Ping Xu; Yu Wang; et al. (Science China Life Sciences, 2026)

High-quality genome of guar (Cyamopsis tetragonoloba) provides the new insights into the biosynthesis and origination of galactomannans in Fabaceae family - Yuanhao Ding; Xinglong Zhao; Hui Yao; Shicai Huang; Xuyao Wang; Yayu Chen; Ping Li; Chengzhi Xie; Jiaquan Huang; Zhuang Yang; Haiyan Hu (Plant Cell Reports, 2026)

The aging eye: navigating molecular mechanisms and innovative interventions - Yumeng Lin; Zhongyu Han; Yunfeng Zhang; Ruimin Yuan; Mingyu Huang; Yating Liu; Jun Wang; Chen Xu; Luze Liu; Ping Yu; Qingsong Yang; Liuzhi Zeng; et al. (Biogerontology, 2026)

Osteopontin-driven TGF-β1 signaling via integrin αvβ3-NF-κB axis impairs NK cell function in head and neck squamous cell carcinoma - Zhe Shen; Xin Li; Shi Luo; Yuzhang Gao; Imadoudini Hassimi Safia; Jie Jiang; Xin Qi; Wei Huang; Yalan Liu; Xing Fang; Yaoyun Tang; Ping Wu (Apoptosis, 2026)

Characterization and source apportionment of halogenated organic pollutants in sediments from the Daya Bay, South China Sea - Ren-Jie Shang; Jian-Fang Hu; Ming-Yang Liu; Yao Xiao; Yi-Ting Zeng; Li-Tian Huang; Ping-An Peng (Marine Pollution Bulletin, 2026)

Isolation and whole-genome sequencing of antibiotic-resistant bacteria revealed the reservoir for indigenous antibiotic resistance genes in the deepest ocean sediment of the Challenger Deep - Wenmian Ding; Yuepeng Wang; Yuewei Ma; Ping Chen; Ji Yang; Zhiping Song; Yuguo Wang; Wenju Zhang; Xuan Li; Yanyan Huang; Peng Nan (Marine Pollution Bulletin, 2026)

Unraveling grain quality in cereals: development, heat stress, and molecular mechanisms - Ping Li; Zheng Li; Jiangyue Su; Yanjie Lv; Shuhua Liao; Pu Wang; Shoubing Huang (Food Chemistry, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

Distribution, source, and pollution risk assessment of heavy metals in the coastal sediments of the northern South China sea - Wen Yu; Yuqing Fan; Qinghua Chen; Jing Yang; Xin Li; Wei Huang; Kun Yue; Liuyi Zhang; Ping Ding; Guocheng Hu; Yunjiang Yu (Environmental Pollution, 2026)

Long-term organic amendments accelerate straw decomposition via specialized microbial enrichment in greenhouse vegetable soils - Long Ma; Shaowen Huang; Dali Song; Chao Ai; Ruonan Li; Liying Wang; Ping He; Wei Zhou (Applied Soil Ecology, 2026)

Microplastics promote N2O emissions by enhancing nitrification via ammonia-oxidizing bacteria in estuarine and coastal sediments - Xiufeng Tang; Yingyu Bao; Jun Li; Bolin Liu; Yixuan Huang; Lijun Hou; Patrick K.H. Lee; Ping Han (Water Research, 2026)

Predicting distribution characteristics of PM2.5 concentrations across China combining land use regression model and spatiotemporally weighted stacking machine learning algorithms - Wentao Wang; Ping Zhang; Yuanyuan Han; Fengqian Zhang; Yue Huang; Jinbao Liu; Ying Pan; Wenping Liu; Jian Chen; Mingyao Li; Yong Wang; Yefan Jia; et al. (Journal of Environmental Chemical Engineering, 2026)

Distribution pattern and development of typical antibiotic resistance genes in the continuous-flow aerobic granular sludge-membrane bioreactor system - Yongsheng Jiang; Yu Zeng; Lei Shang; Dehong Bai; Liying Bin; Weirui Chen; Xinyi Chen; Shanglong Wen; Shaosong Huang; Ping Li; Bing Tang (Journal of Environmental Chemical Engineering, 2026)

Fe-CN activated peracetic acid system achieving hydroxyl radical-dominated degradation of organic pollutants - Wei Ren; Xiao-Wen Huang; Dongmei Hou; Zhuoyuan Li; Jingenqi Li; Denglong Chen; Yuehong Ma; Chongli Wu; Qian-Qian Tang; Yi Hu; Long-Shuai Zhang; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Metal mixture exposure and elevated risk of hypertensive disorders in pregnancy: Insights from a case-control study in northwestern China - Xueman Ding; Li Liu; Zhaochun Liu; Shurui Zuo; Yu Huang; Yizhong Yan; Shangzhi Xu; Ping Yao; Menghuan Xiao; Chengxian Dong; Chulin Yan; Xiaoyu Song; et al. (Journal of Environmental Sciences, 2026)

The formation mechanism of ultra-deep gas condensate reservoirs: A case study of the Shunbei No. 4 strike-slip fault zone in the Tarim Basin, NW China - Xin Yang; Hongwei Ping; Zicheng Cao; Lu Yun; Haiying Li; Jun Han; Feng Geng; Cheng Huang; Xinle Zhang; Zhongdeng Lu; Honghan Chen (Journal of Asian Earth Sciences, 2026)

Mechanistic insights into high-pressure-induced structural and thermal changes of wheat starch in flour and dough systems - Yung-Jia Chan; Ping-Hsiu Huang; Xiao-Song Huang; Wen-Chien Lu; Zeng-Chin Liang; Po-Hsien Li (Food Hydrocolloids, 2026)

Andrographolide Alleviates Inflammation in Chronic Obstructive Pulmonary Disease by Inhibiting Alveolar Macrophage Pyroptosis Through the JNK/NLRP3 Pathway - Tingting Zhang; Xiaofeng Li; Zhe Wang; Xin Li; Ping Huang; Xiaoli Zeng; Xiaoju Liu (Cell Biochemistry and Biophysics, 2026)

Pseudosparassis yunnanensis, gen. et sp. nov. (Sclerotiniaceae, Helotiales, Ascomycota) from Yunnan Province, Southwestern China - Yuan-Hao Ma; Qi Zhao; Li-Mei Huang; Ping Liu; Hong-Mei Chai; Yong-Chang Zhao; Hong-Li Su; Ishika Bera; Wei-Min Chen (Mycological Progress, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

High-loading single-atom photocatalysts for high-selectivity conversion of CO2 to ethanol - Long-Shuai Zhang; Feiyao Wu; Shenrui Liang; Qianqian Tang; Hui Li; Huang Zhou; Fanqi Meng; Xunheng Jiang; Haiyan Liu; Qing Sun; Meifeng Wu; Yitao Cui; et al. (Science Bulletin, 2026)

Sustainable postharvest management practices for kiwifruit: Principles, approaches, and future directions - Qinhong Liao; Xiaojiao Li; Shixian Zeng; Wenxuan Chen; Ping Huang; Zihao Wang; Chi Yan; Qiqiang Wu; Qiuhong Niu; Yong Wang; Zhenshuo Wang (Postharvest Biology and Technology, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Potential mechanisms of phosphorus removal in bioelectrochemical systems: The synergy between electrochemical precipitation and the effects of microorganisms - Xinhui Lin; Xiaoxia Huang; Xiaowen Li; Ping Lyu; Yuchen Liu; Xianqiao Tao; Yanhong Jiang (Journal of Water Process Engineering, 2026)

Diapause termination alters the m6A methylation profiles and regulates gene expression associated with early embryonic development in the silkworm (Bombyx mori) - Zhi-Hao Huang; Jia-Yue Yang; Cai-Ping Hou; Shi-Huo Liu; Bing Li; Jie Wang; Shou-jun Huang; Jia-Ping Xu (Journal of Insect Physiology, 2026)

Synergistic technology of liquid nitrogen condensation integrated with pressure swing adsorption for CH4/VOCs recovery: modeling, experiment, and optimization - Suiyang Han; Weiqiu Huang; Xufei Li; Yankang Zhou; Xinchen Tian; Zhanyou He; Fangrui Feng; Ping Xia; Wenlong Xu (Fuel, 2026)

Drying methods impact bioactive compounds in Siraitia grosvenorii fruit: Metabolomic insights - Li Li; Lihong Xie; Ping Yi; Ting Gan; Zhenmei Fan; Min Huang; Shiqi Wang; Dan Luo; Rui Pang; Fenglai Lu; Jinfeng Sheng; Jian Sun; et al. (Food Chemistry, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Co-assembly of natural small molecules from Cordyceps militaris into a carrier-free hydrogel targeting Egr1-CSPG4-AKT signaling for glioblastoma therapy - Yong Hou; Lei Chen; Zongyang Li; Xiangbao Meng; Yuecheng Liu; Fanfan Chen; Weiping Li; Jihu Yang; Xudong Xu; Ping Cui; Guoxu Ma; Guodong Huang (Chemical Engineering Journal, 2026)

Green valorization of invasive alien plants using a novel method of simultaneous hydrothermal treatment and ball milling - Binglei Li; Yi Zhong; Chaoming Li; Xun Tan; Mingquan Lv; Shengjun Wu; Ping Huang; Zhilin Huang; Jiwei Bai; Zhong Chen (Biomass and Bioenergy, 2026)

Metabolomic analysis of coloration mechanism of bamboo sheaths in different cultivars of Chimonobambusa utilis - Yan Lan; Xiao Zhu; Guang-Qian Gou; Ai-Juan Tan; Zhao-Xia Dai; Shi-Ping Huang; Gui-Li Yang (Physiology and Molecular Biology of Plants, 2026)

Genome-Wide Identification and Expression Analysis of the TCP Gene Family in Quinoa (Chenopodium quinoa Willd.) - Yutao Bai; Heng Zhang; Guofei Jiang; Xuqin Wang; Lingyuan Zhang; Ping Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Shan Zhang; Rongbo Li; et al. (Journal of Plant Growth Regulation, 2026)

Correction: Modulation of the immune response by focused ultrasound suppressed brain abscess formation - Zhuo-Hao Liu; Nan-Yu Chen; Chiung-Yin Huang; Ya-Jui Lin; Ping K. Yip; Kuo-Chen Wei; Hao-Li Liu (Drug Delivery and Translational Research, 2026)

Modulation of the immune response by focused ultrasound suppressed brain abscess formation - Zhuo-Hao Liu; Nan-Yu Chen; Chiung-Yin Huang; Ya-Jui Lin; Ping K. Yip; Kuo-Chen Wei; Hao-Li Liu (Drug Delivery and Translational Research, 2026)

Probabilistic large deformation analysis of rainfall-induced slope failures considering spatial variability of saturated hydraulic conductivity - Jian-Ping Li; Shui-Hua Jiang; Jiawei Xie; Jinsong Huang (Bulletin of Engineering Geology and the Environment, 2026)

UAV-SfM coupled PBD simulation of graded rockfall fragmentation and air resistance: validation at Bijiashan, Chongqing - Jian Ping Pan; Lu Li; Wei Gao; Dan Huang; Jia Shu Liao (Bulletin of Engineering Geology and the Environment, 2026)

Rhizosphere fungal community and microbial networks shape N2O emissions and crop yield in a rice-rapeseed rotation system under varying nitrogen levels: A case study from Southwest China - Jin-meng Li; Rong Zhao; Tian-yang Ye; Cong-hua Zhu; Jin Chen; Ping Huang; Xue-qing Yang (Agriculture, Ecosystems & Environment, 2026)

Advanced technologies of artery-on-a-chip: a review of construction strategies and disease models - Shi-Qi Chang; Li Qiao; Oluwatosin David Abodunrin; Lin Zou; Ning-Ping Huang (Angiogenesis, 2026)

Aloperine mitigates cigarette smoke-induced inflammation and pyroptosis by inhibiting the BRD4/NLRP3/GSDMD pathway in chronic obstructive pulmonary disease - Xiaofeng Li; Zhe Wang; Tingting Zhang; Xiaoli Zeng; Xin Li; Kai Liu; Ping Huang; Xiaoju Liu (Toxicology and Applied Pharmacology, 2026)

Histone H3.3 phosphorylation facilitates H3K9me3-heterochromatin formation during retrotransposon silencing and X-chromosome inactivation via H3.3K27me3–CBX7–KAP1 axis - Jun Chen; Jiyu Chen; Zhouliang Yu; Liwei Zhang; Yanchao Liu; Xuan Ouyang; Juan Yu; Menghan Wang; Shangqiang Xie; Ming Wang; Tiantian Zhang; Zhaohui Jin; et al. (Science Bulletin, 2026)

Process parameter optimization for greenhouse gas mitigation during green-waste composting and mechanistic insights from microbe–environment networks in treatments with contrasting outcomes - Xiaowen Li; Min Cao; Wenyuxin Huang; Hao Mei; Pan Luo; Ping Ma; Junhao Zhang; Weiqin Zhu; Miaomiao He; Ying Ding (Journal of Cleaner Production, 2026)

Metal and nonmetal active sites induced by dual-ligand engineering in Cu-MOF/GO composites for enhanced electrocatalytic metronidazole degradation - Ya-ping Guo; Yu-bo Li; Zhi Huang; Yan-ying Liu; Qian Zhang (Journal of Environmental Chemical Engineering, 2026)

Structure-optimized hollow carbon spheres from lignite for advanced lithium–sulfur batteries - Yao Huang; Long-Jun Zhang; Wei Wang; Zhan-Ku Li; Xu Liu; Hong-Lei Yan; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; et al. (Fuel, 2026)

Lactic acid bacteria in Jiangxiangxing Baijiu fermentation: Resource exploration, community succession and their ecological dynamics - Pan Huang; Zhongfu Duan; Shiyuan Ma; Wei Cheng; Qiuxia Li; Dan Huang; Ping Huang; Rongqing Zhou; Jiao Niu; Yadong Zhang; Chongde Wu (Food Bioscience, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Molecularly engineered interfaces drive nano-entanglement architectures for synergistic mechanical amplification in silicone rubber composites - Longjin Huang; Xiaomin Song; Yang Yang; Zihao Song; Sisi Shang; Zheyu Yang; Zihan Wang; Ping Zhang; Shichun Li; Xueyan Zhao; Sheng Cui; Chunhua Zhu; et al. (Chemical Engineering Journal, 2026)

Hydrological inundation legacy and seasonal variation jointly regulate soil respiration by shaping microbial community assembly in reservoir riparian zones - Kai Zhu; Fei Ye; Jiaqing Liu; Wenliu Zhang; Weitao Jia; Songlin Zhang; Jinlin Li; Shengjun Wu; Kang Dan; Yulin Wang; Ping Huang (CATENA, 2026)

PbrRALF5/10 prevents incompatible pollen tube death by reconstructing the methyl-esterified pectin and reactive oxygen species metabolism of pear in vitro - Xiao-Xiong Kong; Tao Chen; Li-Yu Gao; Xu Huang; Xiao Liu; Jing Zhang; Zhi-Ping Zhang; Chun-Lei Wang (Plant Molecular Biology, 2026)

Association between atorvastatin and sarcopenia: a study based on NHANES and FAERS databases - Hao Zhang; Ping Zhang; Xi Luo; Li Pan Zhao; Hua Huang; Qi Hong Ou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Whole-body RNA Sequencing Analysis of the Post-larval Reveals the Sex-biased Gene and MiRNA in the Prawn Macrobrachium rosenbergii - Kun Xie; Yu-Meng Shi; Jin-Xia Yang; Jia-Yan Chen; Xu Huang; Xin-Yu Liu; Li-Ping Chen; Jie Chen; Chao-Ping Lu; Gao-Feng Qiu (Marine Biotechnology, 2026)

Identification and biological control of a pathogenic Aspergillus niger causing soft rot in Citrus unshiu Marc - Meng-ping Huang; Jiang-sheng He; Yi Tu; Xiao-li Ke; Ke Huang (Antonie van Leeuwenhoek, 2026)

Virgibacillus aidingensis sp. nov., a bacterium isolated from a hypersaline sediment in Xinjiang Province, North-west China - Li Yang; Hua-Wei Huang; Juan Wang; Cui-Ping Miao; Yi-Qing Li; Xiang-Tao Cen; Li-Xing Zhao; Wen-Yong Zhu; Shu-Kun Tang (Antonie van Leeuwenhoek, 2026)

Brachymonas moutaii sp. nov., a floc-forming bacterium isolated from a distillery wastewater treatment plant - Yaqi Liu; Hui Wang; Ansi Jiang; Junmei Wu; Bi Chen; Yong Zhang; Siliang Yuan; Yan Huang; Haiyan Zeng; Xin Wang; Dian Jiao; Wei Li; et al. (Antonie van Leeuwenhoek, 2026)

Undescribed dihydro- β -agarofuran sesquiterpenoids from the roots of Tripterygium wilfordii - Ya-Lin Hu; Jia-Li Huang; Chong Wang; Wen-Jie Chen; Jing-Yi Huang; Yi-Ping Xie (Natural Product Research, 2026)

A new isoprenyl-phenol-type meroterpenoid from mangrove endophytic fungus Aspergillus sp. GXNU-Y65 - Fan-Fan Wang; Guo-Bao Huang; Cai-Hong Lu; Li-Jun Chen; Hui-Zhen Chen; Meng-Qin Luo; Ping-Fang Tao; Ming-Xiong Tan; Feng Qin (Natural Product Research, 2026)

Triterpenoid and trichothecenes from a rhizospheric soil-derived Paramyrothecium sp. KMU22107 - Hong-Tao Li; Xing-Yi Guo; Ya-Ting Shao; Wen-Yu Huang; Cui-Ping Miao; Wei Li (Natural Product Research, 2026)

Measuring grazing grassland aboveground biomass and spatial heterogeneity based on UAV LiDAR observation with upscaling samples - Yu-Qing Wu; Li-Biao Guo; Wei-Xian Tan; Ping-Ping Huang; Ming-Ze Ma; Yang Zhao (International Journal of Remote Sensing, 2026)

The bactericidal efficacy of carvacrol against drug-resistant Streptococcus iniae and its protective effects on channel catfish (Ictalurus punctatus) - Lizi Yin; Minmin Wang; Jianing Wu; Xiaonan Li; Fen Chen; Bowen Liu; Yi Geng; Xiaoli Huang; Defang Chen; Ping Ouyang (Aquaculture, 2026)

Performance, metabolism, and resistance of an SMX-stressed continuous-flow AGS-MBR system: Microscopic mechanism of macroscopic instability phenomena - Yu Zeng; Haowei Gao; Huiya Huang; Wenqiang Xiong; Liying Bin; Bingda Liao; Weirui Chen; Xinyi Chen; Shanglong Wen; Ping Li; Shaosong Huang; Bing Tang (Water Research, 2026)

Long-term chemical fertilizer application enhances ammonia oxidizers-mediated soil carbon neutrality - Xueru Huang; Zhuo Zhang; Taoyi Ren; Song Li; Ping Zhu; Jingjing Ma; Zhongjun Jia; Jingkuan Wang; Marcela Hernández (Soil Biology and Biochemistry, 2026)

Insights into the phosphate stabilization and removal mechanism enabled by phosphogypsum-fly ash ceramsite - Simeng Gan; Zhaorui Li; Yunkang Zhang; Fei Wang; Xiaofeng Huang; Yixing Ma; Quxiu Dai; Ping Ning; Kai Li; Xin Sun (Process Safety and Environmental Protection, 2026)

Deciphering spatio-seasonal impacts of agricultural irrigation on water quality evolution and surface water-groundwater interaction in a large irrigation district, northwest China - Muhan Li; Keyi Zhang; Wei Bao; Shen Qu; Guanglei Yu; Yansong Bai; Xu Yang; Zeyuan Liu; Hongli Ma; Ping Miao; Fuyang Huang; Ruihong Yu (Journal of Hydrology, 2026)

Thermal resistance and stability of multilayers embedding probiotic structure - Ping-Hsiu Huang; Chien-Shan Chiu; Wen-Chien Lu; Chang-Wei Hsieh; Po-Hsien Li (Journal of Food Engineering, 2026)

Evolution of rheological properties and prediction of mastic viscoelastic behavior of warm mix asphalt - Meiyan Huang; Jianguo Wei; Ping Li; Yuming Zhou; Yiliang Li; Qilin Fu (Fuel, 2026)

Breaking acidic barriers and thermal defenses: Light-induced membrane disruption and heat synergy for efficient inactivation of Alicyclobacillus acidoterrestris in juice - Bingzhi Li; Wenchao Zhang; Yiya Ping; Liang Zhang; Linpin Luo; Yuechun Li; Guangjun Huang; Jinyou Duan; Jianlong Wang (Food Research International, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

Molecular interface engineering light-driven gellan gum antibacterial films with amplified photothermal-photocatalytic synergy for enhanced cherry tomato preservation - Bingzhi Li; Yangyang Li; Yiya Ping; Liang Zhang; Linpin Luo; Yuechun Li; Wentao Zhang; Guangjun Huang; Jianlong Wang (Chemical Engineering Journal, 2026)

Benzofuran-based covalent organic framework with regular fiber-rod structure for efficient photocatalytic H2O2 production under broad visible light - Ting Xu; Zhongxing Zhang; Zijing Wang; Yihao Zhang; Yayang Wang; Yaowen Wang; Liguang Lin; Ping Xue; Jiming Huang; Mi Tang; Lingjun Kong; Xiangcheng Li; et al. (Chemical Engineering Journal, 2026)

Longitudinal decoupling between sedimentary phosphorus concentrations and sediment sorting in the Three Gorges Reservoir, China - Jinlin Li; Pingsheng He; Xiubin He; Jie Wei; Qiang Tang; Xiaoya Tang; Xin Gao; Ziqiang Mao; Ping Huang; Shengjun Wu (CATENA, 2026)

Statistical characteristics of storm cells and centroid-based probability nowcasts by tracking error - Kao-Shen Chung; Tsai-Jung Lee; Li-Pen Wang; Bing-Zhang Wang; Chieh-Ying Ke; Yi-Hao Tsou; Shin-Gan Chen; Ping-Yu Lin; Treng-Shi Huang (Atmospheric Research, 2026)

Phytochemistry, pharmacology and bibliometrics insight of the genus Callicarpa L.: an extensive review encompassing the years from approximately 2010 to 2024 - Wang Jiang; Si-Rong Huang; Wen-Jie Ma; Yi-Qiu Yi; Ping Li; Zhong-Hui Ma; Zhi-Wei Su (Phytochemistry Reviews, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Lowering cyclosporine trough concentration threshold effectively mitigates acute graft-versus-host disease in children with severe β-Thalassemia post hematopoietic stem cell transplantation - Zhuolin Yang; Xianggui Wang; Xiaojing Wang; Wenjiao Ding; Yiyu Zhang; Qingling Gu; Wenqing Wang; Yousi Miao; Ping Xie; Min Huang; Hua Jiang; Xiaolan Mo; et al. (European Journal of Clinical Pharmacology, 2026)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Tropical tree-mycorrhizal types show divergent phosphorus adaptive strategies after 12-year simulated acid rain - Yuanliu Hu; Ji Chen; Dafeng Hui; Ying-Ping Wang; Xiaolin Huang; Minghui Hu; Yiren Zhu; Yonghui Li; Jianling Li; Deqiang Zhang; Qi Deng (Soil Biology and Biochemistry, 2025)

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Simulating and predicting lake dynamics by fusing HBV modeling, machine learning approach and remote sensing data - Muhammad Naeem; Yongqiang Zhang; Ning Ma; Zixuan Tang; Ping Miao; Xiaoqiang Tian; Congcong Li; Qi Huang; Zhenwu Xu; Longhao wang; Zhen Huang (Journal of Hydrology, 2025)

Contrasting influences of diurnal patterns and rainfall events on riverine CO2 degassing: insights from in situ high-resolution monitoring - Jianhong Li; Tao Zhang; Junbing Pu; Changchun Huang; Shi Yu; Kun Ren; Ping’an Sun; Qiong Xiao (Journal of Hydrology, 2025)

Palladium-catalyzed thermo, photo, and electrocatalytic CO₂ conversion to methanol and formaldehyde: A review of mechanistic pathways using synthetic, biogas, and fossil-derived CO2 - Yen-Yi Lee; Masimukku Srinivaas; I.-Cheng Li; Kapa Keharika; Rajender Boddula; Ramyakrishna Pothu; Sanna Gull; Bo-Wun Huang; Jein-Wen Chen; Prashanth W. Menezes; Guo-Ping Chang-Chien (Journal of Environmental Chemical Engineering, 2025)

Fe2O3@diatomite heterogeneous fenton system for enhancing phosphorus bioavailability in dredged sediment - Wenmin Li; Jian Zhu; Pei Wu; Hongchun Huang; Xindeng Huang; Mengyan Wu; Ying Zhang; Kangrong Xiang; Jiangfeng Teng; Chang Sun; Ao Tan; Mingjing Lei; et al. (Journal of Environmental Chemical Engineering, 2025)

Impact of regionally transported biomass burning on carbonaceous aerosol characterization, contribution and degradation in Pu'er, Southwest China - Jianwu Shi; Wenjun Rao; Chenyang Zhao; Li Deng; Xinyu Han; Wei Du; Jianhong Huang; Senlin Tian; Ping Ning; Jiming Hao; Yaoqian Zhong (Journal of Environmental Sciences, 2025)

Wheat germ peptides enhance hypoxia tolerance by modulating gut microbiota and reprogramming brain energy metabolism in mice - Jing-yang Cai; Ying-Ying Liu; Meng-Cheng Li; Xin-Xin Guo; Ai-Mei Liao; Yin-Chen Hou; Quan-Ping Liu; Yong-Chao Fan; Long Pan; Ji-Hong Huang (Food Bioscience, 2025)

Development of eco-friendly chitosan films enhanced with bioactive citric acid-based deep eutectic agents for sustainable food packaging and fish preservation - Ping Shi; Xin Wang; Sajid Ali; Li-Yan Zeng; Xinhui Xian; Jinling Huang; Shengyun Qin; Yuansen Liu; Hafiz Umer Javed (Food Hydrocolloids, 2025)

Ambient-dried polymer aerogel engineered via interparticle “stringing” towards ultrahigh robustness, flame retardancy and harsh-environment durability - Ting-Ting Li; Ting Wang; Chengxu Xu; Xue Gou; Xi-Ping Huang; Si-Yao Zhong; Zhi-Cheng Fu; Jinni Deng; Wenli An; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Natural compound rhein-based bimetallic nanosheets to induce ferroptosis and activate STING pathway for enhanced cancer immunotherapy - Chang Li; Tiancheng Xie; Xilong Mei; Yu Wen; Mi Huang; Hu Guo; Ping Lu; Xiaoxin Yang; Jun Liu (Chemical Engineering Journal, 2025)

Mechanically robust and rapidly self-recovering hyaluronic acid-based conductive hydrogels via fully physical double-network crosslinking for sensitive strain sensors - Ye-Xiong Huang; Mei-Dan Luo; Dewei Ye; Jinmin Li; Ku Shu; Xian-Ping Chen; Kai Zheng (Chemical Engineering Journal, 2025)

Steering nitrogen and carbon dynamics for functional biochar and emission mitigation via co-pyrolysis of antibiotic-laden sludge and phytoremediation biomass - Zhibin Chen; Jingyong Liu; Ping Zhuang; Dajie Jia; Leyao Tao; Siqi Chen; Fatih Evrendilek; Tao Chen; Wenxiao Huang; Weixin Li (Chemical Engineering Journal, 2025)

Drivers of protistan communities in a subtropical coastal wetland: roles of plant types and soil depths - Zi-Kai Liu; Lu Li; Bowen Huang; Luhong Zhou; Yongxin Lin; Ping Yang; Ju-Pei Shen; Weidong Chen (CATENA, 2025)

Spatiotemporal variation of air quality and its driving mechanism in Poyang lake Eco-economic Zone, China - Qiulin Xiong; Yirong Huang; Zhengkun Xiong; Jiayi Li; Jutao Liu; Ping Yang (Theoretical and Applied Climatology, 2025)

Synergistic effects and mechanism of recombinant viral vector-mediated STAT1 overexpression and STAT3 silencing on glioma U251 apoptosis - Xin-Long Hu; Hong Li; Guo-Dong Zhang; Chao Lin; Ping Huang; Xiu-Feng Chen; Fang Wan; Chang-Wu Dou; Hai-Tao Ju (Molecular Biology Reports, 2025)

Identification of homeobox gene family in Chenopodium quinoa and expression patterns in response to flooding stress during the filling stage - Guofei Jiang; Li Li; Yutao Bai; Xuqin Wang; Lingyuan Zhang; Ping Zhang; Junna Liu; Hanxue Li; Liubin Huang; Shan Zhang; Peng Qin (Genetic Resources and Crop Evolution, 2025)

Prognostic and therapeutic implications related to glycosylation profiles of cancer-associated fibroblasts in colorectal cancer: insights from single-cell and bulk transcriptomics - Keji Chen; Huixia Huang; Zijuan Hu; Yifei Zhu; Yanxi Yao; Yaxian Wang; Jiayu Chen; Yuxue Li; Dawei Li; Ping Wei (Functional & Integrative Genomics, 2025)

Discovering novel type I collagen fragments from Cyprinus carpio supporting bone regeneration - Jianhua Zeng; Miao Chen; Xinglong Wang; Huan Yu; Liang Zhang; Yongxing Peng; Ping Wan; Zhongshi Huang; Fuqiang Ma; Jingtang Li (Functional & Integrative Genomics, 2025)

Multigenerational toxic effects of Butylparaben and Hexylparaben on Moina macrocopa - Xue Lei Hu; Ming Chen; Jin Lan Peng; He Ping Huang; Sui Jun Cai; Jin Ling Liu; Yun Hui Li; Lu Wang (Ecotoxicology, 2025)

Unraveling the functional complexity of the locus coeruleus-norepinephrine system: insights from molecular anatomy to neurodynamic modeling - Chun-Wang Su; Fan Yang; Runchen Lai; Yanhai Li; Hadia Naeem; Nan Yao; Si-Ping Zhang; Haiqing Zhang; Youjun Li; Zi-Gang Huang (Cognitive Neurodynamics, 2025)

Quantitative Evaluation of Gas Injection Contribution Using Fluid Inclusion Data: A Case Study of the Condensate Gas Reservoirs of the Eastern Shunbei Area in the Tarim Basin - Zicheng Cao; Lu Yun; Hongwei Ping; Haiying Li; Feng Geng; Jun Han; Cheng Huang; Xin Yang; Honghan Chen (Journal of Earth Science, 2025)

Exploration of new azole derivatives containing ethanolamine moiety as anti-UC agents by inhibiting NF-κB/MAPK pathways - Ming-Qian Ju; Zheng-Xiao Huang; Qing-Yan Mo; Shuai Liu; Dong-Xue Wang; Yan-Ping Li; Chun-Ping Wan; Ze-Wei Mao (Molecular Diversity, 2025)

Soil and enzymatic C:N:P stoichiometry response to carbon and nutrient input: evidence from long-term fertilization experiments - Qiong Xiao; Yaping Huang; Guoping Chen; Kailou Liu; Yu Jiang; Boku Zhou; Ping Zhu; Xiaori Han; Junyong Ma; Shutang Liu; Shaomin Huang; Aijun Zhang; et al. (Plant and Soil, 2025)

Sorafenib induces intestinal toxicity by disturbing gut microbiota and activating the LPS/TLR4/NF-κB signaling pathway in mice - Yaning Xu; Yongshi Mo; Wenxin Zhou; Meirong Qin; Meifang Li; Guo Yin; Hansheng Yu; Yuchun Chen; Haiyan Du; Yibao Jin; Houshuang Huang; Chong Ma; et al. (Toxicology, 2025)

The soil organic carbon sequestration potential and formation efficiency of China’s temperate grasslands - Lu Yang; Ping Li; Yuntao Wu; Nairsag Jalaid; Weixing Liu; Xiaoqiang Liu; Ziyang Peng; Junsheng Huang; Xiaoxia Zhao; Lubing Jiang; Zhaoyu Peng; Sen Yang; et al. (Science Bulletin, 2025)

Occurrence, distribution, and ecological risks of organic pollutants in global mangrove sediments - Yejiao Sun; Jiangwei Miao; Renjun Huang; Wangqing Tang; Sai Wang; Ping Li; Wei Qian; Jae-Seong Lee; Tuantuan Wang; Xiaoshan Zhu (Journal of Hazardous Materials, 2025)

Mixotrophic Chlorella pyrenoidosa biofilm with enhanced biomass production, microalgal activity, and nutrient removal from nutrient-rich wastewater - Xiongwei Wu; Cong Jin; Chiqian Zhang; Ping Li; Jim Junhui Huang; Jing Wu; Jinhua Wu; Zhiqiang Hu (Journal of Environmental Sciences, 2025)

Sedimentation substantially buries more carbon than nitrogen or phosphorus in the Three Gorges Reservoir, China - Jinlin Li; Xiubin He; Jie Wei; Qiang Tang; Yuhai Bao; Xin Gao; Ziqiang Mao; Xiaoya Tang; Ping Huang; Shengjun Wu (Environmental Research, 2025)

Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2025)

Development of novel smartphone-based micro-electrochemical immunosensors for the point of care testing and typing of Helicobacter pylori in serum and whole blood - Yuhan Wang; Ping Zhang; Wei Fang; Chuxian Zhou; Gengzhou Yang; Wenwei Huang; Lijie Zhang; Xiaoli Zhang; Bing Gu; Minmin Li; Jiajie Liang; Yong Tang (Chemical Engineering Journal, 2025)

Synergistic dual-Lewis sites in cobalt-doped Fe3S4 for enhanced hydrogen peroxide activation and contaminant degradation - Li-Ping Jin; Fan Zhou; Qin Liu; Su-Qin Wang; Meng-Meng Zeng; Xin-Yu Huang; Li Liu; Xiao-Han Yu; Mei-Feng Wu; Jian-Ping Zou (Chemical Engineering Journal, 2025)

[3 + 2 + 1] iridium(III) complexes for high-efficiency saturated red organic light-emitting diodes - Ping Chen; Qingwu Wu; Gui-Yan Yang; Qifei Xie; Sheng Yu; Ming-Yu Teng; Huabo Han; Guo-Li Huang; You-Xuan Zheng; Guangzhao Lu (Chemical Engineering Journal, 2025)

Oxide layer removal effect of F2602 in promoting combustion of multi-metal amphibious energetic composites - Peihui Xu; Juncheng Lai; Longjin Du; Rongrong Li; Ping Huang; Jianzhong Liu (Chemical Engineering Journal, 2025)

Characterization of particle number size distribution and new particle formation in a highly-humid megacity Wuhan, central China - Haoqian Wang; Xiaoxiao Li; Jin Wu; Hao Wu; Yiran Li; Chong Liu; Ning Ma; Ping Zeng; Xuehui He; Jiapeng Ran; Huaying Song; Dandan Huang; et al. (Atmospheric Environment, 2025)

Retraction Note: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2025)

The role of TLR4/NF-kB signaling axis in pneumonia: from molecular mechanisms to regulation by phytochemicals - Jun Yin; Jianxiang Huang; Ping Zhou; Linwei Li; Qin Zheng; Hong Fu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Concentrated mannan oligosaccharide supports grass carp (Ctenopharyngodon idellus) health during Ichthyophthirius multifiliis infection: Histopathological and immunological study - Fulong Li; Ming Xu; Baipeng Chen; Senyue Liu; Yanhao Cao; Yufan Zhang; Gang Lin; Ping Ouyang; Defang Chen; Yi Geng; Xiaoli Huang (Aquaculture, 2025)

Polycyclic polyprenylated acylphloroglucinols with cytotoxicity against human tongue squamous carcinoma cells in vitro from Hypericum curvisepalum - Min-Min Cao; Xian Wei; Jie Huang; Zhong-Qiu Gan; Li-Ping Teng; Zhong-Bo Zhou (Phytochemistry Letters, 2025)

Discovery of a new 1-monoglyceride from Streptomyces albogriseolus JM128 symbiotic with Lendenfeldia sponge - Yun-Ting Zeng; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; You-Ying Chen; Li-Guo Zheng; Chih-Yin Huang; Hsi-Wen Sun; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Quantifying the impact of thermal maturity on carbon isotope variations of marine oils from the Shunbei ultra-deep petroleum system, Tarim Basin - Zhongdeng Lu; Hongwei Ping; Zicheng Cao; Lu Yun; Haiying Li; Feng Geng; Jun Han; Cheng Huang; Honghan Chen (Organic Geochemistry, 2025)

Reducing melamine exposure and oxidative stress markers in melamine-exposed workers: A pragmatic intervention study - Chia-Fang Wu; Chih-Hong Pan; Yu-Ming Hsu; Chiung-Yu Peng; Ching-Mei Cheng; Sih-Syuan Li; Chien-Ping Huang; Ming-Tsang Wu (Journal of Hazardous Materials, 2025)

Z-scheme Cu2O/g-C3N4/Ag heterostructures: A novel approach for simultaneous water pollutant removal and real-time SERS monitoring - Kaiyue Li; Wenhui Li; Ping Huang; Yuquan Zhuo; Ziwen Yang; Bo Wang; Runru Liu; Bing Liu; Enzhu Hou; Shuo Yang; Donglai Han (Journal of Environmental Chemical Engineering, 2025)

Bioaugmentation with novel heterotrophic nitrifying bacteria enhances nitrogen removal in low C/N wastewater: Elucidating nitrogen metabolic traits and reactor-scale validation - Yuji Dong; Tianyi Zhang; Liuan Xie; Jiapeng Ping; Lihong Zhang; Yuxuan Huang; Huiting Song; Chuan Li (Journal of Environmental Chemical Engineering, 2025)

Enhanced aerobic granular sludge cultivation in continuous-flow membrane bioreactors: Evaluating a novel vertical circulation configuration and multi-mechanism approach - Tenglong Dai; Mengci Ni; Liying Bin; Weirui Chen; Ping Li; Xinyi Chen; Shanglong Wen; Shaosong Huang; Bing Tang (Journal of Environmental Chemical Engineering, 2025)

Experimental and mechanistic study on the removal of elemental mercury in coal-fired flue gas by SO2-modified activated coke within a wide temperature range - Lingxuan Chen; Guangqian Luo; Mingyu Yu; Chunhui Sun; Yi Xiao; Yongda Huang; Sheng Chen; Ping Xiao; Shiqing Wang; Xian Li; Hong Yao (Fuel, 2025)

Application potential of submicron-sized bamboo cellulose as natural Pickering emulsion stabilizers: Structural properties and stabilization mechanisms - Chen-long Hou; Hao-tian Wei; Chang Liu; Hui-min Yang; Li-Chun Chen; Jian-ping Xu; Lu-yao Wang; Xiu-hua Rao; Jian-jun Huang; Qing Ge (Food Chemistry, 2025)

Metagenomics-metabolomics integration reveals the impacts and action mechanisms of sulfamethoxazole in a continuous-flow aerobic granular sludge membrane bioreactor: System performance and microbial functional shifts - Wenqiang Xiong; Yu Zeng; Liying Bin; Weirui Chen; Xinyi Chen; Shanglong Wen; Shaosong Huang; Ping Li; Bing Tang (Chemical Engineering Journal, 2025)

Cold crystallization-enabled permanent shape transformation in 4D-printed PLA/TPU composites for personalized wearable devices - Chuanru Zheng; Xi Li; Juan Tan; Anna Tan; Xiuchen Li; Hailiang Ni; Wenhao Yu; Yuefeng Bai; Ping Hu; Wei Min Huang; Hongmei Chen (Chemical Engineering Journal, 2025)

Targeted gene therapy for intracranial aneurysm using SOX17-CRISPRa - Dujie Xie; Yi Yuan; Panyao Long; Juan Huang; Mi Jiang; Yongzhong Tang; Yuanqiang Luo; Cancan Zhang; Ping Zheng; Liang Yang; Yiwei Chen; Xiaobo Li; et al. (Chemical Engineering Journal, 2025)

Chemical constituents of Engleromyces sinensis and their chemotaxonomic significance - Xiao-Xue Jiang; Lai-Wei Li; Xing-Ping Zhang; Ke-Pu Huang; Wen-Jie Ma; Li-Ping Tang; Kou Wang (Biochemical Systematics and Ecology, 2025)

Genome-wide identification and expression analysis of C2H2 zinc finger protein transcription factor in quinoa - Xuqin Wang; Xingmei Zong; Guofei Jiang; Lingyuan Zhang; Yutao Bai; Ping Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Shan Zhang; Peng Qin (Genetic Resources and Crop Evolution, 2025)

A rapid and ultrasensitive CRISPR/Cas12a-based assay for the accurate identification of T-even type phages - Chenhang Jiang; Yang Li; Ping Yu; Mengjun Fang; Di Huang; Xiangming Fang; Zhinan Xu (Biotechnology Letters, 2025)

Impact of Phosphate Solubilizing Bacterial Agent on Cadmium Bioavailability and Microbial Communities in Soil and Cd Accumulation in Lettuce Plants - Yue Yu; Ping Li; Yanhong Wang; Xinzhe Lu; Chunlei Huang; Hanqin Yin (Journal of Earth Science, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Inhalable Inclusion Cocrystal of Exocarpium Citri Grandis Volatile Oil for Treatment of Acute Lung Injury - Ying Luo; Zeyu Li; Guilan Wang; Ergang Liu; Huan Shen; Guilong Zhao; Ping Zhao; Yongzhuo Huang (AAPS PharmSciTech, 2025)

New 1,2,3-triazole-linked (±)-agrimonolide derivatives as anti-ulcerative colitis agents inhibiting JAK1/STAT3 pathways - Xiao Zhang; Ming-Qian Ju; Heng-Li Yang; Chun-Fei Zhang; Mao-Kui Huang; Yan-Ping Li; Chun-Ping Wan; Ze-Wei Mao (Molecular Diversity, 2025)

Quantifying high-temperature-induced reproductive growth imbalance in citrus at anthesis: Insights from the CF-ASPM model - Xia Qiu; Feiyu Zhu; Ping Huang; Hongwen Chen; YaLi Li; Changbing Pu; Zongnan Li; Dan Zhong; Chao Xiang; Jin Chen; Si Wang (Computers and Electronics in Agriculture, 2025)

In situ addition of layered double hydroxides promotes sulfate-dependent anaerobic methane oxidation and microbial community shifts in freshwater-influenced mangroves sediments - Jijuan Ding; Fei Liu; Jing Huang; Ping Li; Junmao Zhang; Bo Wu; Longfei Shu; Zhili He; Cheng Wang (Water Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Changes in cell wall characteristics and expression of MiERF12, MiERF109-like, and MiERF113 during mango softening - Yuhan Long; Lihong Xie; Ping Yi; Fang Huang; Min Huang; Ting Gan; Jian Sun; Li Li; Hao Dong; Qi Wei; Zhenmei Fan; Qiuyu Cheng (Postharvest Biology and Technology, 2025)

Hydrothermal cyclic regeneration performance and synergistic pollutant degradation of spent activated carbon from water purification - Guifang Chen; Mengning Liu; Wei Wang; Zhanyao Li; Fuyu Huang; Xujiang Wang; Shouyan Chen; Ping Zhou (Journal of Water Process Engineering, 2025)

Comparative analysis of microplastic and microbial communities in varied aquatic environments: Disparities in occurrence, interconnections, and ecological implications - Lingfang Fu; Yongxin Guo; Jialiang Tang; Mengdi Yang; Lu Huang; Jieer Xiao; Zhongya Fan; Zhongyang Wang; Jiangyu Zhi; Zhiwei Huang; Huaiyang Fang; Ping Li (Journal of Hazardous Materials, 2025)

The deficiencies in texture, organic matter distribution, and active mineral composition of reservoir sediments constrain the formation of healthy soils - Xun Tan; Sidong Zeng; Binglei Li; Shengjun Wu; Ping Huang; Zhong Chen; Xingxing He; Zhilin Huang; Jiwei Bai (Journal of Environmental Management, 2025)

Construction of double S-scheme heterojunction in MIL-125(Ti)/ZnIn2S4/ZnS QDs to improve interfacial charge transfer and reduction potential for photocatalytic hydrogen production - Xiuxiu Huang; Shijian Zhang; Wenbin Ruan; Xinru Wang; Xiang Li; Shuangshuang Huai; Rui Cheng; Congliang Cheng; Ping Li; Jingjing Xia; Xiufang Wang (Fuel, 2025)

Multifunctional au-DTNB-ag nanoparticles immunoprobes based on color-Raman properties for lateral flow immunoassay detection of Glycinin - Peng Bo Huang; Jing Long Qu; Shuo Yang; Tian Jiao Shui; Huan Huan Yang; Li Ping Cheng; Yang Qin; Jun Xi (Food Chemistry, 2025)

A flexible and efficient UNITID-based access control (UBAC) model for environmental monitoring data - Jinku Huang; Changxiu Cheng; Bin Li; Yang Gao; Ping Li; Jiawei Wan; Jadunandan Dash (Environmental Modelling & Software, 2025)

Unraveling the effect of sorbitol on Cu-based catalysts for the continuous hydrogenation of CO2-derived ethylene carbonate to methanol and ethylene glycol - Tong-Yang Song; Ji-Zheng Zhang; Jun He; Xian-Lang Chen; Xin-Yuan Huang; Ai-Ping Jia; Xiaohong Li; Rong-Rong Li; Ji-Qing Lu (Chemical Engineering Journal, 2025)

Internal encapsulation for enhancing perovskite solar cell stability based on moisture-triggered in situ polymerization - Jingwei Zhu; Jianting Huang; Ping Hu; Wei Yue; Mingdeng Wei; Ying Zhang; Yafeng Li (Chemical Engineering Journal, 2025)

Interfacial electron accumulation of Ir-Co3O4 toward efficient acidic oxygen evolution reaction - Aiying Song; Chao Cai; Ming Jiang; Pengcheng Li; Ping Liao; Yue Huang; Lang Chen; Xuming Yang; Yuanmin Zhu (Chemical Engineering Journal, 2025)

Lysine inhibition of expression of genes encoding type III secretion system in Ralstonia pseudosolanacearum and its virulence in host plants - Liangliang Han; Runxiao Li; Jiajun Huang; Xia Xiao; Ping Ouyang; Tao Liang; Tao Guo; Yasufumi Hikichi; Kouhei Ohnishi; Yong Zhang (Journal of General Plant Pathology, 2025)

A time-domain multi-parameter elastic full waveform inversion with pseudo-Hessian preconditioning - Jian-ping Huang; Zhang Liu; Ke-jie Jin; Kai-lun Ba; Yu-hang Liu; Ling-hang Kong; Chao Cui; Chuang Li (Applied Geophysics, 2025)

Dynamic response analysis of cross-fault tunnel considering source-to-structure seismic input and near-fault effect - Liqun Li; Zhiyi Chen; Ping Lu; Yu Huang (Tunnelling and Underground Space Technology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Oleanane-type triterpenoids from Sabia limoniacea with nitric oxide inhibitory activity - Ping Hou; Liwei Pan; Liuting Peng; Chunqiu Gan; Chenyang Ren; Ruiyun Yang; Weifeng Xu; Chaowen He; Yanlin Cui; Wen Tang; Jun Li; Yan Huang (Phytochemistry, 2025)

Soil mineral-associated and particulate organic matter differentially alleviate the toxic effects of 2,4,6-tribromophenol on arylsulfatase - Yu YANG; Ziquan WANG; Hui HUANG; Yan LI; Jiaqi CUI; Ping LÜ; Haixia TIAN; Mallavarapu MEGHARAJ; Wenxiang HE (Pedosphere, 2025)

BarleyOmics: A comprehensive multi-omics database of barley - Junheng Zhao; Shanggeng Xie; Chenyang Zhang; Zengjie Hu; Xiangqian Lu; Nannan Zheng; Yujie Fu; Jie Yao; Ping Zhou; Danyin Huang; Zhizhong Zhang; Mengdi Li; et al. (Molecular Plant, 2025)

How did the Hukou Waterfall of the Yellow River form? - Hao Liang; Ke Zhang; Jianguo Xiong; Zhongyun Li; Xiu Hu; Ying Xu; Ping Huang; Zhigang Li; Yipeng Zhang; Gege Hui; Kang Liu; Weitao Wang; et al. (Geomorphology, 2025)

Agronomic characteristics, objective quantitative, metabolome and transcriptome analysis reveal the influence of fertilization treatments on fresh leaf characteristics and finished tea quality - Liyue Yang; Xizhe Zhu; Ziming Yu; Bicheng Hu; Ping Liu; Fenglan Zhang; Ming Chen; Jinjin Wang; Youyi Huang; Haibo Yuan; Yeyun Li; Jinjie Hua (Food Chemistry, 2025)

Study on the correlation between Flavobacterium columnare infection and gill injury in Largemouth bass (Micropterus salmoides) and the protective effect of Enoxolone - Chen Li; Yunshan Qiu; Lin Luo; Xinnan Zhou; Hongli Liu; Ping Ouyang; Yi Geng; Defang Chen; Xiaoli Huang (Fish & Shellfish Immunology, 2025)

Initiatorless solar-photopolymerized heterostructured hydrogel with high performance, environmental adaptability, and recyclability - Chenghao Wang; Ping Li; Mingming Deng; Lin Luo; Boyi Fu; Qi Liu; Chi Huang (Chemical Engineering Journal, 2025)

High-quality reference genome and population analysis of allotetraploid Elymus sibiricus provide insight into genome origin and environmental adaptations to the Qinghai-Tibetan Plateau - Xinrui Li; Changbing Zhang; Lili Wang; Gai Huang; Daxu Li; Changmian Ji; Zujun Yang; Minghong You; Lijun Yan; Lili Chen; Wenlong Gou; Xiong Lei; et al. (Science China Life Sciences, 2025)

Revealing the Oxidative Stress-Related Molecular Characteristics and Potential Therapeutic Targets of Schizophrenia through Integrated Gene Expression Data Analysis - Xiu-Mei Zhu; Ji Chen; Hua-Jie Ba; Chun Yang; Jian-Wei Liu; Rui Guo; Shi-Lin Li; Ping Huang; Cheng-Tao Li; Su-Hua Zhang (Molecular Neurobiology, 2025)

Clinical characteristics and outcomes of tuberculosis and non-tuberculous mycobacteria infections: a population-based study of concurrent and sequential infections - Zhen-Tao Fei; Dan-Ping Zhou; Wei Huang; Ping Liu; Qian-Ping Lu; Hao Li; Yang Yang; Dan Ye; Xu-Hui Liu; Lu Xia (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

A Novel Selenite-Reducing Bacterium Bacillus pseudomycoides SA14 Isolated from Se-Enriched Soil and Its Potential Se Biofortification on Brassica chinensis L. - Xianxin Huang; Yanhong Wang; Helin Wang; Xinyan Shi; Chunlei Huang; Hanqin Yin; Yixian Shao; Ping Li (Journal of Earth Science, 2025)

Leaf and Root Traits Show Contrasting Resource Exploitation Strategies, but Converge Along Elevation in the Hengduan Mountain Forests - Jie Song; Sebastian Seibold; Liang‐Liang Ma; Jia‐Yun Zou; Jie Liu; Ming‐Shu Zhu; Wei Zheng; Zhi‐Qiong Mo; Sheng‐Ping Ming; Jin Li; Kun Xu; De‐Zhu Li; et al. (Journal of Biogeography, 2025)
Aim The variations of leaf and root traits in communities are associated with above‐ and below‐ground resource exploitation strategies and are used to infer community assembly processes along environmental gradients. However, little is known about variations in leaf and root traits and their drivers along elevations in mountain forests. Location Yulong Mountain, southeastern Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We measured six leaf traits and seven root traits across 47 woody species and collected environmental variables from forest plots along a 1200 m elevational gradient. We employed linear mixed models to examine how resource exploitation strategies (community‐weighted mean, CWM) and functional diversity (standardised effect size of RaoQ, SES.RaoQ) associated with leaf and root traits varied along elevations. Furthermore, we determined the relative effects of environmental variables on these metrics. Results We observed that the resource exploitation strategy of leaves shifted from an acquisitive to a conservative strategy (higher leaf carbon concentration) with increasing elevation. Conversely, root trait variation exhibited an opposite trend, shifting from a conservative to an acquisitive strategy (higher root branching intensity but lower root diameter and root tissue density) along elevations, potentially influenced by mycorrhizal interactions. We detected functional convergence for leaf and root traits across elevations, with a greater degree of functional convergence at high elevations. Leaf trait convergence was closely linked to soil nitrogen conditions, whereas root trait convergence was associated with soil organic carbon levels. Main Conclusions Our results highlight that the patterns of resource exploitation strategies along elevational gradients are decoupled for leaf and root traits, with distinct environmental factors shaping the convergence of root and leaf traits. We argue that forest communities in mountain ecosystems may modify their resource exploitation strategies and functional diversity through varying combinations of leaf and root traits to improve resilience to future global change.

A Dual-Functional NIR Fluorescent Probe for Detection SO2 Derivatives and Colorimetric Sensing pH as well as its Applications in Food Monitoring and Hepatoma Cells Imaging - Yu Zhu Yang; Lei Ao; Xiao Ping Mao; Gui Yong Li; Xiao Ye Luo; Huan Li Liu; Nan Jun Huang (Journal of Fluorescence, 2025)

Two new species of Russula sect. Heterophyllae (Russulaceae, Russulales) from Jiangxi Province, Eastern China - Lin-Ping Zhang; Li-Hui-Dong Zhao; Xin-Gui Le; Zhen-Wei Mao; Shao-Hua Huang (Mycological Progress, 2025)

The pathological characteristics at different stages and early diagnosis by duplex PCR of Nocardia seriolae disease in largemouth bass (Micropterus salmoides) - Xinnan Zhou; Yunshan Qiu; Chen Li; Ya Huang; Ping Ouyang; Defang Chen; Yi Geng; Xiaoli Huang (Aquaculture, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

In vivo and in vitro degradation and biological toxicity studies of polyesters with varying degradation rates - Ze-Yang Zhang; Wei-Zhen Zheng; Zhi-Chao Zhen; Xiao Li; Ping-Li Wang; Bo Lu; Xiu-bin Yang; Dan Huang; Jun-Hui Ji; Ge-Xia Wang (Journal of Hazardous Materials, 2025)

Effects of pore structures of carbon paper on water management capability of a proton exchange membrane fuel cell - Yu-Ting Liu; Guo-Bao Huang; Xiao-Fang Zhang; Ting-Ting Yao; Li-Xia Cheng; Hong Zhu; Gang-Ping Wu (Fuel, 2025)

One-step forming strategy of highly stable Li4SiO4 for low-concentration CO2 capture - Yu Zhang; Shuo Chen; Shikun Wen; Jiaojiao Li; Rui Yang; Liang Huang; Junya Wang; Ping Ning; Qiang Wang (Chemical Engineering Journal, 2025)

Dual soil–rice interventions of silicon–selenium–calcium composites mitigate cadmium and arsenic accumulation in rice grains - Yang Ping; Zhenzhou Zhang; Jingwen Yu; Xiaofeng Zhai; Cuihong Yang; Peicheng Huang; Qi Liao; Mengying Si; Qingzhu Li; Chongjian Tang; Zhihui Yang (Environmental Geochemistry and Health, 2025)

Key aspects of karst development and tunnel construction countermeasures: a case study of the Ehan expressway - Fangtao Li; Zhiping Hu; Yonghui Zhang; Xuexu An; Huaming Li; Lejun Cai; Ping Huang (Bulletin of Engineering Geology and the Environment, 2025)

Impact of the Yangtze River on Sediment source-to-sink processes in estuarine bays: a study of the Oujiang River Estuary, SE China - Xia Guang; Ping Yin; Ke Cao; Fei Gao; Yuan Tian; Xiangtong Huang; Bin Chen; Meina Li; Jinqing Liu (Frontiers in Marine Science, 2025)
Our study was designed to unravel the provenance signals of sediments from various sediment source-to-sink processes. To achieve this, we systematically collected samples from river basins, estuaries, and offshore waters of the Oujiang River estuary. Analyses of clay minerals and trace geochemical elements (Cr, Th, Sc) were then conducted. Our findings revealed a dynamic pattern of sediment distribution, with the predominant clay minerals in the surface sediment of the offshore area being illite, followed by kaolinite and chlorite, with a minor smectite content. Notably, we observed a gradual increase in the proportions of illite and smectite from the upstream to the estuary, while kaolinite decreased accordingly. The ratios of Cr/Th and Sc/Th in the small mountain rivers also showed a gradual increase, indicating a rising influence of fine-grained sediment from the Yangtze River. Furthermore, we utilized a robust nonlinear mathematical model to determine and quantify the sources and provenance contributions of the clay fraction sediment in the Oujiang River estuary. Our model results revealed that the majority (64%) of the clay fraction sediment in the offshore region of the estuary originates from the Yangtze River. In contrast, sediments from small mountain rivers, including the Oujiang River, contribute an average of 29%, but this can increase to 40% within the Oujiang River estuary and its southern areas. Coastal currents and tides influence the sediment distribution in coastal areas. The Zhe-Min Coastal Current plays a significant role in transporting sediments from the Yangtze River to the estuaries of Zhejiang Province, where they settle in the downstream areas of the current. Moreover, sediment from the Oujiang River is carried southward by the coastal current, most of which is deposited in the estuary and the nearby coastal waters to the south. In conclusion, our study underscores the significant influence of sediments from the Yangtze River on the surface sediments in small mountain rivers and offshore regions near the Zhejiang coastline.

Effects of Maternal Trace Elements Exposure in Early Pregnancy on Maternal Thyroid Hormones and Birth Outcomes - Ting Wu; Tao Li; Chen Zhang; Yan-Hui Hao; Si-Wei Zhang; Xuan-Ping Wang; Yi-Cong Meng; Yan-Ting Wu; He-Feng Huang (Biological Trace Element Research, 2025)

Cepharanthine mitigates NIBV-induced pyroptosis via the MDA5/NF-κB/NLRP3 signaling pathway - Zhenni Liu; Ruoyun Tang; Mengbing Ding; Meiqin Wu; Ying Li; Cheng Huang; Qiurong Qi; Ping Liu; Xiaona Gao; Xiaoquan Guo (Veterinary Microbiology, 2025)

STING-activating pyroptotic nanoparticles for in situ pancreatic cancer vaccination and immunotherapy - Shiyi Shao; Xiaohong Chen; Yuxuan Chen; Meng Wang; Junmin Huang; Jianwei Wang; Xiazhen Yu; Xinya Li; Yao Zhang; Yuan Ping; Qida Hu; Tingbo Liang (Science Bulletin, 2025)

Selenium-calcium-magnesium co-application mitigates cadmium toxicity in rice: Mechanisms of cell wall detoxification and transporter gene regulation - Chukwuma Arinzechi; Peicheng Huang; Pengwei Zhao; Chongjian Tang; Mengying Si; Qi Liao; Qiming Wang; Yang Ping; Qingzhu Li; Zhihui Yang (Rhizosphere, 2025)

Discovery of structurally intriguing diterpenoids as anti-neuroinflammatory agents from mangrove plant Excoecaria agallocha L. via inhibiting macrophage polarization and inflammasome - Jun-Yi Li; Ming-Bin Chen; Ting-Ting Fu; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Jing Zhou; Yong Rao; Zhong-Ping Jiang; Ling Huang (Phytochemistry, 2025)

Early Eocene Metasequoia and Taxodium (Cupressaceae) from Lingbao, Henan Province and their implication for a perhumid climate in central China - Ping Liu; Hui Jia; Li Xu; Yu Li; Ming-Yue Luo; Tian-Qi Dong; Jiao Huang; Cheng Quan (Palaeoworld, 2025)

Comparative mechanisms of PDS-activated antibiotic remediation in groundwater via controlled-release materials with different mesoporous catalysts - Ting Wang; Jing-le Chen; Rui Huang; Hua-li Chen; Cheng Hu; Gang Chen; Kou-ping Chen; Ji-chun Wu (Journal of Environmental Management, 2025)

Co-transport of polyethylene microplastics and antibiotic resistance genes in soil: Influencing factors, mechanisms, and control strategies - Xiao-Ming Lu; Li-Bo Lu; Xi-Cheng Huang; Xue-Ping Liu (Journal of Environmental Chemical Engineering, 2025)

Comparison of microwave-assisted and hot-air-drying method on the physicochemical properties and eating quality of rice bran noodles - Ping-Hsiu Huang; Yu-Tsung Cheng; Wen-Chien Lu; I-Yu Chiu; Chiun-Chung R. Wang; Po- Hsien Li (Food Bioscience, 2025)

Terpene-conjugated curcumin analogs alleviated alcoholic liver injury in rats through mitigation of intestinal barrier abnormalities - Shuaihu Tao; Ruanping Song; Ziyu Wang; Wenjing Xie; Siyuan Xiao; Yangyang Liao; Xinjie Zhang; Qiongdan Hu; Xinxing Tang; Jingyuan Huang; Wan Liao; Hongtao Xiao; et al. (Food Bioscience, 2025)

Transcriptome analysis reveals the mechanism of cortisol through GR regulating the expression of inflammatory cytokines in Siberian sturgeon (Acipenser baerii) after LPS treatment in vitro - Peng Tang; Yinqiu Chen; Defang Chen; Hao Zhu; Shaotong Dai; Jiawen Zhou; Xin Zhang; Xiaoli Huang; Ping Ouyang; Yi Geng; Zhiqiong Li (Fish & Shellfish Immunology, 2025)

Intensive rotational grazing has positive effects on productivity of rangeland - Ping Ge; Jianguo Xue; Yaqian Ru; Yulin Li; Dongxu Li; Peng Han; Ang Li; Jianhui Huang (Agriculture, Ecosystems & Environment, 2025)

Multi-Objective Optimization Based on Response Surface Methodology and Multi-Objective Particle Swarm Optimization for Pipeline Selection of Replenishment Oiler - Yujin Cong; Cheng Meng; Ming Yang; Yong Liu; Ping Yi; Tie Li; Shuai Huang (Journal of Marine Science and Engineering, 2025)
Ship pipeline selection, as a crucial component of ship pipeline design, is often a time-consuming process due to its high complexity. In this study, the response surface methodology combined with the multi-objective particle swarm optimization algorithm was used to optimize the fuel pipeline resistance and its space volume, aiming to select the optimal design scheme for an X-type replenishment oiler. Firstly, a one-dimensional pipeline system simulation model of a replenishment oiler was established based on the Flowmaster software (version 4.2_0 2020), and the fueling process was simulated. The simulation results were validated against the experimental results, and good agreements were obtained. Then, the response surface methodology was employed to establish regression models for the pipeline resistance, pipeline space volume, and imbalance degree of branch flows. Finally, multi-objective particle swarm optimization was used to optimize the target and select the optimal virtual solution from the Pareto front. Constrained by the international application standard, the optimal real solution was determined. Compared with the original scheme, the optimized scheme reduced the resistance by 3.57% for the #1 pipeline system and by 3.51% for the #2 pipeline system, respectively, and the space volume of the pipeline system was reduced by 5.72% while ensuring the flow balance.

Flame retardant contamination and ecological risk analysis in estuarine and marine sediments around an industrial port - Tuan Truong Minh Dang; Li-Man Li; Bo-Wun Huang; Chien-Er Huang; Chien-Hsing Wu; Nicholas Kiprotich Cheruiyot; Guo-Ping Chang-Chien (Marine Pollution Bulletin, 2025)

Five undescribed chromone-phenylpyridone hybrids from Cineraria repanda-derived Penicillium oxalicum with cytotoxic and antibacterial activity - Yu Wei Huang; Jing Guan; Yin Tang; Ren Xiang Tan; Li Ping Lin (Phytochemistry, 2025)

Tracing the Changjiang-derived sediments along the southeast coast of China during the Holocene - Yalong Li; Xin Shan; Xiangtong Huang; Zhanghua Wang; Jianhua Gao; Ping Yin; Quanhong Zhao; Juan Xu; Zhen Song; Shouye Yang (Global and Planetary Change, 2025)

Vine tea (Ampelopsis grossedentata) ameliorates chronic alcohol-induced hepatic steatosis, oxidative stress, and inflammation via YTHDF2/PGC-1α/SIRT3 axis - Qihan Luo; Jiang Qiu; Minxia Chen; Na Yang; Xinyue Li; Shuo Huang; Qing Ma; Zongyuan Li; Dayong Lou; Yu Du; Li Chen; Qing Shen; et al. (Food Research International, 2025)

Unraveling Spatiotemporal Metabolic Perturbation of Amino Acids Associated with Ischemia–Reperfusion Injury by MALDI MS Imaging - Kening Li; Yingying Gong; Wenqiao Chang; Jieping Yan; Ying Hu; Zongfu Pan; Ping Huang (Molecular Neurobiology, 2025)

Evaluation of the antibacterial activity and mechanism of cannabigerol against drug-resistant Streptococcus iniae in vitro - Jianing Wu; Minmin Wang; Tingke He; Xiaonan Li; Bowen Liu; Fen Chen; Yi Geng; Weiming Lai; Xiaoli Huang; Defang Chen; Ping Ouyang (Archives of Microbiology, 2025)

Optimized Multiple Unmanned Surface Vehicle Strategies for Target Tracking with Field of View Constraints - Kai Xue; Zeyu Xu; Ping Wang; Qiuhong Li; Zhiqin Huang; Decheng Kong (Journal of Marine Science and Engineering, 2025)
Unmanned surface vehicles (USVs) have garnered significant interest due to their potential in various maritime applications, particularly target tracking. However, when USVs perform rotational motion around a target, their operations are often hindered by limited fields of view (FOVs) within formations. In this paper, we establish a constraint propagation model to integrate formation constraints, motion constraints, and FOV constraints. Then, we propose four strategies to enforce FOV constraints. The proposed strategies are divided into two categories: those that adjust formation radius and those that adjust rotational velocity. The advantages and disadvantages of each approach are systematically analyzed, highlighting their suitability for various operational scenarios. The effectiveness and robustness of these strategies are validated through simulations.

Four new constituents from the fruits of Cyclocodon lancifolius (Roxburgh) Kurz - Meng-Jie Ma; Wei Wu; Bei Tian; Li-Ping Shen; Tong Wu; Chun-Yue Huang; Xu-Dong Mao; Xiao Hu (Natural Product Research, 2025)

Three megastigmane glycosides from the stem of Mallotus barbatus - Yanling Chang; Xiaoqin Liang; Yan Huang; Chenyang Ren; Ping Hou; Liwei Pan; Jun Li (Natural Product Research, 2025)

Dynamic analysis of fungal community and metabolome associated with postharvest diseases in banana peel under natural condition - Ping Yi; Ming Zhao; Fang Huang; Li Li; Jian Sun; Lihong Xie; Dongning Ling; Jiemin Li; Min Huang; Ting Gan; Yayuan Tang; Changbao Li; et al. (Postharvest Biology and Technology, 2025)

Graph-based pangenome provides insights into structural variations and genetic basis of metabolic traits in potato - Xiaoling Zhu; Rui Yang; Qiqi Liang; Yuye Yu; Tingting Wang; Li Meng; Ping Wang; Shaoyang Wang; Xianping Li; Qiongfen Yang; Huachun Guo; Qijun Sui; et al. (Molecular Plant, 2025)

Cooperation of Lactoplantibacillus plantarum and polyethylene microplastics facilitated the disappearance of tetracycline during anaerobic fermentation of whole plant maize - Yubo Zhang; Pan Wang; Yu Tang; Chaosheng Liao; Xiaolong Tang; Pai Hou; Cheng Chen; Xiaokang Huang; Guangrou Lu; Lin Li; Mingjie Zhang; Fuxiang Li; et al. (Journal of Hazardous Materials, 2025)

Preparation of electrospun ZIF-67/PVP/PVDF composite nanofiber membranes for efficient tetracycline removal from water - Shaolin Deng; Jing Zhang; Xiaolin Yue; Ping Li; Anhong Li; Zehua Huang; Wenyuan Tan (Journal of Environmental Chemical Engineering, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Unveiling the secrets of the bistability of aerobic granular sludge in a continuous flow membrane bioreactor for treating real municipal wastewater - Biao Yang; Liying Bin; Weirui Chen; Xinyi Chen; Ping Li; Shanglong Wen; Shaosong Huang; Zhiqi Zhang; Bing Tang (Chemical Engineering Journal, 2025)

Identification of quinoa B3 gene family and its expression pattern in response to low temperature stress - Lingyuan Zhang; Yanbo Xia; Guofei Jiang; Xuqin Wang; Yutao Bai; Ping Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Shan Zhang; Peng Qin (Genetic Resources and Crop Evolution, 2025)

Hydrochemical insights into spatiotemporal characteristics of groundwater salinization and health risk assessment of fluoride in the south bank of Yellow River irrigation area, Northwest China - Muhan Li; Shen Qu; Guanglei Yu; Yansong Bai; Xu Yang; Zeyuan Liu; Rina Wu; Hongli Ma; Ping Miao; Fuyang Huang; Ruihong Yu (Environmental Geochemistry and Health, 2025)

Effects of pre‐experimental fasting and sheltering on the swimming performance and oxygen consumption of juvenile grass carp ( Ctenopharyngodon idella ) - Malik Haris Ali; Ying‐ping Huang; David Johnson; Wei‐ming Li; Xi Yuan (Journal of Fish Biology, 2025)
This study investigated the effects of pre‐experimental fasting for 2, 7, and 14 days under both unsheltered (12 h dark–12 h light) and sheltered conditions on the critical swimming speed ( U crit ) and oxygen consumption (MO 2 ) of juvenile grass carp, using a modified swim respirometer. Key findings include (1) the U crit of test fish decreased significantly, by 28%, after fasting for 14 days and sheltering intensified the impact to a 43% decrease, and (2) fish anaerobic capacity decreased after 7 days but increased after 14 days, and was enhanced by sheltering conditions. These findings are important as they indicate that fasting and sheltering can impair grass carp survival and disrupt river ecosystem balance, highlighting the need for habitat conservation.

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

A mini review of Liparis species: an ornamental genus with considerable medicinal value - Xiao-Bing Chen; Li-Yun Huang; Min Zhou; Zhi-Jie Ling; Yan-Ping Liu; Xi-Lin Ouyang (Natural Product Research, 2025)

RIPK3 activation of CaMKII triggers mitochondrial apoptosis in NIBV-infected renal tubular epithelial cells - Ying Li; Qiurong Qi; Yifei Chen; Mengbing Ding; Manzi Huang; Cheng Huang; Ping Liu; Xiaona Gao; Xiaoquan Guo; Zhanhong Zheng (Veterinary Microbiology, 2025)

Untargeted qualitative and targeted quantitative analysis of saponins reveal differential chemotypes of Gynostemma pentaphyllum and G. longipes from different geographical origins - Hai-Zhen Liang; Mei-Yan Wang; Guang Yang; Gang Li; Jie Zhang; Lan Yao; Yi Nan; Chang-Liang Huang; Xiao-Juan Chen; Juan Song; Feng Cao; Bao-Lin Guo; et al. (Food Chemistry, 2025)

Liubao insect tea polyphenols ameliorate DSS-induced experimental colitis by protecting intestinal barrier and regulating intestinal microbiota - Xinyu Feng; Yanwen Chen; Lina Luo; Zhoutao Fang; Shicheng Ma; Zhongxia Li; Jing Huang; Yani Pan; Helin Lv; Shuying Gong; Xiaodong Zheng; Fangyuan Fan; et al. (Food Chemistry, 2025)

A method for the identification and evaluation of Glycyrrhiza germplasm based on DNA barcodes and leaf micromorphology - Zhenzhu Du; Wenbin Xu; Yuxia Wang; Zhancang Ma; Ping Yan; Gang Huang; Hongbin Li (Flora, 2025)

Construction of non-noble decorated Z-scheme Bi-BiVO4-Bi12TiO20 for enhanced full solar-spectrum driven photocatalytic activity - Jinhai Li; Hongkai Huang; Pili Lu; Zao Zeng; Ping Zhang; Yongpeng Wang; Tianhao Li; Xiaocan Li; Changxiong Luo (Environmental Research, 2025)

Synergistic neurotoxicity of clothianidin and photoaged microplastics in zebrafish: Implications for neuroendocrine disruption - Ping Ding; Yajing Han; Yanan Sun; XiaoXia Chen; Qing Ge; Wei Huang; Lijuan Zhang; Adela Jing Li; Guocheng Hu; Yunjiang Yu (Environmental Pollution, 2025)

Proteomics analysis reveals the antagonistic interaction between high CO2 and warming in the adaptation of the marine diatom Thalassiosira weissflogii in future oceans - Jiamin Lin; Jingyao Li; Xiao Liang; Hao Zhang; Baoyi Peng; Leyao Xu; Yuan Jia; Bin Huang; Fangzhou Liu; Peixuan Liu; Mengcheng Ye; Fenghuang Wu; et al. (Environmental Pollution, 2025)

Defective Zn1-xCuxS nanosheet as efficient and durable cathode catalyst for photo-assisted Li-O2 batteries - Cong-Cong Dang; Yi-Ping Liu; Yu-Xin Huang; Xin-Yi Zhang; Zhen-Yi Gu; Jun-Ming Cao; Jin-Zhi Guo; Li-Ming Gao; Xing-Long Wu; Yi-Chun Liu (Chemical Engineering Journal, 2025)

A study on iron-composite polymer propellants for improved plasma generation in electric propulsion systems - Chao-Wei Huang; Ping-Han Huang; Zong-Ying Yang; Yueh-Heng Li (Chemical Engineering Journal, 2025)

Transforming behavior and removal mechanism of phosphorus from municipal wastewater in a continuous flow aerobic granular sludge-membrane bioreactor: Unveiling the functional genes associated with phosphorus metabolism - Bingduo Wang; Mengci Ni; Yu Zeng; Biao Yang; Lei Shang; Liying Bin; Weirui Chen; Ping Li; Xinyi Chen; Shanglong Wen; Shaosong Huang; Bing Tang (Chemical Engineering Journal, 2025)

Corrigendum to “Chargeable persistent luminescence 3D-printed scaffolds: A stepwise tactic for osteosarcoma treatment” [Chem. Eng. J. 479 (2024) 147436] - Rui Huang; Ni Ni; Yun Su; Li Gu; Yahan Ju; Dandan Zhang; Jipeng Li; Meiqi Chang; Yu Chen; Ping Gu; Xianqun Fan (Chemical Engineering Journal, 2025)

Skin-like soft yet robust hydrogels with rapid mechanical and electronic responses - Longya Xiao; Yiwan Huang; Sanyu Qian; Shijun Long; Hongjie Jiang; Ping Rao; Xuefeng Li (Chemical Engineering Journal, 2025)

Multi-omics analysis of the accumulation mechanism of flavonoids in rice caryopsis under blue light - Ping Zhang; Yongsheng Tang; Juxiang Zhang; Junna Liu; Li Li; Hanxue Li; Liubin Huang; Guofei Jiang; Xuqin Wang; Lingyuan Zhang; Yutao Bai; Peng Qin (Plant Cell Reports, 2025)

Therapeutic Potential of TUBB6 Inhibition for Hematoma Reduction, Microtubule Stabilization, and Neurological Recovery in an In Vivo Model of Intracerebral Hemorrhage - Jun-Yao Huang; Qiang Ma; Ya-Jie Qi; Zhi-Yao Wang; Xiao-Guang Liu; Yi-Ming Zhu; Yu-Ping Li (NeuroMolecular Medicine, 2025)

Growth, biochemical indexes, and intestinal microbiota response of red tilapia (Oreochromis spp.) under different densities and feeding frequencies in the land-based aquaculture tank - Yu-Xiang Xie; Jun-Neng Liang; Gen Kaneko; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Qiong Yang; Zhen-Ping Liao; Xue-Ming Yang; Hong-ping Zhang; Lin-Yuan Jiang; et al. (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

An integrated photocatalytic redox architecture for simultaneous overall conversion of CO2 and H2O toward CH4 and H2O2 - Muhammad Salman Nasir; Bowen Sheng; Ying Zhao; Haotian Ye; Jun Song; Jinglin Li; Ping Wang; Tao Wang; Xinqiang Wang; Zhen Huang; Baowen Zhou (Science Bulletin, 2025)

Evaluation of the shear stability of aerobic granular sludge from a pilot-scale membrane bioreactor: Establishment of a quantitative method - Biao Yang; Bingduo Wang; Liying Bin; Weirui Chen; Xinyi Chen; Ping Li; Shanglong Wen; Shaosong Huang; Zhiqi Zhang; Bing Tang (Journal of Environmental Sciences, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Multifunctional Lactiplantibacillus plantarum SQ1 from Baijiu Daqu: Application of histamine degradation and probiotic potential in yogurt production - Wenhua Tong; Haoran Xu; Ping He; Yutao Li; Yang Zhang; Zhijiu Huang; Huibo Luo; Ying Yang; Dong Li; Zhifeng Zhao (Food Research International, 2025)

Mantle induced hydration and oxidation of intracontinental granite sources in the North China Craton - Chuan-Mao Yang; Yi-Gang Xu; Xiao-Ping Xia; Jin-Hui Yang; Xiao-Long Huang; Christopher J. Spencer; Jin-Feng Sun; Ze-Xian Cui; Meng-Jing Li; Wan-Feng Zhang; Qing Yang (Earth and Planetary Science Letters, 2025)

Corrigendum to “Application of Mo2C for enhancement of co-catalytic performance of Fe3+/PS based fenton-like reaction in degrading tetracycline hydrochloride” [Chem. Eng. J. 474 (2023) 145508] - Hao Cheng; Yi Wen; Chao Huang; Ping Wang; Chengyou Sun; Chongling Feng; Jialu Xu; Li Du; Ting Yan; Min Cheng (Chemical Engineering Journal, 2025)

Insights into the formation and development of membrane fouling in a continuous flow aerobic granular sludge membrane bioreactor - Mengci Ni; Juan Jiang; Biao Yang; Bingduo Wang; Liying Bin; Weirui Chen; Ping Li; Shaosong Huang; Bing Tang (Chemical Engineering Journal, 2025)

Megastigmane glycoside and phenol glycosides from the bark of Mallotus barbatus - Chenyang Ren; Ping Hou; Jian Li; Yan Huang; Liwei Pan; Liuting Peng; Chunqiu Gan; Xinlan Guan; Jun Li (Natural Product Research, 2025)

Stochastic hazard assessment framework of landslide blocking river by depth-integrated continuum method and random field theory - Shui-Hua Jiang; Jian-Ping Li; Guotao Ma; Mohammad Rezania; Jinsong Huang (Landslides, 2025)
Landslide-induced barrier dams pose a threat to the safety of humans, livestock and nearby infrastructures. The efficient assessment of landslide blocking river is crucial for disaster prevention and mitigation solutions. This study proposes a novel stochastic assessment framework to evaluate the landslide blocking river through the prediction of their deposition depths and considering the heterogeneity of shear strength parameters on the potential sliding surface. The depth-integrated continuum method (DICM) is used to simulate the landslide runout process. Using an enhanced Karhunen-Loève expansion (KLE) method, the spatial variations in soil's shear strength parameters are modeled by random fields to incorporate the effects of soil's spatial heterogeneity on the landslide deposition pattern. Subsequently, the multi-response surrogate model is constructed to relate the random field variables to the deposition depths based on extreme gradient boosting (XGBoost). To improve the performance of the surrogate model, principal component analysis (PCA) and sliced inverse regression (SIR) methods are employed for the dimension reduction of output and input variables, respectively. Furthermore, the algorithm for river blockage identification is developed to search for the deposition ridges. To demonstrate the capability of the stochastic assessment framework, an example of the first Baige landslide in Tibet, China is simulated, and the affected region and deposition depths of the landslide are predicted to calculate the probability of river damming. The presented methodology provides a practical means for improving the landslide blocking river prediction and new insights for early warning and risk mitigation.

Plasma Ionomic Profile and Interaction Patterns in Coronary Artery Disease Patients - Qing-Qing Zhao; Xian-Long Shu; Zhen Yuan; Qian Gao; Ying Huang; Yuan-Qing Yang; Li-Ming Peng; Guo Wang; Xiao-Ping Chen; Bi-Lian Chen; Jie Tang (Biological Trace Element Research, 2025)

Effect of cortisol through GR regulated inflammatory cytokine expression and apoptosis of Siberian sturgeon (Acipenser baerii) after LPS treatment - Peng Tang; Hao Zhu; Defang Chen; Yinqiu Chen; Shuhuang Chen; Youlian Liu; Xin Zhang; Xiaoli Huang; Zhiqiong Li; Ping Ouyang; Yi Geng (Aquaculture, 2025)

Isolation, identification and histopathological observation of Francisella noatunensis subsp. orientalis from Nile tilapia (Oreochromis niloticus) - Ming Xu; Fulong Li; Baipeng Chen; Yongqiang Deng; Defang Chen; Yi Geng; Ping Ouyang; Xiaoli Huang (Aquaculture, 2025)

Pathological and molecular characteristics of a new infectious Streptococcus agalactiae from farmed Schizopygopsis pylzovi in southern China - Baipeng Chen; Ming Xu; Fulong Li; Zao He; Ping Ouyang; Defang Chen; Yi Geng; Xiaoli Huang (Aquaculture, 2025)

Study on the hydrolysis characteristics of polymeric aluminum chloride forced by fine bubbles and its key factors affecting the efficiency and capacity of forcing hydrolysis - Xiaojiang Huang; Kunyu Chen; Zhiqiang Zhang; Chunbo Li; Ping Li; Xuan Wang; Jinsuo Lu (Water Research, 2025)

Evaluation of PM2.5 bound microplastics and plastic additives in several cities in Taiwan: Spatial distribution and human health risk - Chien-Hsing Wu; Tuan Truong Minh Dang; Justus Kavita Mutuku; Li-Man Lin; Bo-Wun Huang; Guo-Ping Chang-Chien (Science of The Total Environment, 2025)

Functionalization of waste-derived artificial aggregates: A state-of-the-art review - Lan-Ping Qian; Ling-Yu Xu; Bo-Tao Huang; Yi Li; Jirong Lan; Fuyuan Gong; Hong Guan (Resources, Conservation and Recycling, 2025)

Seven undescribed compounds from dried flower buds of Ochrocarpus longifolius - Shu-Lan Liu; Xue-Ling Huang; Shun-Hua Zhong; Yong-Hui Ma; Feng Wei; Yu-Ye Zhang; Jin Li; Ke-Jian Pang; Ping Zhao; Xin-Zhou Yang (Phytochemistry, 2025)

Penicipyrrolizidinones A−C, three pyrrolizidinone alkaloids with unprecedented skeletons from the mangrove-derived fungus Penicillium sp. DM27 - Zhenling Chen; Jing-Jing Zhang; Cheng-Yun Huang; Wei-Chen Chen; Li-Ming He; Qing-Qing Tang; Kong-Kai Zhu; Jing Li; Ping Gao; Meng-Ke Zhang; You-Sheng Cai (Phytochemistry, 2025)

Review: Development and application of porous materials to antibiotic drug adsorption and removal - Chao-Ping Hou; Qiang Wang; Qi Liu; Zhi-Guang Li; Chang-Liang Ke; Xu-Feng Wang; Ke Huang (Journal of Water Process Engineering, 2025)

Flooding increases plant-derived carbon accumulation in soils of aquatic-terrestrial ecotone - Yiguo Ran; Ziqiang Mao; Hanzhong Jia; Xianjing He; Shaopan Xia; Fei Ye; Chamindra L. Vithana; Siyue Li; Shengjun Wu; Ping Huang (Journal of Environmental Management, 2025)

Structural characterization and proteomic profiling of oviposition secretions across three rice planthopper species - Jia-Bao Lu; Peng-Peng Ren; Ying Tian; Yan-Yan Yang; Qing-Kai Feng; Xiao-Ya Zhang; Fang He; Hai-Jian Huang; Jian-Ping Chen; Jun-Min Li; Chuan-Xi Zhang (Insect Biochemistry and Molecular Biology, 2025)

Study on the condensate gas phase behavior in Nano-porous media - Ping Wang; Yuepeng Jia; Junjie Zhong; Wensong Huang; Wei Ding; Peng Lian; Xiangwen Kong; Li Liu; Zibin Zhao (Fuel, 2025)

Responses of microbial communities to the addition of different types of microplastics in agricultural soils - Ke Li; Qihao He; Jian Zhu; Jieying Wang; Chang Sun; Ao Tan; Xiaoqi Zhao; Yuanhao Peng; Chao Huang; Jingju Cai; Ping Wang; Zhiming Liu (Environmental Pollution, 2025)

In situ reactivation of aerobic granular sludge in a membrane bioreactor after long-term storage: Revealing the variation in metabolic pathways under restored bioactivity - Yu Zeng; Bingduo Wang; Liying Bin; Weirui Chen; Ping Li; Xinyi Chen; Shanglong Wen; Shaosong Huang; Bing Tang (Chemical Engineering Journal, 2025)

Nanoplastic-mineral heteroaggregation under varying degrees of plastic pollution: Implications for antibiotic adsorption in aquatic systems - Xiupei Zhou; Aoze Li; Marko Cerne; Sophie MacRae; Ian Eggleston; Hongtao Qiao; Xiaoyun Li; Guoyong Huang; Ping Wang; Jian Zhao; Baoshan Xing (Chemical Engineering Journal, 2025)

Interfacial [Ti-O-M] bonds reinforced delectric responses in MXene/transition metal sulfide aerogels for efficient electromagnetic wave attenuation - Baojun Wang; Fangzhi Huang; Ping Zhang; Shikuo Li; Hui Zhang (Chemical Engineering Journal, 2025)

The complex interplay of flooding intensity and land use on soil microbial communities in riparian zones: Insights for ecological restoration - Kai Zhu; Fei Ye; Yu Mei; Weitao Jia; Xiai Zhu; Shuzhen Li; Shengjun Wu; Songlin Zhang; Ping Huang (CATENA, 2025)

Heavy metal emissions from on-road vehicles in Xia-Zhang-Quan metropolitan area in southeastern China from 2015 to 2060: impact of vehicle electrification - Zhe-Nan Wen; Qi-Yu Miao; Jiang-Ru Chen; Shui-Ping Wu; Li-Xiong He; Bing-Qi Jiang; Yi-Jing Liu; Zhi Huang (Environmental Science and Pollution Research, 2024)

International mangrove carbon sink research analysis - Youpeng Xiao; Chenglin Li; Xuxia Li; Yudong Wang; Ping Sun; Xu Xu; Haipeng Wang; Yimeng Chen; Junchuan Lin; Guisong Huang; Zhenguo Huang; Wang Xu (Regional Studies in Marine Science, 2024)

Melatonin protects spermatogenic cells against DNA damage and necroptosis induced by atrazine - Tian-Ning Yang; Ning-Ning Huang; Yu-Xiang Wang; Ping-An Jian; Xiang-Yu Ma; Xue-Nan Li; Jin-Long Li (Pesticide Biochemistry and Physiology, 2024)

Discovery of polyoxygenated briaranes from octocoral Briareum stechei - Yue-Wen Chuang; Wei-Chen Ting; Su-Ying Chien; Li-Guo Zheng; Chih-Yin Huang; Zhi-Hong Wen; Yu-Jen Wu; Junichi Tanaka; You-Ying Chen; Jui-Hsin Su; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Advanced ceramic membranes: Novel strategies for sulfamethoxazole removal in wastewater treatment - Yen-Yi Lee; Guo-Ping Chang-Chien; I.-Cheng Li; Bo-Wun Huang; Minh-Ky Nguyen; Minh-Thuan Pham; Chien-Hsing Wu (Journal of Environmental Chemical Engineering, 2024)

Closed-loop recycling of biodegradable poly(butylene adipate-co-terephthalate) based on hydrolysis and repolymerization strategy - Wei-Zhen Zheng; Xiao Li; Jing Xie; Ze-Yang Zhang; Ping-Li Wang; Dan Huang; Zhong-Lai Ren; Jun-Hui Ji; Ge-Xia Wang (Journal of Environmental Chemical Engineering, 2024)

Snow depth retrieval method for PolSAR data using multi-parameters snow backscattering model - Haiwei Qiao; Ping Zhang; Zhen Li; Lei Huang; Zhipeng Wu; Shuo Gao; Chang Liu; Shuang Liang; Jianmin Zhou; Wei Sun (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Highly Efficient AIE-Active palmatine photosensitizer for photodynamic inactivation of Listeria monocytogenes in apple juice preservation - Shiyu Peng; Qianying Li; Hui Wei; Ping Li; Shuyuan Liu; Lijuan Nie; Yuankui Leng; Xiaolin Huang (Food Research International, 2024)

The remediation performance and mechanism for tetracycline from groundwater using controlled release materials containing mesoporous MnOx with different morphology - Ting Wang; Jing-le Chen; Rui Huang; Li-guang Wu; Kou-ping Chen; Ji-chun Wu; Hua-li Chen (Environmental Pollution, 2024)

Single-cell transcriptome analysis of the mouse lungs during the injury and recovery periods after lipopolysaccharide administration - Hou-Ping Wang; Jian He; Jian-Rong He; Dan-Dan Li; He Huang; Bing Chen (Inflammation Research, 2024)

Anionic surfactant-activated remediation of Pb, Cd, As contaminated soil by electrochemical technology - Ping Zhang; Penggang Li; Yang Ping; Hao Xu; Zhenzhou Zhang; Feiping Zhao; Gai Zeng; Peicheng Huang; Zhihui Yang (Science of The Total Environment, 2024)

Dynamic evolution of particulate and gaseous emissions for typical residential coal combustion - Siyuan Li; Dantong Liu; Xiaotong Jiang; Ping Tian; JiuJiang Sheng; Yangzhou Wu; Kang Hu; Kai Bi; Ruijie Li; Delong Zhao; Mengyu Huang; Shaofei Kong; et al. (Science of The Total Environment, 2024)

Impacts of food additives on gut microbiota and host health - Ping Li; Ru Qu; Ming Li; Ping Sheng; Liang Jin; Xiaochang Huang; Zhenjiang Zech Xu (Food Research International, 2024)

Uncovering the Shuixian tea grades hierarchy in Chinese national standard: From sensory evaluation to microstructure and volatile compounds analysis - Yanping Lin; Yibiao Huang; Xia Liu; Yani Pan; Xinyu Feng; Haowei Guo; Xiaolan Li; Yike Tao; Ping Chen; Qiang Chu (Food Chemistry, 2024)

1-Dimensional metal Nitride-Supported platinum nanoclusters for Low-Temperature hydrogen production from formic acid - Liang Qiu; Bowen Sheng; Haotian Ye; Ping Wang; Jinglin Li; Ying Li; Yixin Li; Tianqi Yu; Muhammad Salman Nasir; Xinqiang Wang; Hu Pan; Zhen Huang; et al. (Chemical Engineering Journal, 2024)

Population pharmacokinetics of fluconazole for prevention or treatment of invasive candidiasis in Chinese young infants - Honghong Wang; Dandan Li; Yongjiang Jiang; Jing Liang; Qiaoai Yu; Linghong Kuang; Yuling Huang; Dongjie Qin; Ping Li; Jing He; Feng Xu; Xueli Li; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Characterization and genomic analysis of phage vB_SmaP_c9-N, a novel Stenotrophomonas maltophilia podophage with antibiofilm activity - Yaosheng Xi; Wei Zhou; Xiao Li; Xiangru Lan; Qili Yang; Yu-Ping Huang (Archives of Virology, 2024)

Analysis of Impact of Control Strategies on Integrated Electric Propulsion System Performance During Icebreaking Process - Liang Li; Ping Yi; Shen Wu; Shuai Huang; Tie Li (Journal of Marine Science and Engineering, 2024)
Developing an efficient power system is an important way for icebreakers to respond to high maneuverability and strong fluctuation loads under icebreaking conditions. The performance of power systems under short-period, regularly fluctuating load-sea conditions has been intensively studied. However, the performance of the power system in the face of a long-period, stochastic multi-frequency fluctuation icebreaking process has not been fully explored, especially the parameter uncertainty and battery cycle life. In this study, an integrated electric propulsion system with an optimal control strategy is suggested for improving the power system’s dynamic performance and battery cycle life. First, an energy flow model with a diesel–electric unit as the main body and coupled energy storage system/hybrid energy storage system has been constructed. A comparative analysis of rule-based and optimization-based energy management strategies has been performed, and an optimized strategy with dynamic programming as global regulation at the upper level and model predictive control at the lower level is suggested to integrate the slow and fast dynamic powers and achieve adaptability to strong fluctuation loads. In this control strategy, the uncertainties of energy storage system/hybrid energy storage system parameters have been introduced to eliminate their impact on the system performance. Then, the icebreaking process with multi-frequency fluctuation has been simulated, and the hybrid energy storage system with battery and supercapacitor is recommended to reach multi-objective with the lowest power fluctuation of diesel–electric unit, highest efficiency, and the minimum battery degradation. Finally, the fuel oil consumption and emissions of the hybrid energy storage system have been discussed, and the optimized strategy can save fuel oil by up to 5.33% and reduce the CO2 emission by 22% during the icebreaking process, exhibiting great potential in the environmental friendliness and significant advantages in terms of low fuel oil consumption.

Sustainable recycling of the biodegradable polyester poly(butylene succinate) via selective catalytic hydrolysis and repolymerization - Wei-Zhen Zheng; Xiao Li; Peng-Yuan Xu; Ze-Yang Zhang; Ping-Li Wang; Bo Lu; Dan Huang; Zhi-Chao Zhen; Jun-Hui Ji; Ge-Xia Wang (Resources, Conservation and Recycling, 2024)

High sulfur-to-iron ratios enhance thallium(I) sequestration by sulfidated zero-valent iron - Nana Wang; Fengli Liu; Huosheng Li; Ping Zhang; Juanxi Huang; Gaosheng Zhang; Tangfu Xiao; Jianyou Long; Dan Peng; Yuqi Wang; Huanbin Huang; Zengping Ning (Process Safety and Environmental Protection, 2024)

ESR chronology of the Quaternary sedimentary sequence of the Shinaimiao borehole in Hebi City, Henan Province, China - Hao Ji; Zhong-shan Shen; Chun-Ru Liu; Xiong-Nan Huang; Xiao-Ping Yang; Chuan-Yi Wei; Xin-Xiu Li; Qing Zhou; Gong-Ming Yin (Quaternary Geochronology, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Effects of polystyrene microplastic composite with florfenicol on photosynthetic carbon assimilation of rice (Oryza sativa L.) seedlings: Light reactions, carbon reactions, and molecular metabolism - Luoqin Shen; Zhiheng Li; Xinting Huang; Ping Zhang; Liangyu Zhang; Wenlu Zhao; Yuezhong Wen; Huijun Liu (Journal of Hazardous Materials, 2024)

Water-soluble biodegradable polyesters with pH and ionic responsivity - Xiao Li; Wei-Zhen Zheng; Peng-Yuan Xu; Ze-Yang Zhang; Ping-Li Wang; Bo Lu; Dan Huang; Zhi-Chao Zhen; Yang Zhao; Jun-Hui Ji; Ge-Xia Wang (Journal of Hazardous Materials, 2024)

Synthesis and characterization of Ce-BiOBr/Bi2S3 catalyst with enhanced catalytic activity for organic dye reduction under dark - Mengistu Tadesse Mosisa; Pengkun Zhang; Binghong Wu; Longyan Chen; Zhengjie Su; Ping Li; Hanya Zhang; Ambar Farooq; Ting Huang; Adugna Boke Abdeta; Osman Ahmed Zelekew; Dong-Hau Kuo; et al. (Journal of Environmental Chemical Engineering, 2024)

Enhanced hydrate formation at the liquid CO2-brine interface with shear flow for solid CO2 sequestration - Ming-Long Wang; Yi-Fei Sun; Wei-Xin Pang; Qing-Ping Li; Ting Huang; Hong-Nan Chen; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Dan Rao; Bei Liu; Chang-Yu Sun; et al. (Gas Science and Engineering, 2024)

A review in two classes of hypoglycemic compounds (prebiotics and flavonoids) intervening in type 2 diabetes mellitus: Unveiling their structural characteristics and gut microbiome as key mediator - Zerun Li; Tingting Zhang; Yang Liu; Yanhong Huang; Jianjun Liu; Shanshan Wang; Ping Sun; Yupeng Nie; Yanlei Han; Fanghua Li; Hui Xu (Food Bioscience, 2024)

Study on regulation and effect mechanism of fish collagen peptide on retrogradation of corn starch gel - Yunfei Dai; Shuhan Zhang; Jinlei Li; Zhangzhang Li; Ninghua Deng; Yong Liu; Ping Wang; Dejian Huang; Yue Li (Food Bioscience, 2024)

Multi-scenario application of chitosan emulsions as fat replacers: Based on the regulation of chitosan hydrophobicity and emulsion rheological properties - Cheng-Zhen Nie; Yao Li; Xu-Hui Huang; Hao-Peng Wang; Xu-Song Wang; Xiu-Ping Dong; Bei-Wei Zhu; Lei Qin (Food Hydrocolloids, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

Triarylamine-based polyimide COFs for achieving high performance ambipolar multi-color electrochromic energy-storage films - Lei Huang; Rong Guo; Qingqing Qiu; Huan Li; Putrakumar Balla; Jinming Zeng; Tongxiang Liang; Xiaopeng Qi; Ping Liu (Chemical Engineering Journal, 2024)

Efficient continuous synthesis of long-chain alkylbenzenes catalyzed by ionic liquids in microreaction systems - Haoran Ma; Wei Zhao; Ping Li; Ailing Huang (Chemical Engineering Journal, 2024)

Renewable hemicellulose-based materials for value-added applications - Guangfu Liao; Enhui Sun; E.B. Gueguim Kana; Hongying Huang; Isaac A. Sanusi; Ping Qu; Hongmei Jin; Jun Liu; Li Shuai (Carbohydrate Polymers, 2024)

Unravelling ice growth characteristics beneath cloud tops with joint analysis of airborne Ka-band radar and Himawari observations - Shuangzhi You; Delong Zhao; Haoran Li; Wei Zhou; Yuanmou Du; Ping Tian; Jiujiang Sheng; Wei Xiao; Fei Wang; Hui He; Mengyu Huang; Deping Ding; et al. (Atmospheric Research, 2024)

Improved Streamflow Simulation by Assimilating In Situ Soil Moisture in Lumped and Distributed Approaches of a Hydrological Model in a Headwater Catchment - Hongxia Li; Yuanyuan Huang; Yongliang Qi; Yanjia Jiang; Xuan Tang; Elizabeth W. Boyer; Carlos R. Mello; Ping Lan; Li Guo (Water Resources Management, 2024)

Synthesis and antiproliferative activity of 7-substituted amide estradiol derivatives - Chun-Fang Gan; Ying Li; Hua-Long Chen; Jia-Wei Yao; Yun-Qiong Gu; Bin Su; Zhi-Wei Zhong; Jian-Guo Cui; Yan-Min Huang; Zhi-Ping Liu (Medicinal Chemistry Research, 2024)

Microbial metabolism strengths carbon sequestration and crop yield in upland red soil after long-term ex situ incorporation of straw - Li Tang; Xiaobin Guo; Daoyou Huang; Xiaomeng Wei; Hao Sheng; Pei Luo; Ping Zhou; Wei Gao; Yan Li; Miaomiao Zhang; Wei Zheng; Jinshui Wu (Journal of Soils and Sediments, 2024)

Applewood Biochar at Different Smoldering Conditions Passivates Pyrite by Promoting the Formation of Jarosite - Hecheng Fu; Jiale Fan; Jie Li; Jianhong Huang; Senlin Tian; Ping Ning (Bulletin of Environmental Contamination and Toxicology, 2024)

Simultaneously inhibit cadmium and arsenic uptake in rice (Oryza sativa L.) by Selenium enhanced iron plaque: Performance and mechanism - Peicheng Huang; Dan Zou; Chunhua Dong; Chongjian Tang; Qingzhu Li; Pengwei Zhao; Ping Zhang; Qi Liao; Zhihui Yang (Chemosphere, 2024)

A new paradigm for construction safety management in China: Introducing knowledge graph and accident database into the early-stage of BIM - Wangxin Li; Ping Wu; Jiaming Huang; Yidong Xu (Journal of Cleaner Production, 2024)

Sustainable flood control strategies under extreme rainfall: Allocation of flood drainage rights in the middle and lower reaches of the yellow river based on a new decision-making framework - Xin Huang; Juqin Shen; Shuqin Li; Chen Chi; Ping Guo; Pei Hu (Journal of Environmental Management, 2024)

Real-time PCR method based on single-copy nuclear DNA sequences for the quantitative detection of pork adulteration in processed beef products - Lijuan Chang; Ping Huang; Jikai Liu; Chengping Fu; Wenjuan Liu; Yongfeng Gao; Yuanhong Li; Yongling Liu; Ailin Long (Food Control, 2024)

Histopathology and transcriptome profiling reveal features of immune responses in gills and intestine induced by Spring viremia of carp virus - Ping Ouyang; Qiunan Li; Shuya Liu; Yankai Li; Shuhan Li; Yongheng Zhou; Peng jia; Defang Chen; Xiaoli Huang; Yi Geng (Fish & Shellfish Immunology, 2024)

Ocean acidification alters microeukaryotic and bacterial food web interactions in a eutrophic subtropical mesocosm - Ruiping Huang; Ping Zhang; Xu Zhang; Shouchang Chen; Jiazhen Sun; Xiaowen Jiang; Di Zhang; He Li; Xiangqi Yi; Liming Qu; Tifeng Wang; Kunshan Gao; et al. (Environmental Research, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Synchronous Mutual Learning Network and Asynchronous Multi-Scale Embedding Network for miRNA-Disease Association Prediction - Weicheng Sun; Ping Zhang; Weihan Zhang; Jinsheng Xu; Yanrong Huang; Li Li (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Development of polysaccharide-coated layered double hydroxide nanocomposites for enhanced oral insulin delivery - Huiwen Pang; Youzhi Wu; Yang Chen; Chen Chen; Xuqiang Nie; Peng Li; Guojun Huang; Zhi Ping Xu; Felicity Y. Han (Drug Delivery and Translational Research, 2024)
Oral insulin (INS) is predicted to have the most therapeutic advantages in treating diabetes to repress hepatic glucose production through its potential to mimic the endogenous insulin pathway. Many oral insulin delivery systems have been investigated. Layered double hydroxide (LDH) as an inorganic material has been widely used in drug delivery thanks to its appealing features such as good biocompatibility, low toxicity, and excellent loading capability. However, when used in oral drug delivery, the effectiveness of LDH is limited due to the acidic degradation in the stomach. In this study, to overcome these challenges, chitosan (Chi) and alginate (Alg) dual-coated LDH nanocomposites with the loading of insulin (Alg-Chi-LDH@INS) were developed by the layered-by-layered method for oral insulin delivery with dynamic size of ~ 350.8 nm, negative charge of ~ − 13.0 mV, and dispersity index 0.228. The insulin release profile was evaluated by ultraviolet–visible spectroscopy. The drug release profiles evidenced that alginate and chitosan coating partially protect insulin release from a burst release in acidic conditions. The analysis using flow cytometry showed that chitosan coating significantly enhanced the uptake of LDH@INS by Caco-2 cells compared to unmodified LDH and free insulin. Further in the in vivo study in streptozocin-induced diabetic mice, a significant hypoglycemic effect was maintained following oral administration with great biocompatibility (~ 50% blood glucose level reduction at 4 h). This research has thus provided a potential nanocomposite system for oral delivery of insulin. Graphical Abstract

Antibacterial and gut health effects of Amomum tsao‐ko in aquatic feed: A sustainable alternative to chemical antibiotics - Weiyao Peng; Guohui Liao; Lianzhang Wu; Jian Zhang; Juncai He; Penghui Gao; Yunsheng Cha; Shengjun You; Mei Huang; Jilan Zhou; Yuqiu He; Yi Yang; et al. (Journal of Fish Biology, 2024)
Amomum tsao‐ko Crevost et Lemarie (Zingiberaceae), an aromatic plant, has been considered to have diverse medicinal values and economic significance. It has been reported to possess antibacterial, antioxidant, and antidiabetic effects. With the increasing risk of diseases in aquaculture, there is a need for alternative solutions to chemical antibiotics. Plant extracts have shown promise as natural feed additives for aquatic animals. In this study, the antibacterial effect of Amomum tsao‐ko crude extracts was evaluated using the Oxford cup method. The extracts exhibited significant antimicrobial activity against Salmonella typhimurium and Salmonella enteritidis . Furthermore, the addition of Amomum tsao‐ko to fish feed resulted in notable changes in the gut structure of zebrafish and tilapia. The length and morphology of intestinal villi were enhanced, promoting improved digestion. Analysis of the gut microbial community revealed that Amomum tsao‐ko supplementation induced key changes in the gut microbial community composition of both zebrafish and tilapia. Notably, a 1% inclusion of Amomum tsao‐ko resulted in a marked rise in Proteobacteria levels in zebrafish, which diminished at 10% dosage. The supplement elicited mixed reactions among other bacterial phyla like Actinobacteria and Verrucomicrobiota. Fluctuations were also observed at the genus level, pointing to the concentration of Amomum tsao‐ko playing a pivotal role in influencing the structure of intestinal bacteria. The findings of this study suggest that Amomum tsao‐ko has antibacterial properties and can positively influence the gut health of fish. The potential use of Amomum tsao‐ko as a natural feed additive holds promise for improving aquaculture practices and reducing reliance on chemical antibiotics. Further research is needed to explore the full potential and applications of Amomum tsao‐ko in fish feed development.

Integrated analysis of the gonadal methylome and transcriptome provides new insights into the expression regulation of sex determination and differentiation genes in spotted scat (Scatophagus argus) - Kai-Zhi Jiao; Yu Li; Yuan-Qing Huang; Charles Brighton Ndandala; Gang Shi; Si-Ping Deng; Hong-Juan Shi; Hua-Pu Chen; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Garciyunnanones A–R: Caged polycyclic polyprenylated acylphloroglucinols decorated with a lavandulyl substituent from Garcinia yunnanensis - Miaomiao Nan; Yueyou Yang; Ping Ying; Qiang Zheng; Youjun Wu; Tianjie Cao; Ting Li; Weiming Huang; Chuanlu Fu; Lingyi Kong; Wenjun Xu (Phytochemistry, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Temporal and spatial variation of typhoon-induced surges and the impact of rainfall in a tidal river - Yicheng Huang; Erfeng Zhang; Weihua Li; Ya Ping Wang (Estuarine, Coastal and Shelf Science, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Efficacy and safety of dabigatran and rivaroxaban in atrial fibrillation patients with impaired liver function: a multicenter retrospective cohort study - Xinhai Huang; Wenlin Xu; Guilan Wu; Ruijuan Li; Ping Gu; Qiaowei Zheng; Xiumei Liu; Hengfen Dai; Xiangsheng Lin; Yuxin Liu; Xiaoming Du; Jun Su; et al. (European Journal of Clinical Pharmacology, 2024)

Wearable solid-phase microextraction sampling for enhanced detection of volatile analytes in human ears - Wenzheng Mo; Lei Li; Bi-Cheng Yang; Xiangjie Wang; Baixue Wang; Jianfeng Zhang; Qiaoyun Huang; Zhong-Ping Yao; Dong Zhang; Bin Hu (Analytica Chimica Acta, 2024)

Complete genome sequence of a novel amalgavirus in sponge gourd, Luffa cylindrica - Ting Li; Zhuang-Xin Ye; Yao-Liang Huang; Jian-Ping Chen; Chuan-Xi Zhang; Jun-Min Li (Archives of Virology, 2024)

Functional metabolomics characterizes the contribution of farnesoid X receptor in pyrrolizidine alkaloid-induced hepatic sinusoidal obstruction syndrome - Aizhen Xiong; Longhui Lu; Kaiyuan Jiang; Xiaoning Wang; Yan Chen; Xunjiang Wang; Wei Zhang; Yuzheng Zhuge; Wendong Huang; Lujin Li; Qi Liao; Fan Yang; et al. (Archives of Toxicology, 2024)

Different reference genomes determine different results: Comparing SNP calling in RAD-seq of Engelhardia roxburghiana using different reference genomes - Pei-Han Huang; Tian-Rui Wang; Min Li; Ou-Yan Fang; Ren-Ping Su; Hong-Hu Meng; Yi-Gang Song; Jie Li (Plant Science, 2024)

Inhibition of flowering by gibberellins in the woody plant Jatropha curcas is restored by overexpression of JcFT - Ping Huang; Jie Yang; Jiapeng Ke; Li Cai; Yingxiong Hu; Jun Ni; Chaoqiong Li; Zeng-Fu Xu; Mingyong Tang (Plant Science, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

Dynamic modulation of nodulation factor receptor levels by phosphorylation-mediated functional switch of a RING-type E3 ligase during legume nodulation - Hao Li; Yajuan Ou; Jidan Zhang; Kui Huang; Ping Wu; Xiaoli Guo; Hui Zhu; Yangrong Cao (Molecular Plant, 2024)

Heterogeneous catalytic ozonation of ciprofloxacin in wastewater with red mud: Characterization and performance - Fuyu Huang; Huiru Ma; Zhanyao Li; Liqiang Zhang; Jun Li; Shouyan Chen; Ping Zhou; Guifang Chen (Journal of Water Process Engineering, 2024)

Evolution of physicochemical and leaching characteristics of municipal solid waste incineration fly ash in China under ultra-low emission standard - Guangyuan Yao; Rongbin Xu; Zhu Liang; Ping Li; Ya Xu; Yuqiang Liu; Can Qian; Qifei Huang (Journal of Environmental Management, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

A newly-discovered tea population variety processed Bai Mu Dan white tea: Flavor characteristics and chemical basis - Yanping Lin; Yibiao Huang; Su Zhou; Xiaolan Li; Yike Tao; Yani Pan; Xinyu Feng; Haowei Guo; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Health risk assessment of heavy metal(loid)s in road dust via dermal exposure pathway from a low latitude plateau provincial capital city: The importance of toxicological verification - Jingya Li; Daolei Cui; Ziyue Yang; Jiaoyang Ma; Jianjun Liu; Yingxin Yu; Xianfeng Huang; Ping Xiang (Environmental Research, 2024)

GHK-Cu/Pionin-loaded in situ electrospun PVB/PVP smart dressing promotes wound healing via anti-oxidant, anti-inflammatory, antimicrobial, and tissue regenerative effects - Yan Wang; Zhichao Zheng; Janak L. Pathak; Haoyu Cheng; Sizhen Huang; Zi Fu; Ping Li; Lihong Wu; Huade Zheng (Chemical Engineering Journal, 2024)

Amorphous/Graphitic carbon phase engineering of Corrosion-Resistant Fe@C Core-Shell nanowires for optimized dipole polarization and enhanced microwave absorption - Ping-an Yang; Wenjiao Deng; Haibo Ruan; Zhengwei Qu; Rui Li; Lirui Wang; Jiufei Luo; Zhihao Zhou; Mengjie Shou; Xin Huang; Qiao Chen; Xinglong Gong (Chemical Engineering Journal, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Application of 210Pbex dating to establishing chronologies of modern terrestrial sedimentary deposits in estuarine deltas - Jinlin Li; Xinbao Zhang; Xiubin He; Jie Wei; Yong Yuan; Runchuan Zhang; Shengjun Wu; Yuhai Bao; Qiang Tang; Ping Huang (CATENA, 2024)

Analysis of Root Response Mechanism of Quinoa Seedlings to Waterlogging Stress Based on Metabolome - Yirui Guo; Qianchao Wang; Heng Xie; Xuesong Zhang; Tingzhi Huang; Ping Zhang; Junna Liu; Li Li; Peng Qin (Journal of Plant Growth Regulation, 2024)

Sulfur doping-induced morphological and electronic structure modification of polyoxometalate FeWO4 for enhanced removal of organic pollutants from water - Dong-Hua Xie; Wen-Qiang Li; Nuo Xu; Li Yuan; Wen-Hua Zhang; Tian-Yin Huang; Guo-Ping Sheng (Water Research, 2024)

Moniezia benedeni infection increases IgE+ cells in sheep (Ovis aries) small intestine - Jing Pan; Wan-Ling Yao; Li-Ping Liu; Bao-Shan Wang; Wen-Zhu Chai; Zhen Huang; Xi-Ping Fan; Wan-Hong He; Wen-Hui Wang; Wang-Dong Zhang (Veterinary Parasitology, 2024)

High-frequency monitoring during rainstorm events reveals nitrogen sources and transport in a rural catchment - Xuan Huang; Yi Zhu; Han Lin; Dongli She; Ping Li; Man Lang; Yongqiu Xia (Journal of Environmental Management, 2024)

Physicochemical properties of Dioscorea alata Tainung No. 1 and 2 via different drying methods and application on the frozen tangyuan - Ping-Hsiu Huang; Yu-Tsung Cheng; Shu-Ju Chen; Wen-Chien Lu; Po-Yuan Chiang; Wen-Pei Cheng; Chiun-Chuang R. Wang; Po-Hsien Li (Food Bioscience, 2024)

Near-infrared laser induced direct ignition of 4,4′,5,5′-tetranitro-1H,1′H-[2,2′-biimidazole]-1,1′-diamine by constructing diverse crystal structures - Ping Ye; Weimiao Wang; Xiaodong Li; Zhiqiang Qiao; Yirui Lu; Bing Huang; Liangfei Bai; Liang Chen; Xiaoqing Tu; Rui Li; Guangcheng Yang; Guoqing Lv (Chemical Engineering Journal, 2024)

Chemical constituents from Strobilanthes cusia and their chemotaxonomic significance - Si-Qi Huang; Chao-Tian He; Qiu-Ying He; Gui-Shuai Lang; Hong-Jie Chen; Li-Ping Teng; Zhong-Bo Zhou (Biochemical Systematics and Ecology, 2024)

Implantation of Adipose-Derived Mesenchymal Stromal Cells (ADSCs)-Lining Prosthetic Graft Promotes Vascular Regeneration in Monkeys and Pigs - Xiao Zuo; Pengfei Han; Ding Yuan; Ying Xiao; Yushi Huang; Rui Li; Xia Jiang; Li Feng; Yijun Li; Yaya Zhang; Ping Zhu; Hongge Wang; et al. (Tissue Engineering and Regenerative Medicine, 2024)
Background: Current replacement procedures for stenosis or occluded arteries using prosthetic grafts have serious limitations in clinical applications, particularly, endothelialization of the luminal surface is a long-standing unresolved problem. Method: We produced a cell-based hybrid vascular graft using a bioink engulfing adipose-derived mesenchymal stromal cells (ADSCs) and a 3D bioprinting process lining the ADSCs on the luminal surface of GORE-Tex grafts. The hybrid graft was implanted as an interposition conduit to replace a 3-cm-long segment of the infrarenal abdominal aorta in Rhesus monkeys. Results: Complete endothelium layer and smooth muscle layer were fully developed within 21 days post-implantation, along with normalized collagen deposition and crosslinking in the regenerated vasculature in all monkeys. The regenerated blood vessels showed normal functionality for the longest observation of more than 1650 days. The same procedure was also conducted in miniature pigs for the interposition replacement of a 10-cm-long right iliac artery and showed the same long-term effective and safe outcome. Conclusion: This cell-based vascular graft is ready to undergo clinical trials for human patients.

A Four Amino Acid Metabolism-Associated Genes (AMGs) Signature for Predicting Overall Survival Outcomes and Immunotherapeutic Efficacy in Hepatocellular Carcinoma - Lu-sheng Liao; Zi-jun Xiao; Jun-li Wang; Ting-jun Liu; Feng-die Huang; Yan-ping Zhong; Xin Zhang; Ke-heng Chen; Run-lei Du; Ming-you Dong (Biochemical Genetics, 2024)

Catalytic ozonation of ammonia nitrogen with powdered activated coke: Influence of operational parameters and surface chemistries - Guifang Chen; Huiru Ma; Fuyu Huang; Zhanyao Li; Liqiang Zhang; Jun Li; Ping Zhou; Shouyan Chen; Yongwei Li (Journal of Water Process Engineering, 2024)

Vertical migration behavior simulation and prediction of Pb and Cd in co-contaminated soil around Pb-Zn smelting slag site - Ying Luo; Zhe Wang; Yong-De Zhang; Jia-Qian Zhang; Qiu-ping Zeng; Zhen-Long Zhang; Duan Tian; Chao Li; Chao-liang Peng; Kai Ye; Yi-Ming Chen; Feng-Yu Huang; et al. (Journal of Hazardous Materials, 2024)

Microbial mechanisms of C/N/S geochemical cycling during low-water-level sediment remediation in urban rivers - Wen-Long Chen; Min Zhang; Jian-Guo Wang; Wei-Jie Huang; Qiong Wu; Xiao-Ping Zhu; Ning Li; Qian Wu; Wei Guo; Jun Chen (Journal of Environmental Management, 2024)

Comparative study of reactive oxygen species and tetracycline degradation pathways in catalytic peroxodisulfate activation by asymmetric mesoporous TiO2 and the corresponding controlled-release materials - Ting Wang; Rui Huang; Hua-Li Chen; Kun-Miao Xu; Li-Guang Wu; Kou-Ping Chen; Ji-Chun Wu (Environmental Pollution, 2024)

A bipolar SMPS network for measuring atmospheric aerosols using natural air ions - Yiran Li; Jin Wu; Hao Wu; Xiaomeng Liu; Qi Zhou; Yiqun Lu; Yuhang Wu; Mengyu Liu; Hengjia Ou; Shixin Mai; Xuehui He; Huaying Song; et al. (Atmospheric Environment, 2024)

Effect of Perilla seeds inclusion on the performance, egg quality characteristics, biochemical parameters and egg yolk fatty acid composition of laying hens - Ping Li; Samiullah Khan; Yanhua Huang; Shengtao Lu; Panhong Zhou; Jiale Ling; Tianzheng Xu; Xiaoli Shi (Tropical Animal Health and Production, 2024)

Correlation of Immune-Inflammatory Response System (IRS)/Compensatory Immune-Regulatory Reflex System (CIRS) with White Matter Integrity in First-Episode Patients with Schizophrenia - Mengzhuang Gou; Wei Li; Jinghui Tong; Yanfang Zhou; Ting Xie; Ting Yu; Wei Feng; Yanli Li; Song Chen; Baopeng Tian; Shuping Tan; Zhiren Wang; et al. (Molecular Neurobiology, 2024)

Proposal of Streptomyces bellus Margalith and Beretta 1960 as a Later Heterotypic Synonym of Streptomyces coeruleorubidus (Preobrazhenskaya 1957) Pridham et al. 1958 and an Emended Description of Streptomyces coeruleorubidus - Yi Peng; Ping Mo; Yaxi Zheng; Chenxi Li; Kerui Huang (Current Microbiology, 2024)

Removal efficiency and mechanism of geosmin by modified micro-nano bubbles in drinking water treatment process - Ziang Zhao; Xiaojiang Huang; Zhiqiang Zhang; Heliang Pang; Xuan Wang; Ping Li; Chunbo Li; Jinsuo Lu (Journal of Water Process Engineering, 2024)

Synergistic removal of sulphur-containing malodourous gases via peroxydisulfate activation in three-dimensional electrode system - Rui Luo; Shugen Liu; Chen Li; Xiaofeng Huang; Ping Ning; Senlin Tian (Journal of Environmental Chemical Engineering, 2024)

Engine-out emissions from an ammonia/diesel dual-fuel engine – The characteristics of nitro-compounds and GHG emissions - Run Chen; Tie Li; Xinran Wang; Shuai Huang; Xinyi Zhou; Shiyan Li; Ping Yi (Fuel, 2024)

Quercetin attenuates cisplatin-induced mitochondrial apoptosis via PI3K/Akt mediated inhibition of oxidative stress in pericytes and improves the blood labyrinth barrier permeability - Tian-Lan Huang; Wen-Jun Jiang; Zan Zhou; Tian-Feng Shi; Miao Yu; Meng Yu; Jun-Qiang Si; Yan-Ping Wang; Li Li (Chemico-Biological Interactions, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Synthesis, antitumor evaluation and computational study of thiazolidinone derivatives of dehydroabietic acid-based B ring-fused-thiazole - Nai-Yuan Chen; Cui-Ping Li; Hong-Fei Huang (Molecular Diversity, 2024)

Effects of the Glucocorticoid-Mediated Mitochondrial Translocation of Glucocorticoid Receptors on Oxidative Stress and Pyroptosis in BV-2 Microglia - Ruonan Dang; Xuyang Hou; Xinglan Huang; Caifeng Huang; Xiaoqing Zhao; Xingrong Wang; Ning Zhang; Yuqi Yang; Nan Li; Sheng Liu; Peng Yan; Ping Fan; et al. (Journal of Molecular Neuroscience, 2024)

Microbial colony sequencing combined with metabolomics revealed the effects of chronic hexavalent chromium and nickel combined exposure on intestinal inflammation in mice - Yueming Gu; Shuangyan Zheng; Cheng Huang; Xianhong Cao; Ping Liu; Yu Zhuang; Guyue Li; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Science of The Total Environment, 2024)

Potential of perennial sorghum for biogas production: Pretreatment with yeast-contained inoculants during anaerobic storage - Xiaolong Tang; Chaosheng Liao; Shufeng Zhou; Cheng Chen; Lin Li; Guangrou Lu; Xiaokang Huang; Mingjie Zhang; Chao Chen; Ping Li (Fuel, 2024)

Identification, characterization and the inflammatory regulating effect of NOD1/2 in sturgeon - Defang Chen; Hao Zhu; Lu Lu; Yinqiu Chen; Xin Zhang; Xiaoli Huang; Ping Ouyang; Yi Geng; Zhiqiong Li (Fish & Shellfish Immunology, 2024)

Dynamic, synergistic, and optimal emissions and kinetics of volatiles during co-pyrolysis of soil remediation plants with kaolin/modified kaolin - Zhibin Chen; Weijie Li; Shengzheng Huang; Ping Zhuang; Dajie Jia; Fatih Evrendilek; Sheng Zhong; Yoshihiko Ninomiya; Zuoyi Yang; Yao He; Wuming Xie; Jingyong Liu; et al. (Chemical Engineering Journal, 2024)

Charge-reversal biodegradable nanoplatform with ferroptosis and ICD induction for tumor synergistic treatment - Ping Sun; Li Huang; Zimu Li; Yao Yang; Shiman Lu; Nansha Gao; Hongzhong Chen; Xiaowei Zeng; Zhongjian Xie (Chemical Engineering Journal, 2024)

Effect of land use conversion on the soil aggregate-associated microbial necromass carbon in estuarine wetland of the Pearl River in China - Chun Liu; Zhinan Wu; Chunhuan He; Bin Huang; Yuheng Zhang; Ping Li; Weijia Huang (CATENA, 2024)

Emissions of polycyclic aromatic hydrocarbons in PM2.5 emitted from motor vehicles exhaust (PAHs-PM2.5-MVE) under the plateau with low oxygen content - Qinzuo Yao; Jianwu Shi; Xinyu Han; Senlin Tian; Jianhong Huang; Yingjie Li; Ping Ning (Atmospheric Environment, 2024)

Mechanisms of Ferritinophagy and Ferroptosis in Diseases - Siqi Li; Ping Huang; Feifan Lai; Ting Zhang; Jiaqi Guan; Haitong Wan; Yu He (Molecular Neurobiology, 2024)

Effects of Fractionation Methods on Soil Aggregate Microbial Community Composition: Settling vs. Wet Sieving - Xin Gao; Rui Wang; Yaxian Hu; Weijia Li; Lanlan Du; Shengli Guo; Shengjun Wu; Ping Huang (Journal of Soil Science and Plant Nutrition, 2024)

Genotype diversity and antibiotic resistance risk in Aeromonas hydrophila in Sichuan, China - Kun Peng; Mengzhu Chen; Yilin Wang; Ziqi Tian; Longjun Deng; Tiancai Li; Yang Feng; Ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Brazilian Journal of Microbiology, 2024)

Dietary ellagic acid supplementation improves meat quality in growing-finishing pigs - Tengteng Huang; Huawei Li; Xiaoling Chen; Daiwen Chen; Jun He; Bing Yu; Yuheng Luo; Ping Zheng; Hong Chen; Zhiqing Huang (Animal Feed Science and Technology, 2024)

A system dynamics simulation-based strategic analysis of integrated water resources utilization and management in Shenzhen city - Guangzhi Zheng; Jing-Cheng Han; Ping Li; Bing Li; Xiaofeng Wu; Yuefei Huang; Muhammad Ahmad (Environmental Science and Pollution Research, 2024)

Whole genome analysis of intestinal source Bacillus and its effect on the prevention and control of hybrid snakehead (Channa maculata ♀ × Channa argus ♂) nocardiosis - Tingting Zhou; Ping Cai; Junwei Li; Zhongsheng Li; Xueming Dan; Xiande Huang; Xiaoyong Zhang (Frontiers in Marine Science, 2024)
In order to explore the antagonistic mechanism of Lysinibacillus sphaericus AEB18 against Nocardia seriolae , the whole genome of strain AEB18 was sequenced, and the effect of strain AEB18 in controlling nocardiosis of hybrid snakehead was verified in vitro and in vivo . Strain AEB18 genome was a circular DNA of 4,653,716 base pairs (bp) and GC content of 37.4%, predicting 4,529 coding genes, 108 tRNAs, 37 rRNAs, and 95 non-coding (nc)RNAs. The eggNOG (Non-supervised Orthologous Groups), GO (Gene Ontology), KEGG (Kyoto Encyclopedia of Genes and Genomes) and the CAZy (Carbohydrate-Associated Enzyme) database annotated the strain AEB18 genome to 3,965, 3,325, 2,061, and 112 genes, respectively. Furthermore, nine gene clusters, including polyketones, non-ribosomal synthetic peptides, β-lactones, terpenes, ribosomal synthetic peptides, and other secondary metabolites with bacteriostatic effect were obtained through the prediction of secondary metabolites of strain AEB18. After the addition of L. sphaericus AEB18 (1 × 10 9 CFU/g) with a mass fraction of 1% to the basal diet for 21 days, the weight gain rate and the activity of amylase in intestinal chyme of hybrid snakehead were significantly increased ( P < 0.05). In addition, hybrid snakehead fed with L. sphaericus AEB18 supplemented diets showed significantly reduced mortality rate ( P< 0.05) after N. seriolae infection, compared with the control group (mortality rate was 100%). Overall, L. sphaericus AEB18 positively affected hybrid snakeheads, promoted growth and reduced mortality rate of hybrid snakeheads with nocardiosis. Taken together, the L. sphaericus AEB18 possesses great potential as a biocontrol agent, which can be commercially developed to improve disease control in freshwater aquaculture.

Constructing α-MnO2/Mn2O3 heterojunction for formaldehyde oxidation - Xuelin Huang; Muhua Chen; Guangyao Li; Ping Wang (Chemosphere, 2024)

Cinnamaldehyde treats largemouth bass non-lethal bacterial enteritis by regulating gut morphology, barrier, inflammation, microbiota and serum biochemistry - Ping Ouyang; Shuanghui Huang; Wenyan Wei; Jianing Wu; Yongheng Zhou; Shuhan Li; Qiunan Li; Yi Geng; Xiaoli Huang; Defang Chen; Lizi Yin (Aquaculture, 2024)

Chronic ammonia stress caused disorder of intestinal microbiota and damaged intestinal structure and function in yellow catfish (Pelteobagrus fulvidraco) - Lin Luo; Senyue Liu; Baipeng Chen; Fulong Li; Yongqiang Deng; Xiaoli Huang; Yi Geng; Ping Ouyang; Defang Chen (Aquaculture, 2024)

Environmentally persistent free radicals on photoaged microplastics from disposable plastic cups induce the oxidative stress-associated toxicity - Hanlin Cao; Ping Ding; Xintong Li; Chushan Huang; Xin Li; Xiaoxia Chen; Lijuan Zhang; Jianying Qi (Journal of Hazardous Materials, 2024)

Underlying the mechanisms of pathogen inactivation and regrowth in wastewater using peracetic acid-based disinfection processes: A critical review - Yuqian Lin; Yunpeng He; Qiya Sun; Qian Ping; Manhong Huang; Lin Wang; Yongmei Li (Journal of Hazardous Materials, 2024)

Experimental study on the mass burning rate and flame tilt angle of annular pool fires under cross air flow - Ping Huang; Rui Zhang; Chunxiang Liu; Xinyue Wu; Shanshan Chen; Jinhao Li; Man Li; Longxing Yu (Fuel, 2024)

Experimental study on the morphology of turbulent diffusion flames with different aspect ratios under slope conditions - Chunxiang Liu; Tairun Lai; Hao Zhang; Ping Huang; Kaihong Lin; Yuchao Lin; Man Li (Fuel, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Self-powered photocatalytic system fabricated by bifunctional coordination polymers - Qiang Zhang; Chao Huang; Yue Zhang; Saiwei Liu; Dianbo Zhang; Ping Li; Fei Wang; Dandan Wang; Ying-Ying Zhang (Chemical Engineering Journal, 2024)

Layered double hydroxide@zeolite composite modified sponge: A versatile biocarrier for enhancing nitrogen removal in biofilters - Zhuwu Jiang; Mengfan Wu; Panyang Gu; Wenzhong Huang; Chang-Ping Yu; Zhongjian Zheng; Yanqu Wang; Ning Yao; Yan Li (Chemical Engineering Journal, 2024)

Removal and recovery of phosphate by modified oyster shell and its fertilizer application - Ping Li; Jianxu Li; Weirui Chen; Xiujuan Guan; Bing Tang; Liying Bin; Shaosong Huang (Science of The Total Environment, 2024)

Adaptive evolution in asymptomatic host confers MDR Salmonella with enhanced environmental persistence and virulence - Bing He; Ting-ting Zhu; Yin Liang; Hai-jing Wei; Zi-lei Huang; Li-jie Liang; Jia-hao Zhong; Yang Luo; Xin-lei Lian; Dong-hao Zhao; Xiao-ping Liao; Ya-hong Liu; et al. (Science of The Total Environment, 2024)

Climate warming enhances chemical weathering in permafrost-dominated eastern Siberia - Ping Wang; Qiwei Huang; Shiqi Liu; Yu Liu; Zehong Li; Sergey P. Pozdniakov; Tianye Wang; Ekaterina S. Kazak; Natalia L. Frolova; Olga I. Gabysheva; Jialing Zhang; Bing Bai; et al. (Science of The Total Environment, 2024)

Multiomics analyses of two Leonurus species illuminate leonurine biosynthesis and its evolution - Peng Li; Meng-Xiao Yan; Pan Liu; Dan-Jie Yang; Ze-Kun He; Yun Gao; Yan Jiang; Yu Kong; Xin Zhong; Sheng Wu; Jun Yang; Hong-Xia Wang; et al. (Molecular Plant, 2024)

A new snow depth retrieval method by improved hybrid DEM differencing and coherence amplitude algorithm for PolInSAR - Haiwei Qiao; Ping Zhang; Zhen Li; Lei Huang; Shuo Gao; Chang Liu; Zhipeng Wu; Shuang Liang; Jianmin Zhou; Wei Sun; Jian Wang (Journal of Hydrology, 2024)

Chargeable persistent luminescence 3D-printed scaffolds: A stepwise tactic for osteosarcoma treatment - Rui Huang; Ni Ni; Yun Su; Li Gu; Yahan Ju; Dandan Zhang; Jipeng Li; Meiqi Chang; Yu Chen; Ping Gu; Xianqun Fan (Chemical Engineering Journal, 2024)

Lipopolysaccharides from a Shiraia fruiting body-associated bacterium elicit host fungal hypocrellin A biosynthesis through nitric oxide generation - Xin Ping Li; Wen Hao Shen; Lu Lu Zhou; Qun Yan Huang; Rui Peng Cong; Li Ping Zheng; Jian Wen Wang (Carbohydrate Polymers, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

Sediment depth-related variations of comammox Nitrospira: Evidence in the Three Gorges Reservoir, China - Baohong Yu; Quanchao Zeng; Jinlin Li; Jun Li; Xun Tan; Xin Gao; Ziqiang Mao; Ping Huang; Shengjun Wu (Science of The Total Environment, 2023)

Interactions between CuO NPs and PS: The release of copper ions and oxidative damage - Yan Cao; Senlin Tian; Yingxue Geng; Linfeng Zhang; Qun Zhao; Jie Chen; Yingjie Li; Xuewei Hu; Jianhong Huang; Ping Ning (Science of The Total Environment, 2023)

Microbial ecological clusters structured by environments drive maize residue decomposition at the continental scale - Meiling Zhang; Shiyu Wang; Liyu Zhang; Wentao Li; Mengmeng Cao; Shuyu Huang; Xinpeng Xu; Ping He; Wei Zhou; Laurent Philippot; Chao Ai (Science of The Total Environment, 2023)

C4 leaf development and evolution - Chi-Fa Huang; Wen-Yu Liu; Chun-Ping Yu; Shu-Hsing Wu; Maurice S.B. Ku; Wen-Hsiung Li (Current Opinion in Plant Biology, 2023)

Gas barrier coating based on cellulose nanocrystals and its preservation effects on mango - Mingxia Li; Zhenxu Shi; Shulin He; Qiang Hu; Ping Cai; Lin Gan; Jin Huang; Yongqiang Zhang (Carbohydrate Polymers, 2023)

Bamboo polysaccharides elicit hypocrellin A biosynthesis of a bambusicolous fungus Shiraia sp. S9 - Wen Hao Shen; Lu Lu Zhou; Xin Ping Li; Rui Peng Cong; Qun Yan Huang; Li Ping Zheng; Jian Wen Wang (World Journal of Microbiology and Biotechnology, 2023)

Association between thermal stress and cardiovascular mortality in the subtropics - Maidina Jingesi; Shuhua Lan; Jing Hu; Mengyi Dai; Suli Huang; Siyi Chen; Ning Liu; Ziquan Lv; Jiajia Ji; Xiaoheng Li; Peng Wang; Jinquan Cheng; et al. (International Journal of Biometeorology, 2023)

Comparative metabolomics analysis investigating the impact of melatonin-enriched diet on energy metabolism in the crayfish, Cherax destructor - Ying Yang; Jiangtao Tian; Wenyue Xu; Cuobaima Ping; Xinglin Du; Yucong Ye; Bihong Zhu; Yizhou Huang; Yiming Li; Qichen Jiang; Yunlong Zhao (Journal of Comparative Physiology B, 2023)

Establishment and characterization of a novel hilar cholangiocarcinoma cell line, CBC3T-1 - Mingzhen Bai; Ningzu Jiang; Wenkang Fu; Chongfei Huang; Liang Tian; Ningning Mi; Long Gao; Haidong Ma; Yawen Lu; Jie Cao; Chao Zhang; Ping Yue; et al. (Human Cell, 2023)
Cholangiocarcinoma (CCA) is a group of malignant heterogeneous cancer arising from the biliary tree. The tumor is characterized by insidious onset, high degree of malignancy, poor prognosis, and high recurrence rate. Immortalized cancer cell lines are the best and easiest models for in vitro cancer research. Here, we established a naturally immortalized highly tumorigenic hilar cholangiocarcinoma (hCCA) cell line, CBC3T-1. The CBC3T-1 cell line was cultured for over 60 passages. Thorough analysis showed that CBC3T-1 cells share characteristics similar to original tumor cells from patients with cholangiocarcinoma and display a stable phenotype, including features of epithelial origin, stem cell-like properties, as well as a high invasive and migratory capability and tumorigenicity in mice. Furthermore, this cell line showed the best sensitivity to paclitaxel, followed by gemcitabine. RNA sequencing and whole‑exome sequencing showed that cancer-associated pathways and somatic mutations played a dominant role in the development of CCA. We established and characterized a new hCCA cell line, CBC3T-1, which contributes to a better understanding of bile duct cancer, and can be used to study tumorigenesis and progression and the role of anticancer drugs.

Baicalin mitigates nephropathogenic infectious bronchitis virus infection-induced spleen injury via modulation of mitophagy and macrophage polarization in Hy-Line chick - Guanming Tian; Cheng Huang; Zhengqing Li; Zhihua Lu; Chenlu Feng; Yu Zhuang; Guyue Li; Ping Liu; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Veterinary Microbiology, 2023)

All-natural environmentally degradable poly (butylene terephthalate-co-caprolactone): A theoretical and experimental study of its degradation properties and mechanisms - Peng-Yuan Xu; Ping-Li Wang; Tian-Yuan Liu; Zhi-Chao Zhen; Bo Lu; Dan Huang; Ge-Xia Wang; Jun-Hui Ji (Science of The Total Environment, 2023)

Contribution of the bacterial community of poorly fermented oat silage to biogas emissions on the Qinghai Tibetan Plateau - Chaosheng Liao; Binbin Na; Xiaolong Tang; Man Zhao; Changbing Zhang; Shiyong Chen; Minghong You; Binqiang Bai; Lizhuang Hao; Dorjeeh Tondrob; Guangpeng Qu; Shuqing Yang; et al. (Science of The Total Environment, 2023)

Geochemical and provenance heterogeneity of small mountainous river systems in Southeast China - Yalong Li; Xiangtong Huang; Ergang Lian; Chao Li; Juan Xu; Ping Yin; Zhen Song; Shouye Yang (Global and Planetary Change, 2023)

High starch diets attenuate the immune function of Micropterus salmoides immune organs by modulating Keap1/Nrf2 and MAPK signaling pathways - Hongli Liu; Baipeng Chen; Yanhao Cao; Yi Geng; Ping Ouyang; Defang Chen; Liangyu Li; Xiaoli Huang (Fish & Shellfish Immunology, 2023)

Vertical variation in prokaryotic community composition and co-occurrence patterns in sediments of the Three Gorges Reservoir, China - Baohong Yu; Quanchao Zeng; Jinlin Li; Jun Li; Xun Tan; Xin Gao; Ping Huang; Shengjun Wu (Environmental Research, 2023)

Ketoprofen exposure perturbs nitrogen assimilation and ATP synthesis in rice roots: An integrated metabolome and microbiome analysis - Huan Wang; Zhiheng Li; Luoqin Shen; Ping Zhang; Yanyao Lin; Xinting Huang; Shaoting Du; Huijun Liu (Environmental Pollution, 2023)

Preparation and properties of thermal insulation coating based on silica aerogel - Song He; Xiya Wu; Xiaoqian Zhang; Junwei Sun; Fuliang Tian; Saiping Guo; Haipeng Du; Ping Li; Yajun Huang (Energy and Buildings, 2023)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

Tandem c-cl cleavage and oxidation over Pt/ZSM-5 catalysts for CH2Cl2 deep oxidation: Acidity – Redox synergy, rate – Limiting step, and catalyst stability - Yu-Kun Ma; Li-Li Xu; Long-Ren Ouyang; Lu-Lu Huang; Ai-Ping Jia; Yu Wang; Ji-Qing Lu (Chemical Engineering Journal, 2023)

Repair of dysfunctional bone marrow endothelial cells alleviates aplastic anemia - Shu-Qian Tang; Tong Xing; Zhong-Shi Lyu; Li-Ping Guo; Mi Liang; Chen-Yuan Li; Yuan-Yuan Zhang; Yu Wang; Lan-Ping Xu; Xiao-Hui Zhang; Xiao-Jun Huang; Yuan Kong (Science China Life Sciences, 2023)

Construction Safety Risk Assessment and Early Warning of Nearshore Tunnel Based on BIM Technology - Ping Wu; Linxi Yang; Wangxin Li; Jiamin Huang; Yidong Xu (Journal of Marine Science and Engineering, 2023)
The challenging nature of nearshore tunnel construction environments introduces a multitude of potential hazards, consequently escalating the likelihood of incidents such as water influx. Existing construction safety risk management methodologies often depend on subjective experiences, leading to inconsistent reliability in assessment outcomes. The multifaceted nature of construction safety risk factors, their sources, and structures complicate the validation of these assessments, thus compromising their precision. Moreover, risk assessments generally occur pre-construction, leaving on-site personnel incapable of recommending pragmatic mitigation strategies based on real-time safety issues. To address these concerns, this paper introduces a construction safety risk assessment approach for nearshore tunnels based on multi-data fusion. In addressing the issue of temporal effectiveness when the conflict factor K in traditional Dempster–Shafer (DS) evidence theory nears infinity, the confidence Hellinger distance is incorporated for improvement. This is designed to accurately demonstrate the degree of conflict between two evidence chains. Subsequently, an integrated evaluation of construction safety risks for a specific nearshore tunnel in Ningbo is conducted through the calculation of similarity, support degree, and weight factors. Simultaneously, the Revit secondary development technology is utilized to visualize risk monitoring point warnings. The evaluation concludes that monitoring point K7+860 exhibits a level II risk, whereas other monitoring points maintain a normal status.

Co-isolated bacteria from septicemia of female Siberian sturgeon broodstock: Lactococcus petauri resisting Aeromonas hydrophila infection - Defang Chen; Fei Yang; Lei Yang; Qiaolin Pei; Xin Zhang; Xiaoli Huang; Ping Ouyang; Zhiqiong Li; Yi Geng (Aquaculture, 2023)

Innovative pyrite-based constructed wetland-microbial fuel cell for enhancing nutrients removal and bioelectricity generation - Zhi-Wei Zhu; Pei Xu; Li Yu; Xian-Huai Huang; Hou-Yun Yang; Wei-Hua Li; Ping Zhang; Jian Chen; Ling-Tao Kong (Journal of Water Process Engineering, 2023)

Polystyrene microplastic attenuated the toxic effects of florfenicol on rice (Oryza sativa L.) seedlings in hydroponics: From the perspective of oxidative response, phototoxicity and molecular metabolism - Luoqin Shen; Ping Zhang; Yanyao Lin; Xinting Huang; Siyi Zhang; Zhiheng Li; Zhiguo Fang; Yuezhong Wen; Huijun Liu (Journal of Hazardous Materials, 2023)

What entrepreneurial ecosystem elements promote sustainable entrepreneurship? - Yangjie Huang; Ping Li; Yajing Bu; Guojing Zhao (Journal of Cleaner Production, 2023)

Red mud with enhanced dealkalization performance by supercritical water technology for efficient SO2 capture - Zimeng Nie; Qun Zhao; Qilin Zhao; Yingjie Li; Dian Yang; Huaying Liu; Shupu Yang; Jie Li; Senlin Tian; Chen Li; Cheng Tie; Jianhong Huang; et al. (Journal of Environmental Management, 2023)

Fabrication of multi-morphological Bi2O2(OH)NO3-BiVO4 Z-Scheme heterojunction for enhanced photocatalytic antibiotic removal performance - Jinhai Li; Chenyu Wang; Jianhai Zhou; Zhang Ping; Guopei Huang; Yuanhui Wu; Shuxing Luo; Dongmei Bao; Zhu Wen; Pili Lu (Journal of Environmental Chemical Engineering, 2023)

A neglected contributor of thermal hydrolysis to sludge anaerobic digestion: Fulvic acids release and their influences - Mingze Shi; Hongbo Liu; Xuedong Zhang; Yajie Li; Fang Huang; Cheng Zhao; Jun Guo; Ping Wu; He Liu (Journal of Environmental Management, 2023)

Sulfur-doped Sb4Mo10O31 bimetallic sulfur-oxide catalyst for highly efficient reduction of toxic organic and hexavalent chromium under dark - Ping Li; Qinhan Wu; Qiao Ji; Adugna Boke Abdeta; Dong-Hau Kuo; Ting Huang; Hanya Zhang; Osman Ahmed Zelekew; Jinguo Lin; Xiaoyun Chen (Journal of Environmental Chemical Engineering, 2023)

Application of Mo2C for enhancement of co-catalytic performance of Fe3+/PS based fenton-like reaction in degrading tetracycline hydrochloride - Hao Cheng; Yi Wen; Chao Huang; Ping Wang; Chengyou Sun; Chongling Feng; Jialu Xu; Li Du; Ting Yan; Min Cheng (Chemical Engineering Journal, 2023)

Human TRMT1 catalyzes m2G or m22G formation on tRNAs in a substrate-dependent manner - Qing-Ping Xiong; Jing Li; Hao Li; Zhi-Xuan Huang; Han Dong; En-Duo Wang; Ru-Juan Liu (Science China Life Sciences, 2023)

The Epidemiology of Tinea Capitis in Guangxi Province, China - Dongyan Zheng; Tianwei Liang; Weixuan Wu; Najwa Al-Odaini; Kaisu Pan; Lan Huang; Guomei Huang; Lulu Tang; Xinlei Li; Shao He; Huahui Jian; Nibo Wei; et al. (Mycopathologia, 2023)

Lateral flow DNA biosensor for visual detection of nucleic acid with triple-helix DNA functionalized carbon nanotube - Yan Huang; Zhihao Cheng; Li-Ping Xu; Xueji Zhang; Guodong Liu (Analytica Chimica Acta, 2023)

Co-adsorption mechanisms of As(V) and Cd(II) by three-dimensional flower-like Mg/Al/Fe-CLDH synthesized by “memory effect” - Donghui Chen; Ruiyue Li; Fangming Nan; Hong Li; Ping Huang; Wei Zhan (Environmental Science and Pollution Research, 2023)

Insights into the life-cycle of aerobic granular sludge in a continuous flow membrane bioreactor by tracing its heterogeneous properties at different stages - Biao Yang; Weifeng Liang; Liying Bin; Weirui Chen; Xinyi Chen; Ping Li; Shanglong Wen; Shaosong Huang; Bing Tang (Water Research, 2023)

Assessing tunnel basement structure damage under train excitation: Impacts of surrounding rock deterioration - Zi-Qiang Li; Kun-ping Chen; Wei-wei Huang; Jian-wen Feng; Hang Zhang; Zheng Li; Shi-jian Yang (Transportation Geotechnics, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

A novel global snow depth retrieval method considering snow metamorphism and forest influence - Shuo Gao; Zhen Li; Ping Zhang; Quan Chen; Lei Huang; Jianmin Zhou; Changjun Zhao; Haiwei Qiao; Zhaojun Zheng (Remote Sensing of Environment, 2023)

Comprehensive understanding of tetracycline hydrochloride adsorption mechanism onto biochar-based gel pellets based on the combination of characterization-based and approximate site energy distribution methods - Bai-Qin Zhou; Qian-Qian Sang; Yu-Jun Wang; Hui Huang; Fang-Jun Wang; Rui-Chun Yang; Yuan-Tian Zhao; Zi-Jie Xiao; Chun-Yue Zhang; Hui-Ping Li (Journal of Cleaner Production, 2023)

Reduction and adsorption of uranium(VI) from aqueous solutions using nanoscale zero-valent manganese - Xiaohan Li; Juanxi Huang; Zhengqin Shi; Yuan Xie; Zhengfan Xu; Jianyou Long; Gang Song; Yaxuan Wang; Gaosheng Zhang; Xiatiao Luo; Ping Zhang; Shuxiang Zha; et al. (Journal of Environmental Management, 2023)

Plant facilitation improves carbon production efficiency while reducing nitrogen input in semiarid agroecosystem - Wei Wang; Meng-Ying Li; Shuang-Guo Zhu; Aziz Khan; Xiu-Ping Tao; Guang-Fu Huang; Hai-Ying Liu; Wei Zhang; Hong-Yan Tao; Dong-Shan Gong; Chao Song; You-Cai Xiong (CATENA, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Minimal addition of transglutaminase on the preparation and characteristics of tilapia (Oreochromis mossambicus) surimi - Ping-Hsiu Huang; Yu-Tsung Cheng; Yung-Jia Chan; Wen-Chien Lu; Wen-Ching Ko; Hung-Chun Hsieh; Po-Hsien Li (Fisheries Science, 2023)

Study of advanced dewatering and its influence on tunnel in water rich and sandy dolomite stratum - Yifan Jiang; Jinyi Li; Feicong Zhou; Qi Yongli; Hua Huang; Xiaobing Li; Zhijie Wang; Ping Zhou (Bulletin of Engineering Geology and the Environment, 2023)

Mechanism of aconitine mediated neuronal apoptosis induced by mitochondrial calcium overload caused by MCU - Chen Jiang; Jun Shen; Chun Wang; Yongjie Huang; Linbo Wang; Yiran Yang; Wen Hu; Ping Li; Haiying Wu (Toxicology Letters, 2023)

Naturally and chemically acetylated polysaccharides: Structural characteristics, synthesis, activities, and applications in the delivery system: A review - Hongyu Li; Yingping Wang; Ping Zhao; Lanping Guo; Luqi Huang; Xia Li; Wenyuan Gao (Carbohydrate Polymers, 2023)

Application of 210Pbex in elucidating contemporary sedimentary dynamics in the water-level fluctuation zone of the Three Gorges Reservoir, China - Jinlin Li; Yuhai Bao; Jie Wei; Xiubin He; Qiang Tang; Xinbao Zhang; Shengjun Wu; Ping Huang; Hong Li (CATENA, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

Constructed a self-powered sensing platform based on nitrogen-doped hollow carbon nanospheres for ultra-sensitive detection and real-time tracking of double markers - Yong-ping Gao; Ke-jing Huang; Bo-ya Wang; Qianyue Xu; Honglei Shuai; Guoqiang Li (Analytica Chimica Acta, 2023)

Effects and mechanisms of natural products on Alzheimer’s disease - Zhijun Yang; Dan-Dan Zhou; Si-Yu Huang; Ai-Ping Fang; Hua-Bin Li; Hui-Lian Zhu (Critical Reviews in Food Science and Nutrition, 2023)

Benfotiamine attenuates the high-carbohydrate diet-induced mitochondrial redox imbalance in fish Megalobrama amblycephala by activating SIRT3 - Ling Zhang; Ya-Ping Ge; Yang-Yang Huang; Wei-Liang Chen; Wen-Bin Liu; Ding-Dong Zhang; Xiang-Fei Li (Aquaculture, 2023)

Contamination characteristics and source analysis of potentially toxic elements in dustfall-soil-crop systems near non-ferrous mining areas of Yunnan, southwestern China - Ying Luo; Zhe Wang; Zhen-Long Zhang; Jia-Qian Zhang; Qiu-Ping Zeng; Duan Tian; Chao Li; Feng-Yu Huang; Shu Chen; Li Chen (Science of The Total Environment, 2023)

Photoaged microplastics induce neurotoxicity via oxidative stress and abnormal neurotransmission in zebrafish larvae (Danio rerio) - Ping Ding; Chongdan Xiang; Xintong Li; Haibo Chen; Xiaoxia Shi; Xin Li; Chushan Huang; Yunjiang Yu; Jianying Qi; Adela Jing Li; Lijuan Zhang; Guocheng Hu (Science of The Total Environment, 2023)

Sinomenine ameliorates rheumatoid arthritis by modulating tryptophan metabolism and activating aryl hydrocarbon receptor via gut microbiota regulation - Zheng-Meng Jiang; Su-Ling Zeng; Tian-Qing Huang; Yang Lin; Fang-Fang Wang; Xing-Jiao Gao; Jing Li; Ping Li; E-Hu Liu (Science Bulletin, 2023)

Fluorescence tracing the degradation process of biodegradable PBAT: Visualization and high sensitivity - Tian-Yuan Liu; Zhi-Chao Zhen; Xiao-Ling Zang; Peng-Yuan Xu; Ge-Xia Wang; Bo Lu; Fei Li; Ping-Li Wang; Dan Huang; Jun-Hui Ji (Journal of Hazardous Materials, 2023)

Different dietary fibers unequally remodel gut microbiota and charge up anti-obesity effects - Jia-Jia Wen; Ming-Zhi Li; Jie-Lun Hu; Jiang Wang; Zhi-Qiang Wang; Chun-Hua Chen; Jing-Rui Yang; Xiao-Jun Huang; Ming-Yong Xie; Shao-Ping Nie (Food Hydrocolloids, 2023)

Characterization of two putative norlaudanosoline methyltransferases from Aristolochia debilis - Xiaotao Tuo; Zhiyin Yu; Junheng Li; Yuxin Qi; Guoqing Peng; Sheng-Xiong Huang; Xueshuang Huang; Jian-Ping Huang (Journal of Plant Physiology, 2023)

Ultra-low concentration terbium (Tb) adsorption on garlic peels biosorbent and its application for Nd-Fe-B scraps recovery - Qingqing Chang; Ping Li; Yunwu Han; Xindi Guan; Jiachun Xiong; Qian Li; Hailin Zhang; Kai Huang; Xin Zhang; Haijiao Xie; Tao Qi (Journal of Environmental Chemical Engineering, 2023)

Tetracycline degradation by persulfate activated with nitrogen magnetic graphene oxide confined Fe/Co dual single-atom catalyst: Performance and degradation mechanism - Chenxi Huang; Meifang Li; Ping Wang; Shiyu Song; Beixia Chai; Meijuan Zhang; Xinjiang Hu; Jingju Cai; Shaohua Wu; Qingyun He (Journal of Environmental Chemical Engineering, 2023)

PSS modified by 3-aminopropyltrimethoxysilane linking large-area GNPs/PSS to silicone rubber with stable interface combination for high sensitivity flexible resistive sensor - Han Feng; Ping Liu; Xu Guo; Junliang Li; Yifan Sun; Shunge Wu; Ruohai Hu; Zhi Liu; Helei Tian; Yuanming Ma; Caixia Liu; Houzhu Huang; et al. (Chemical Engineering Journal, 2023)

Rapid granulation of aerobic granular sludge in an integrated moving bed biofilm reactor-membrane bioreactor: Effects and mechanism of Streptomyces cellulosus microspheres - Huanlong Zhang; Yue Xu; Liying Bin; Ping Li; Fenglian Fu; Shaosong Huang; Bing Tang (Bioresource Technology Reports, 2023)

Mining genes related to anthocyanin synthesis and regulation in different potato varieties based on comparative transcriptomics - En-fang Qi; Xiao-xia Jia; He-ping Lv; Wei Huang; Guo-hong Wen; Zhang Li; Jian-wu Li (Journal of Plant Biochemistry and Biotechnology, 2023)

Numerical simulation of the electromagnetic field in layered media applicable to high-frequency scenarios - Kun Li; Xu-Ri Huang; Kang Chen; Yun-Gui Xu; Wei-Ping Cao (Applied Geophysics, 2023)

Incidence and Risk Factors for Dysphagia Following Cerebellar Stroke: a Retrospective Cohort Study - Li Huang; Yunlu Wang; Jikang Sun; Lequn Zhu; Jimin Liu; Yuwei Wu; Chunlei Shan; Juntao Yan; Ping Wan (The Cerebellum, 2023)
The cerebellum is known to play a supportive role in swallowing-related functions; however, wide discrepancies about the incidence rate of swallowing disorders following cerebellar strokes exist within the literature. This study aimed to investigate the incidence rate of dysphagia and the factors which may affect the presence of dysphagia and clinical recovery in individuals diagnosed with cerebellar stroke. A retrospective chart audit of 1651 post-stroke patients (1049 males and 602 females) admitted with a cerebellar stroke to a comprehensive tertiary hospital in China was conducted. Data on demographics, medical, along with swallowing function assessment were collected. Differences between dysphagic and non-dysphagic groups were evaluated using t -tests and Pearson’s chi-square test. Univariate logistic regression analysis was performed to establish factors associated with the presence of dysphagia. A total of 11.45% of participants were identified with dysphagia during inpatient admission. Individuals with mixed types of stroke, multiple lesions in the cerebellum, and ages older than 85 years old were more likely to develop dysphagia. Moreover, the prognosis of dysphagia following a cerebellar stroke was associated with lesions in different parts of the cerebellum. The cumulative recovery rates from the best to worse were the right hemisphere group, the cerebellum vermis or peduncle group, and both the hemisphere group and the left hemisphere group, respectively.

Corrigendum to “Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus)” [Aquaculture 563 (2023) /739023] - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Authentication, chemical profiles analysis, and quality evaluation of corn silk via DNA barcoding and UPLC-LTQ/Orbitrap MS chemical profiling - Ping Li; Ying Huang; Hongyu Zhu; Jiaxin Chen; Guangxi Ren; Dan Jiang; Chunsheng Liu (Food Research International, 2023)

Effects of chitosan coating combined with thermal treatment on physicochemical properties, bacterial diversity and volatile flavor of braised duck meat during refrigerated storage - Huanhuan Li; Sijia Qu; Ping Ma; Jin Zhang; Ke Zhao; Lihong Chen; Qicheng Huang; Gaohang Zou; Honggang Tang (Food Research International, 2023)

Ciprofloxacin degradation performances and mechanisms by the heterogeneous electro-Fenton with flocculated fermentation biochar - Yanchao Jin; Peiwen Huang; Xiongjian Chen; Li-Ping Li; Chun-Yan Lin; Xiao Chen; Rui Ding; Jianxi Liu; Riyao Chen (Environmental Pollution, 2023)

Intelligent shielding material based on VO2 with tunable near-field and far-field electromagnetic response - Si-Yuan Liao; Xiao-Yun Wang; Hai-Peng Huang; Yu-Ying Shi; Qiao-Feng Wang; You-Gen Hu; Peng-Li Zhu; Rong Sun; Ching-Ping Wong; Yan-Jun Wan (Chemical Engineering Journal, 2023)

Unusual hcp Ni with metal and non-metal dual doping modulation to realize boosted urea oxidation - Ping Li; Yuqi Huang; Xiao Ouyang; Wenqin Li; Fengli Li; Shuanghong Tian (Chemical Engineering Journal, 2023)

Rational design of an in-build quasi-solid-state electrolyte for high-performance lithium-ion batteries with the silicon-based anode - Enyou Zhao; Shiqiang Luo; Anyi Hu; Zhu Liao; Chenxi Huang; Orita Akihiro; Ping Jiang; Li Yang (Chemical Engineering Journal, 2023)

Maternal environmental, occupational, and urinary metabolite levels of benzene compounds and their association with congenital heart diseases in offspring: a case‒control study in China - Meixian Wang; Lu Li; Hong Kang; Hongmei Xu; Qian Huang; Nana Li; Ying Deng; Ping Yu; Zhen Liu (Environmental Science and Pollution Research, 2023)
The conclusions about the association of maternal pregnancy environment, occupation, and benzene compounds with fetal CHD are not entirely consistent. Eight hundred seven CHD cases and 1008 controls were included in this study. All occupations were classified and coded against the Occupational Classification Dictionary of the People’s Republic of China (2015 version). Logistic regressions were used to explore the correlation among environmental factors, occupation types, and CHDs in offspring. We found that living near public facilities and having exposure to chemical reagents and hazardous substances were significant risk factors for CHDs in offspring. We found that offspring of mothers who worked in agriculture and similar work during pregnancy suffered from CHD. The risk of all CHDs in the offspring of pregnant women working in production manufacturing and related work was significantly higher than that in unemployed pregnant women, the risk was also observed in 4 subtypes of CHDs. We compared the concentrations of the five metabolite (MA, mHA, HA, PGA, and SPMA) levels of benzene compounds in the urine of mothers in case and control groups and found no significant differences. Our study suggests that maternal exposure during pregnancy and certain environmental and occupational conditions are risk factors for CHD in offspring, but did not support an association between concentrations of metabolites of benzene compounds in the urine of pregnant women and CHDs in their offspring.

Megastigmane glycosides from Streblus ilicifolius (S.Vidal) Corner and their anti-inflammatory activity - Yan Huang; Liwei Pan; Yanling Chang; Xiaoqin Liang; Ping Hou; Chenyang Ren; Weifeng Xu; Ruiyun Yang; Jun Li; Buming Liu (Phytochemistry, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

Global/local buckling analysis of thin-walled I-section beams via hierarchical one-dimensional finite elements - Yichen Yang; Yanchuan Hui; Ping Li; Jie Yang; Qun Huang; Gaetano Giunta; Salim Belouettar; Heng Hu (Engineering Structures, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

Single-base resolution mapping of 2′-O-methylation sites by an exoribonuclease-enriched chemical method - Ping Zhang; Junhong Huang; Wujian Zheng; Lifan Chen; Shurong Liu; Anrui Liu; Jiayi Ye; Jie Zhou; Zhirong Chen; Qiaojuan Huang; Shun Liu; Keren Zhou; et al. (Science China Life Sciences, 2023)

Isothermal exponential amplification reactions triggered by circular templates (cEXPAR) targeting miRNA - Xue-mei Qu; Xiao-dong Ren; Ning Su; Xian-ge Sun; Shao-li Deng; Wei-ping Lu; Qing Huang (Molecular Biology Reports, 2023)

Correction to: Geographical, Sex, Age, and Seasonal Differences in Serum Manganese Status Among Chinese Adults with Hypertension - Hong Chen; Zhixin Cui; Wenhai Lu; Ping Wang; Jia Wang; Ziyi Zhou; Nan Zhang; Zhuo Wang; Tengfei Lin; Yun Song; Lishun Liu; Xiao Huang; et al. (Biological Trace Element Research, 2023)

A novel label-free dual-mode aptasensor based on the mutual regulation of silver nanoclusters and MoSe2 nanosheets for reliable detection of ampicillin - Pengfei Fan; Xin Qian; Qianji Li; Ping Jiang; Qian Wu; Guang Huang; Zhan Zhang; Lei Li (Analytica Chimica Acta, 2023)

Efficiency of scientific and technological resource allocation in Chengdu–Chongqing–Mianyang Urban agglomeration: based on DEA–Malmquist index model - Ruochen Li; Yuyan Luo; Borui Chen; Huan Huang; Ping Liu (Environment, Development and Sustainability, 2023)

Transcriptome analysis reveals insight into the protective effect of N-acetylcysteine against cadmium toxicity in Ganoderma lucidum (Polyporales: Polyporaceae) - Xin Jin; Peng Wu; Ping Li; Chuan Xiong; Mingying Gui; Wenli Huang (Environmental Science and Pollution Research, 2023)

Thallium removal from wastewater using sulfidized zero-valent manganese: Effects of sulfidation method and liquid nitrogen pretreatment - Zhengqin Shi; Ping Zhang; Xiaohan Li; Yijie Zheng; Juanxi Huang; Yaxuan Wang; Xiatiao Luo; Gaosheng Zhang; Tangfu Xiao; Jianyou Long; Huosheng Li (Chemosphere, 2023)

On-road mobile mapping of spatial variations and source contributions of ammonia in Beijing, China - Weiwei Pu; Jiujiang Sheng; Ping Tian; Mengyu Huang; Xiangxue Liu; Jeffrey L. Collett; Ziming Li; Xiujuan Zhao; Di He; Fan Dong; Nannan Zhang; Weijun Quan; et al. (Science of The Total Environment, 2023)

Accelerated Fe(III)/Fe(II) cycle for rapid elimination of Rhodamine B by a novel Mo2C co-catalytic Fe2+/H2O2 system - Hao Cheng; Xinyan Li; Chao Huang; Jian Zhu; Ping Wang; Heng Cao; Chongling Feng; Dingxun Ling; Hao Liu; Min Cheng (Journal of Cleaner Production, 2023)

Quality assessment of variable collagen tissues of sea cucumber (Stichopus japonicus) body wall under different heat treatment durations by label-Free proteomics analysis - Yi-Zhen Huang; Yi-Sha Xie; Yan-Xin Li; Mei-Yu Zhao; Na Sun; Hang Qi; Xiu-Ping Dong (Food Research International, 2023)

Tea polyphenol and epigallocatechin gallate ameliorate hyperlipidemia via regulating liver metabolism and remodeling gut microbiota - Jia-Jia Wen; Ming-Zhi Li; Chun-Hua Chen; Tao Hong; Jing-Rui Yang; Xiao-Jun Huang; Fang Geng; Jie-Lun Hu; Shao-Ping Nie (Food Chemistry, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

Preparation of alumina/silica/exfoliated graphite nanoplatelets composite aerogels and its application as supporting material for erythritol based form-stable phase change materials - Yu-Hao Ning; Ye Tan; Chuan-Huang Lin; Qi Li; Lin-Ping Yu; Zhong Cao; Li-Xian Sun; Chuan-Chang Li; Ju-Lan Zeng (Chemical Engineering Journal, 2023)

Liquid water determination by airborne millimeter cloud radar and in-situ size distribution measurements - Dongfei Zuo; Dantong Liu; Delong Zhao; Ling Yang; Yichen Chen; Wei Zhou; Mengyu Huang; Hui He; Ping Tian; Yuanmou Du; Wei Xiao; Ruijie Li; et al. (Atmospheric Research, 2023)

Glucocorticoid and glycolysis inhibitors cooperatively abrogate acute graft-versus-host disease - Qi Wen; Zheng-Li Xu; Yu Wang; Meng Lv; Yang Song; Zhong-Shi Lyv; Tong Xing; Lan-Ping Xu; Xiao-Hui Zhang; Xiao-Jun Huang; Yuan Kong (Science China Life Sciences, 2023)

Exploration of the link between gut microbiota and purinergic signalling - MingJian Li; BoWen Liu; Rong Li; Ping Yang; Ping Leng; Yong Huang (Purinergic Signalling, 2023)
Growing evidence reveals that microorganisms in the gut are linked to metabolic health and disease risk in human beings to a considerable extent. The focus of research at this stage must tend to focus on cause-and-effect studies. In addition to being a component of DNA and RNA, purine metabolites can be involved in purine signalling in the body as chemical messengers. Abnormalities in purinergic signalling may lead to neuropathy, rheumatic immune diseases, inflammation, tumors, and a wide range of other diseases. It has proved that gut microbes are involved in purinergic signalling. The relationship between these gut-derived purinergic signalling molecules and host metabolism may be one of the important clues to our understanding of the mechanisms by which the microbiota affects host metabolism.

Comparison between the stem and leaf photosynthetic productivity in Eucalyptus urophylla plantations with different age - Xia Chen; Mingyu Luo; Yulin Kang; Ping Zhao; Zhiyao Tang; Yuanyuan Meng; Li Huang; Yanpei Guo; Xiancheng Lu; Lei Ouyang; Markku Larjavaara (Planta, 2023)

Correction to: Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2023)

Anti-Vascular Endothelial Growth Factor Therapy Abolishes Glioma-Associated Endothelial Cell-Induced Tumor Invasion - Feng Tang; Feng-Ping Li; Xue-Tao Huang; Guo-Hua Wang; Ze-Fen Wang; Zhi-Qiang Li (Journal of Molecular Neuroscience, 2023)

Transcriptomic analysis provides new insights into the secondary follicle growth in spotted scat (Scatophagus argus) - Mou-Yan Jiang; Yi-Fan Zhou; Hao Liu; You-Xing Peng; Yuan-Qing Huang; Si-Ping Deng; Yang Huang; Gang Shi; Chun-Hua Zhu; Guang-Li Li; Dong-Neng Jiang (Frontiers in Marine Science, 2023)
Spotted scat ( Scatophagus argus ) is an important mariculture fish that is of great economic significance in East and Southeast Asia. To date, there are no studies on ovary development and regulation in S. argus . Herein, the ovary transcriptome profiles of S. argus at different stages were constructed, and the genes and pathways potentially involved in secondary follicle growth were identified. A total of 25,426 genes were detected by sequencing the mRNAs from the ovary libraries at stage III (n=3) and IV (n=3). Notably, 2950 and 716 genes were up-regulated and down-regulated in the stage IV ovary, respectively, compared to the stage III ovary. The differentially expressed genes (DEGs) were found to be mostly involved in regulating steroidogenesis, vitellogenesis, lipid metabolism, and meiosis. Up-regulation of steroid hormone synthesis pathway genes ( fshr , cyp17a1 , and foxl2 ) and insulin-like growth factor pathway genes ( igf1r , ifg2r , igfbp1 , igfbp3 , and igfbp7 ) in the ovary at stage IV was possibly the reason for the increased serum estrogen. Moreover, ppara , ppard , fabp3 , and lpl were up-regulated in the stage IV ovary and were potentially involved in the lipid droplet formation in the oocyte. Many DEGs were involved in the cellular cycle, meiosis, and cAMP or cGMP synthesis and hydrolysis, indicating that meiosis was restarted at stage IV ovary. In addition, numerous TGF-beta signal pathway genes were up-regulated in the stage IV ovary. This ovary transcript dataset forms a baseline for investigating functional genes associated with oogenesis in S. argus .

Compound minirhizotron device for root phenotype and water content near root zone - Lei Geng; Li Li; Wenyi Sheng; Quan Sun; Jiahao Yang; Qicheng Huang; Ping Lv (Computers and Electronics in Agriculture, 2023)

Source characterization of volatile organic compounds in urban Beijing and its links to secondary organic aerosol formation - Quan Liu; Jiujiang Sheng; Yangzhou Wu; Zhiqiang Ma; Junying Sun; Ping Tian; Delong Zhao; Xia Li; Kang Hu; Siyuan Li; Xiaojing Shen; Yangmei Zhang; et al. (Science of The Total Environment, 2023)

Kojicone C, new anti-inflammatory polyketide from insect-associated fungus Aspergillus versicolor - Tian-Xiao Li; Chi Zhang; Feng-Cheng Shi; Ye Ye; Jia-Le Huang; Lei Wu; Chun-Ping Xu (Phytochemistry Letters, 2023)

Spectral change of dissolved organic matter after extracted by solid-phase extraction and its feasibility in predicting the acute toxicity of polar organic pollutants in textile wastewater - Lingfang Fu; Liying Bin; Zhaobo Luo; Zehong Huang; Ping Li; Shaosong Huang; Dieudonne Nyobe; Fenglian Fu; Bing Tang (Journal of Hazardous Materials, 2023)

Synthesis of cationic polymer decorated with halogen for highly efficient trapping 99TcO4-/ReO4- - You-Gan Wang; Qing-Hua Hu; Juan Huang; Wei Jiang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

Soil particle size fractions affect arsenic (As) release and speciation: Insights into dissolved organic matter and functional genes - Qi Zou; Hang Wei; Zhiliang Chen; Ping Ye; Jianqiang Zhang; Mengqiang Sun; Ling Huang; Jing Li (Journal of Hazardous Materials, 2023)

Research on the hydrothermal regeneration of powdered activated coke in wastewater treatment - Zhanyao Li; Guifang Chen; Huiru Ma; Fuyu Huang; Hao Xu; Liqiang Zhang; Xueliang Yuan; Xinyan Zhang; Shouyan Chen; Ping Zhou (Journal of Environmental Chemical Engineering, 2023)

Enhanced elimination of Cr(VI) from aqueous media by polyethyleneimine modified corn straw biochar supported sulfide nanoscale zero valent iron: Performance and mechanism - Haoran Tian; Chao Huang; Ping Wang; Jie Wei; Xinyan Li; Ruimei Zhang; Dingxun Ling; Chongling Feng; Hao Liu; Mengxin Wang; Zhiming Liu (Bioresource Technology, 2023)

Chinese consensus guidelines for therapeutic drug monitoring of polymyxin B, endorsed by the Infection and Chemotherapy Committee of the Shanghai Medical Association and the Therapeutic Drug Monitoring Committee of the Chinese Pharmacological Society - Xiaofen Liu; Chenrong Huang; Phillip J. Bergen; Jian Li; Jingjing Zhang; Yijian Chen; Yongchuan Chen; Beining Guo; Fupin Hu; Jinfang Hu; Linlin Hu; Xin Li; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Biofertilizer made from a mixed microbial community can enhance the suppression of fusarium wilt of banana when combined with acid soil ameliorant - Jianfeng Huang; Yuwan Pang; Gen Cheng; Tengfei Wu; Qiaoyi Huang; Xu Huang; Qiong Yi; Mu Zhang; Shuanhu Tang; Hongting Fu; Ping Li (European Journal of Plant Pathology, 2023)

Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus) - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Ultra-depleted melt product preserved in the Ladong ophiolitic peridotites of the North Qilian Orogenic Belt, Northern Tibet - Xiang Zhou; Jian-Ping Zheng; Zeng-Bao Huang; Zhi-Yong Li; Wei-Qi Zhang; Hong-Da Zheng; Qing Xiong; Hong-Kun Dai (Lithos, 2023)

Confined Fe single atomic sites on (100) plane of anatase TiO2 nanofibers boost white LED driven Fenton-like norfloxacin degradation - Zhilin Ji; Rongsheng Cai; Wanneng Ye; Ping Lu; Chung-Li Dong; Yu-Cheng Huang; Xilin She; Denys S. Butenko; Yiming Liu; Yukun Zhu; Dongjiang Yang (Journal of Cleaner Production, 2023)

Pilot test of low-rank coal pyrolysis coupled with gasification to hydrogen-rich gas for direct reduced iron: Process modeling, simulation and thermodynamic analysis - Qian Liu; Ying-jie Zhao; Yi Huang; Feng Pei; Yang Cui; Li-juan Shi; Li-ping Chang; Qun Yi (Fuel, 2023)

Correction to: Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2023)

Geographical, Sex, Age, and Seasonal Differences in Serum Manganese Status Among Chinese Adults with Hypertension - Hong Chen; Zhixin Cui; Wenhai Lu; Ping Wang; Jia Wang; Ziyi Zhou; Nan Zhang; Zhuo Wang; Tengfei Lin; Yun Song; Lishun Liu; Xiao Huang; et al. (Biological Trace Element Research, 2023)

The self-powered electrochemical biosensing platform with multi-amplification strategy for ultrasensitive detection of microRNA-155 - Yong-ping Gao; Ke-jing Huang; Fu-ting Wang; Yang-yang Hou; Lu-di Zhao; Bo-ya Wang; Jing Xu; Honglei Shuai; Guoqiang Li (Analytica Chimica Acta, 2023)

Identification and expression profiling of receptor‐interacting serine/threonine‐protein kinase 2 in Siberian sturgeon ( Acipenser baerii ) - Lu Lu; Shaotong Dai; Hao Zhu; Xin Zhang; Zhiqiong Li; Xiaoli Huang; Ping Ouyang; Yi Geng; Defang Chen (Journal of Fish Biology, 2023)
Receptor‐interacting serine/threonine‐protein kinase 2 (RIPK2) is an adaptor protein of the pattern recognition receptors NOD1 and NOD2 involved in regulating inflammatory response and resisting pathogenic microbial infection. In this study, Acipenser baerii RIPK2 ( AbRIPK2 ) was identified. The open reading frame of AbRIPK2 was 1815 bp encoding 604 amino acids. AbRIPK2 possessed the typical N‐terminal kinase domain (KD) and C‐terminal caspase recruitment domain (CARD). The phylogenetic tree analysis revealed that AbRIPK2 shared a relatively high identity with bony fish. Real‐time fluorescence quantitative PCR (qRT‐PCR) results indicated that AbRIPK2 was highly expressed in the gill, followed by muscle, liver and heart. AbRIPK2 was significantly induced in the spleen and valvular intestine after Streptococcus iniae and Aeromonas hydrophila infection. AbRIPK2 was significantly upregulated after peptidoglycan (PGN) treatment in the splenic leukocytes. This study indicated that AbRIPK2 played a potential role in resisting the pathogenic infection of Siberian sturgeon by responding to bacteria.

Comparison the efficacy and safety of different neoadjuvant regimens for resectable and borderline resectable pancreatic cancer: a systematic review and network meta-analysis - Xujia Li; Jinsheng Huang; Chang Jiang; Ping Chen; Qi Quan; Qi Jiang; Shengping Li; Guifang Guo (European Journal of Clinical Pharmacology, 2022)

Knockdown of lncRNA-ASLNC12002 alleviates epithelial–mesenchymal transition of type II alveolar epithelial cells in sepsis-induced acute respiratory distress syndrome - Kaixuan Feng; Weifeng Huang; Jiawei Shang; Feng Ping; Qin Tan; Wei Wang; Yingchuan Li; Yongmei Cao (Human Cell, 2022)
Patients with sepsis-induced acute respiratory distress syndrome (ARDS) have higher mortality and poor prognosis than pneumonia-induced ARDS. Pulmonary fibrosis is an irreversible accumulation of connective tissue in the interstitium of the lung and closely associated with the epithelial–mesenchymal transition (EMT) of type II alveolar epithelial cells (AECIIs). Therefore, it is undoubtedly worth studying whether the EMT of AECIIs in sepsis-induced ARDS patients is different from that in patients with pneumonia-induced ARDS in the regulatory mechanism. Here, we will report for the first time that an lncRNA-ASLNC12002 is highly expressed in AECIIs of patients with sepsis-induced pneumonia and promotes EMT in AECIIs. The research results showed that the expression of ASLNC12002 in AECIIs derived from patients with sepsis-induced ARDS is significantly higher than that in normal people and pneumonia-induced ARDS patients. Mechanism research showed that ASLNC12002 can cause the inactivation of the anti-EMT pathway NR2F2/miR128-3p/Snail1 by acting as the sponge of miR128-3p. Functional experiments showed that targeted silencing of ASLNC12002 could effectively inhibit EMT progression in AECIIs of patients with sepsis-induced pneumonia by restoring NR2F2/miR128-3p/Snail1 pathway. In a word, our study shows for the first time that the inactivation of NR2F2/miR128-3p/Snail1 pathway caused by the enhanced expression of ASLNC12002 is the direct reason why AECIIs in sepsis-induced ARDS patients are prone to get EMT progress. ASLNC12002 has the potential to become a biological target for the prevention and treatment of pulmonary fibrosis in patients with sepsis-induced ARDS. At the same time, the expectation that ASLNC12002 and its related products may be used as clinical markers for the evaluation of early pulmonary fibrosis in ARDS patients should not be ignored.

Association Between Regular Blood Pressure Monitoring and the Risk of Intracranial Aneurysm Rupture: a Multicenter Retrospective Study with Propensity Score Matching - Ping Zhong; Zhiwen Lu; Tianxiao Li; Qing Lan; Jianmin Liu; Zhanxiang Wang; Sifang Chen; Qinghai Huang (Translational Stroke Research, 2022)

Cryo-EM structures reveal the dynamic transformation of human alpha-2-macroglobulin working as a protease inhibitor - Xiaoxing Huang; Youwang Wang; Cong Yu; Hui Zhang; Qiang Ru; Xinxin Li; Kai Song; Min Zhou; Ping Zhu (Science China Life Sciences, 2022)

Copper Toxicity Differentially Regulates the Seedling Growth, Copper Distribution, and Photosynthetic Performance of Citrus sinensis and Citrus grandis - Xin-yu Li; Mei-lan Lin; Ping-ping Hu; Ning-wei Lai; Zeng-rong Huang; Li-song Chen (Journal of Plant Growth Regulation, 2022)

Association between gestational arsenic exposure and intrauterine growth restriction: the role of folate content - Fei-Xiang Xu; Xu Chen; Heng Zhang; Yi-Jun Fan; Ya-Ping Song; Jin-Wei Lv; Ya-Li Xie; Yichao Huang; Dao-Zhen Chen; Hua Wang; De-Xiang Xu (Environmental Science and Pollution Research, 2022)

Derivation of new resistance principle on flow-induced morphological response of flexible vegetation - Feng-Cong Jia; Wei-Jie Wang; Ling-Hua Liu; Jin-Jin Li; Ai-Ping Huang; Jing Zhang; Yi-Cheng Fu; Yang Yu (Environmental Science and Pollution Research, 2022)

Joint effect of East Asia–Pacific and Scandinavian teleconnections on summer precipitation in Southwest China - Yang Mingxin; Xiao Tiangui; Zhao Ping; Li Yong; Huang Wei; Li Yueqing; Tan Jie (Theoretical and Applied Climatology, 2022)
Based on the summer precipitation data from 328 meteorological stations in Southwest China and the monthly mean reanalysis data from the National Centers for Environmental Prediction/National Center for Atmospheric Research, the relationships of summer precipitation in Southwest China with the East Asia–Pacific (EAP) teleconnection pattern and the Scandinavian (SCA) teleconnection pattern are explored by using correlation analysis and composite analysis. The results show that the two teleconnections are significantly negatively correlated with the summer precipitation in Southwest China in the same period. The EAP teleconnection pattern and the SCA teleconnection pattern can affect the summer precipitation in Southwest China by affecting the atmospheric circulation situation in the middle and high latitudes, the north–south and east–west movement of the WPSH, and the water vapor transport in southwest China. In particular, the EAP and SCA teleconnections jointly affect the summer precipitation in Southwest China, which can be divided into four categories of configurations based on their phases, that is, (I) positive EAP + positive SCA, (II) negative EAP + negative SCA, (III) positive EAP + negative SCA, and (IV) negative EAP + positive SCA. The distribution of summer precipitation in Southwest China varies under different categories of configurations. Category I (II) corresponds to an opposite distribution pattern of precipitation anomalies between the north and south of Southwest China. In the configuration of category I(II), the cold air from high latitudes is weaker (stronger), the WPSH is more north(south) and more west(east) than the climatological mean, and the water vapor mainly comes from the Western Pacific (Bay of Bengal), thus resulting in category I(II), the opposite distribution of precipitation. While for configuration of category III(IV), no similar symmetrical distribution of precipitation anomalies can be found, and no obvious other distribution characteristics as well.

Application of regional citrate anticoagulation in patients at high risk of bleeding during intermittent hemodialysis: a prospective multicenter randomized controlled trial - Xiaoyan Tang; Dezheng Chen; Ling Zhang; Ping Fu; Yanxia Chen; Zhou Xiao; Xiangcheng Xiao; Weisheng Peng; Li Cheng; Yanmin Zhang; Hongbo Li; Kehui Li; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Distribution of ultrafine aerosols and volatile organic compounds from surgical smoke during electrocauterization - Chi-Tsung Chen; Shiang-Fu Huang; Cheng-Jung Li; Jou-Mien Huang; Kai-Ping Chang; Gwo-Hwa Wan (Air Quality, Atmosphere & Health, 2022)

Evaluation and prediction of land use change impacts on ecosystem service values in Nanjing City from 1995 to 2030 - Ping Yu; Shuainan Zhang; Peng Wang; Yingnan Li; Lei Huang (Environmental Science and Pollution Research, 2022)

Genome-Wide Bisulphite Sequencing Uncovered the Contribution of DNA Methylation to Rice Short-Term Drought Memory Formation - Shuyan Kou; Qiongyao Gu; Liu Duan; Gaojing Liu; Pingrong Yuan; Huahui Li; Zhigang Wu; Weihua Liu; Ping Huang; Li Liu (Journal of Plant Growth Regulation, 2022)
Rice is the important crop for more than half of the world population. However, drought can have a devastating impact on rice growth and reduce yield drastically. Understanding the response of rice to drought stress is especially important for crop breeding. Previously we found that rice enhanced its tolerance to drought stresses via stress memory mechanisms. Numerous memory genes were identified to play important roles in the process. DNA methylation was reported to mediate tolerance via regulating gene expression and enhances the survival rate of rice encountering drought stress. However, how DNA methylation involved in stress memory is still not clear. In this study, genome-wide bisulphite sequencing at a single base resolution methylome profiling level was performed and analyzed in rice cultivar under recurrent drought stresses and recovery treatments. We found that rice drought stress memory-related differentially methylated regions (DMRs) showed dynamic and distinct patterns. The drought-memory DMRs may regulate Transposable elements and gene expression to cope with short-term repeated drought stresses. Our findings of drought-memory DMRs can explain mechanisms of rice drought stress memory in a new perspective on global methylome details. Using epigenetic markers to breed drought-resistant rice would become a feasible way in the future research.

Protective effects of Ulva clathrata derived polyphenols against oxidative stress in lipopolysaccharide-induced RAW 264.7 cells via Nrf2/HO-1 pathway - Jingxia Hong; Ping Huang; Bolun Sun; Jie Mi; Jinjie Zhang; Chao Li; Wenge Yang (Journal of Applied Phycology, 2022)

Effect of posaconazole on the concentration of intravenous and oral cyclosporine in patients undergoing hematopoietic stem cell transplantation - Li-E Zhu; Hui-Ping Huang; Yi-Peng Cai; Yan Wang; Bao-Hua Xu; Mao-Bai Liu; Xue-Mei Wu (European Journal of Clinical Pharmacology, 2022)

Complete genome analysis of a novel iflavirus from the spotted lanternfly Lycorma delicatula - Yi-Zhe Wang; Zhuang-Xin Ye; Jian‑Ping Chen; Chuan‑Xi Zhang; Jun‑Min Li; Hai-Jian Huang (Archives of Virology, 2022)

Streptomyces akebiae sp. nov., a novel actinomycete isolated from rhizosphere soil of Akebia trifoliate - Ping Mo; Kaiqin Li; Jinhua Zhou; Fumin Zhou; Yazhi Chen; Xiaojia Lin; Xiaoyu Liu; Kerui Huang; Wansheng Zou; Jian Gao (Antonie van Leeuwenhoek, 2022)

PAH-induced metabolic changes related to inflammation in childhood asthma - Hao Wu; Yuling Bao; Tongtong Yan; Hui Huang; Ping Jiang; Zhan Zhang; Lei Li; Qian Wu (Environmental Science and Pollution Research, 2022)

Phylogeny and species diversity in Hygrophorus section Aurei in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Gabriel Moreno; Yun-Ju Pu; Yu-Guang Fan; Shu-Da Yang; Tie-Zhi Liu; Li-Ping Tang (Mycological Progress, 2022)

Dissecting the role of cell signaling versus CD8+ T cell modulation in propranolol antitumor activity - Wei Li; Jielin Wan; Cuiyu Chen; Chengfang Zhou; Ping Liao; Qian Hu; Jiali Hu; Yang Wang; Yu Zhang; Cong Peng; Yuanfei Huang; Weihua Huang; et al. (Journal of Molecular Medicine, 2022)

Super Stability of Cu-Mn/Y Bimetallic Catalyst for Ozone-assisted Catalytic Oxidation of Toluene - Ke Xia; Jin-Hua Huang; Li-Ping Ye (Water, Air, & Soil Pollution, 2022)

Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2022)

The Role of Post-Translational Modifications on the Structure and Function of Tau Protein - Haiqiong Ye; Yue Han; Ping Li; Zhengding Su; Yongqi Huang (Journal of Molecular Neuroscience, 2022)

Two-stage cultivation of Scenedesmus acuminatus with nitrogen and sulfur for growth and lipid accumulation - Ying Zhang; Hongxiao Shen; Ping Zhong; Zhenzhu Huang; Ning Xu; Aifen Li (Journal of Applied Phycology, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

ML323, a USP1 inhibitor triggers cell cycle arrest, apoptosis and autophagy in esophageal squamous cell carcinoma cells - Yaxin Sun; Beibei Sha; Wenjing Huang; Miaomiao Li; Shan Zhao; Yuan Zhang; Jie Yan; Zheng Li; Jingwen Tang; Peiyan Duan; Jianxiang Shi; Pei Li; et al. (Apoptosis, 2022)

Expanding the clinical spectrum of adult-onset neuronal intranuclear inclusion disease - Yuwen Cao; Jingying Wu; Yunhua Yue; Chao Zhang; Shihua Liu; Ping Zhong; Shige Wang; Xiaojun Huang; Weiping Deng; Jing Pan; Lan Zheng; Qing Liu; et al. (Acta Neurologica Belgica, 2022)

Revising the species diversity of Hygrophorus section Olivaceoumbrini s.l. (Hygrophoraceae, Agaricales) in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Shuai Jiang; Yan-Jia Hao; Man Mu; Li-Ping Tang (Mycological Progress, 2022)

MiR-1260b protects against LPS-induced degenerative changes in nucleus pulposus cells through targeting TCF7L2 - Shijie Chen; Guixia Shi; Jin Zeng; Ping Huang Li; Yi Peng; Zhiyu Ding; Hong Qing Cao; Ruping Zheng; Weiguo Wang (Human Cell, 2022)

Chemical constituents of Viscum coloratum (Kom.) Nakai and their cytotoxic activities - Ying-Ying Chen; Jiang-Ping Hou; Ling Huang; Afsar Khan; Fei-Fei Xing; Xiao-Han Zhang; De-Feng Han; Shi-Li Yan; Gui-Dong Cao; Qi-Yang Jiao; Dejie Liu; Xuwei Zhu; et al. (Natural Product Research, 2022)

Preparation and In Vitro and In Vivo Evaluation of a Testosterone Film Forming Gel for the Treatment of Hypoactive Sexual Desire Disorder in Women - Jia Zeng; Tan-Fang Xie; Ting Huang; Fang Li; Zhi-Ping Wang; Ling-Lin Feng (AAPS PharmSciTech, 2022)

Antifungal sesquiterpenes with post-harvest anthracnose control effect on bananas from the fungus Fusarium lateritium - Junjie Zhu; Ping Xiong; Ziyang Li; Jiazhong Li; Longsheng Lin; Xing Fu; Yuxuan Huang; Yahong Xiong; Chunyuan Li (Natural Product Research, 2022)

New sesquiterpeniod esters form Blumea balsamifera (L.) DC. and their anti-influenza virus activity - Yan Xiong; Ping Yi; Yuhuan Li; Rongmei Gao; Junlei Chen; Zhanxing Hu; Huayong Lou; Caixia Du; Jiayu Zhang; Yu Zhang; Chunmao Yuan; Liejun Huang; et al. (Natural Product Research, 2022)

Activating PIK3CA postzygotic mutations in segmental overgrowth of muscles with bone involvement in the body extremities - Wen Tian; Liying Sun; Qi Zhang; Junhui Zhao; Yang Guo; Wenyao Zhong; Liu Liu; Katia Meirelles; Sha Tang; Jing Zhang; Yingzhao Huang; Yuehan Yin; et al. (Molecular Genetics and Genomics, 2022)

Optimizing Method of Main Caverns in Large Underground Water-Sealed Storage Cavern - Yang An; E-Chuan Yan; Xing-Ming Li; Shao-Ping Huang (Geotechnical and Geological Engineering, 2022)

Association of long-term exposure to ambient air pollution with the number of tuberculosis cases notified: a time-series study in Hong Kong - Man Xu; Ping Hu; Ruoling Chen; Bing Liu; Hongying Chen; Jian Hou; Li ke; Jiao Huang; Hairong Ren; Hui Hu (Environmental Science and Pollution Research, 2022)

Mutation of a prenyltransferase results in accumulation of subglutinols and destruxins and enhanced virulence in the insect pathogen, Metarhizium anisopliae - Chengzhou Li; Wenyou Huang; Tingting Zhou; Qian Zhao; Peiquan Huang; Ping Qi; Song Huang; Shuaishuai Huang; Nemat O. Keyhani; Zhen Huang (Environmental Microbiology, 2022)
Summary The insect pathogenic fungus, Metarhizium anisopliae is a commercialized microbial agent used in biological control efforts targeting a diverse range of agricultural and other insect pests. The second step in the synthesis of a group of M . anisopliae α‐pyrone diterpenoids (termed subglutinols) involves the activity of a prenyltransferase family geranylgeranyl diphosphate synthase (product of the subD / MaGGPPS5 gene). Here, we show that targeted gene disruption of MaGGPPS 5 results in earlier conidial germination and faster greater vegetative growth compared to the wild type (WT) parent and complemented strains. In addition, insect bioassays revealed that the Δ MaGGPPS5 mutant strain displayed significantly increased virulence, with a ~50% decrease in the mean lethal time (LT 50 , from 6 to 3 days) to kill (50% of) target insects, and an ~15–40‐fold decrease in the mean lethal dose (LC 50 ). Metabolite profiling indicated increased accumulation in the Δ MaGGPPS5 mutant of select subglutinols (A, B and C) and destruxins (A, A2, B and B2), the latter a set of fungal secondary metabolites that act as insect toxins, with a concomitant loss of production of subglutinol ‘analogue 45’. These data suggest that the increased virulence phenotype seen for the Δ MaGGPPS5 strain can, at least in part, be attributed to a combination of faster growth and increased insect toxin production, linking the production of two different secondary metabolite pathways, and represent a novel approach for the screening of isolates with enhanced virulence via modulation of terpenoid secondary metabolite biosynthesis.

Four new prenylflavonol glycosides from the leaves of Cyclocarya paliurus - Zi-Jun Ye; Hui-Hui Sun; Zu-Hui Chen; Jian-Ping Wu; Jing Li; Hui Zhu; Lu-Lu Huang; Xi-Wen Chang; Sai-Yu Ou; Wen-Xuan Wang; Xiao-Ai He; Gang-Zhi Zhu; et al. (Natural Product Research, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Numerical Analysis of Single-Particle Motion Using CFD-DEM in Varying-Curvature Elbows - Chao Ning; Yalin Li; Ping Huang; Hongbo Shi; Haichao Sun (Journal of Marine Science and Engineering, 2022)
Centrifugal pumps are the critical components in deep-sea mining. In order to investigate the particle motion in the curved channel of the impeller, three different types of curvature conform to blade profile to simplify the impeller design of pumps. A numerical study is conducted to investigate the flow field in a varying-curvature channel for solid-liquid two-phase flow. The flow of particles within the varying curvature channel is studied by combining the discrete element method (DEM) with computational fluid dynamics (CFD) and a comparison with Particle Image Velocimetry (PIV) test results. The results show that a polyhedral mesh with a small mesh number yields very accurate results, which makes it very suitable for CFD-DEM. Based on this method, the movement of a single particle is compared and analyzed, and the particle-motion law is obtained. The effects of the curvature ratio Cr and area ratio Ar on the motion law for a single particle are studied, and the simulation results are analyzed statistically. The results show that the effect of Cr on both the particle slip velocity and the turbulent kinetic energy only changes its strength, while the distribution law does not change significantly. Compared with the curvature ratio Cr, the area ratio Ar has a greater impact on the particles, and its distribution law becomes clearly different. As the area ratio Ar increases, the arc radius and length of the corresponding particle trajectory decrease.

A new indole alkaloid from the stems of Glycosmis puberula var . craibii - Qi Zhou; Chun-Xiao Jiang; Shou-Yuan Wu; Zi-Ming Chen; Li-Ping Huang (Natural Product Research, 2022)

A community effort to assess and improve computerized interpretation of 12-lead resting electrocardiogram - Zijian Ding; Guijin Wang; Huazhong Yang; Ping Zhang; Dapeng Fu; Zhen Yang; Xinkang Wang; Xia Wang; Zhourui Xia; Chiming Zhang; Wenjie Cai; Binhang Yuan; et al. (Medical & Biological Engineering & Computing, 2022)
Computerized interpretation of electrocardiogram plays an important role in daily cardiovascular healthcare. However, inaccurate interpretations lead to misdiagnoses and delay proper treatments. In this work, we built a high-quality Chinese 12-lead resting electrocardiogram dataset with 15,357 records, and called for a community effort to improve the performances of CIE through the China ECG AI Contest 2019. This dataset covers most types of ECG interpretations, including the normal type, 8 common abnormal types, and the other type which includes both uncommon abnormal and noise signals. Based on the Contest, we systematically assessed and analyzed a set of top-performing methods, most of which are deep neural networks, with both their commonalities and characteristics. This study establishes the benchmarks for computerized interpretation of 12-lead resting electrocardiogram and provides insights for the development of new methods.

Integration of metabolomics and transcriptomics revealed the biosynthetic mechanism of anti-parasitic compounds in Salinivibrio proteolyticus strain YCSC6 - Guangxun Du; Lingyun Qu; Ping Gao; Wenhao Huang; Chenghua Li; Dewen Ding (Journal of Oceanology and Limnology, 2022)

Identification of New Transcription Factors that Can Promote Pluripotent Reprogramming - Ping Huang; Jieying Zhu; Yu Liu; Guihuan Liu; Ran Zhang; Dongwei Li; Duanqing Pei; Ping Zhu (Stem Cell Reviews and Reports, 2021)
Background Four transcription factors, Oct4, Sox2, Klf4, and c-Myc (the Yamanka factors), can reprogram somatic cells to induced pluripotent stem cells (iPSCs). Many studies have provided a number of alternative combinations to the non-Yamanaka factors. However, it is clear that many additional transcription factors that can generate iPSCs remain to be discovered. Methods The chromatin accessibility and transcriptional level of human embryonic stem cells and human urine cells were compared by Assay for Transposase-Accessible Chromatin with high-throughput sequencing (ATAC-seq) and RNA sequencing (RNA-seq) to identify potential reprogramming factors. Selected transcription factors were employed to reprogram urine cells, and the reprogramming efficiency was measured. Urine-derived iPSCs were detected for pluripotency by Immunofluorescence, quantitative polymerase chain reaction, RNA sequencing and teratoma formation test. Finally, we assessed the differentiation potential of the new iPSCs to cardiomyocytes in vitro. Results ATAC-seq and RNA-seq datasets predicted TEAD2, TEAD4 and ZIC3 as potential factors involved in urine cell reprogramming. Transfection of TEAD2, TEAD4 and ZIC3 (in the presence of Yamanaka factors) significantly improved the reprogramming efficiency of urine cells. We confirmed that the newly generated iPSCs possessed pluripotency characteristics similar to normal H1 embryonic stem cells. We also confirmed that the new iPSCs could differentiate to functional cardiomyocytes. Conclusions In conclusion, TEAD2, TEAD4 and ZIC3 can increase the efficiency of reprogramming human urine cells into iPSCs, and provides a new stem cell sources for the clinical application and modeling of cardiovascular disease. Graphical abstract

Formation Process of Silicate-Iron Oxyhydroxide Complex and Its Influence on the Distribution of Heavy Metals in Mining Area - Qun Zhao; Jiangtao He; Xinrui Yan; Chen Li; Jie Li; YingJie Li; Senlin Tian; Jianhong Huang; Ping Ning (Bulletin of Environmental Contamination and Toxicology, 2021)

Stress response mechanisms and description of three novel species Shewanella avicenniae sp. nov., Shewanella sedimentimangrovi sp. nov. and Shewanella yunxiaonensis sp. nov., isolated from mangrove ecosystem - Guo-Hong Liu; Qi Zhang; Manik Prabhu Narsing Rao; Shang Yang; Rong Tang; Huai Shi; Jie-Ping Wang; Guan-Min Huang; Bo Liu; Shun-Gui Zhou; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

Hydrological characteristics and changes in the Nu-Salween River basin revealed with model-based reconstructed data - Fan Yang; Hui Lu; Kun Yang; Guang-wei Huang; Yi-shan Li; Wei Wang; Ping Lu; Fu-qiang Tian; Yu-gang Huang (Journal of Mountain Science, 2021)

Induced production of a new polyketide in Penicillium sp. HS-11 by chemical epigenetic manipulation - You-Min Ying; Ling Li; Hang-Fei Yu; Yi-Lian Xu; Lu Huang; Wei Mao; Cui-Ping Tong; Zhi-Dong Zhang; Zha-Jun Zhan; Yun Zhang (Natural Product Research, 2021)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Characterization of a novel shrimp pathogen, Vibrio brasiliensis , isolated from Pacific white shrimp, Penaeus vannamei - Ge Li; Guosi Xie; Hailiang Wang; Xiaoyuan Wan; Xinshu Li; Chengyin Shi; Ziyan Wang; Miao Gong; Ting Li; Ping Wang; Qingli Zhang; Jie Huang (Journal of Fish Diseases, 2021)
A novel pathogenic strain Vibrio 20190611023 was isolated from the hepatopancreas of moribund cultured Penaeus vannamei suffering from black gill disease. This strain was identified as V . brasiliensis based on the phylogenetic analyses of 16S rDNA gene and five other housekeeping genes (i.e., gapA , ftsZ , mreB , topA and gyrB ). Some biochemical features of this strain were determined with an API 20NE system, and its haemolytic activity was determined using a sheep blood agar plate. The pathogenicity of this isolate 20190611023 was confirmed by the experimental challenge tests and histopathological examinations. P. vannamei were challenged via reverse gavage with different doses of bacterial suspensions. The calculated median lethal dose (LD 50 ) was (3.16 ± 1.78) × 10 5 CFU/g (body weight). Moreover, antibiotic susceptibility tests were performed, the results of which showed that the strain 20190611023 was sensitive to chloramphenicol, compound sulphamethoxazole, ciprofloxacin, doxycycline and oxacillin, but resistant to erythromycin, kanamycin, gentamicin, cefoperazone, ceftriaxone, cefamezin and piperacillin. To our knowledge, this is the first report for demonstrating V . brasiliensis as a shrimp pathogen, which expands the host range of V . brasiliensis infection. The present study highlights that more attention should be paid to this novel pathogen in intensive shrimp aquaculture.

The effects of plant–soil feedback on invasion resistance are soil context dependent - Pengdong Chen; Qiaoqiao Huang; Yanhui Zhuge; Chongwei Li; Ping Zhu; Yuping Hou (Oecologia, 2021)

Hygrophorus russula complex (Hygrophoraceae, Agaricales) in China - Hong-Yan Huang; Wen-Hao Zhang; Ting Huang; Moreno Gabriel; Tie-Zhi Liu; Li-Ping Tang (Mycological Progress, 2021)

A De Novo SEMA6B Variant in a Chinese Patient with Progressive Myoclonic Epilepsy-11 and Review of the Literature - Qian Li; Min Liu; Dan-ping Huang; Tao Li; Jing Huang; Ping Jiang; Wei-hao Ling; Xu-qin Chen (Journal of Molecular Neuroscience, 2021)

Passivation and remediation of Pb and Cr in contaminated soil by sewage sludge biochar tubule - Lin Chen; Qi Ni; Yan Wu; Chuan Fu; Wei Ping; Hongyu Bai; Mengnan Li; Hongcheng Huang; Hanshuang Liu (Environmental Science and Pollution Research, 2021)

Two new selenite reducing bacterial isolates from paddy soil and the potential Se biofortification of paddy rice - Chunlei Huang; Helin Wang; Xinyan Shi; Yanhong Wang; Ping Li; Hanqin Yin; Yixian Shao (Ecotoxicology, 2021)

Methane Concentration in the Heartwood of Living Trees and Estimated Methane Emission on Stems in Upland Forests - Zhi-Ping Wang; Huan-Long Li; Hong-Hui Wu; Shi-Jie Han; Jian-Hui Huang; Xi-Mei Zhang; Xing-Guo Han (Ecosystems, 2021)

The sub-inhibitory concentration of cinnamaldehyde resists Aeromonas hydrophila pathogenicity via inhibition of W-pili production - Ping Ouyang; Jiehao Chen; Lizi Yin; Yi Geng; Defang Chen; Kaiyu Wang; Weiming Lai; Hongrui Guo; Jing Fang; Zhengli Chen; Li Tang; Chao Huang; et al. (Aquaculture International, 2021)

Mechanism of bone marrow mesenchymal stem cells secreting miR-26a exosomes affecting high glucose-induced skin fibroblasts function by regulating TLR4/NF-κB signaling - Qian Li; Ping Huang; Weimin Chen; Jiarui Bi (Inflammation Research, 2021)

Long non-coding RNA TPT1-AS1 sensitizes breast cancer cell to paclitaxel and inhibits cell proliferation by miR-3156-5p/caspase 2 axis - Yuan Huang; Yabing Zheng; Xiying Shao; Lei Shi; Guangliang Li; Ping Huang (Human Cell, 2021)

First report of Bacillus altitudinis causing seed rot of pomegranate in China - Qili Liu; Dongxiao Li; Haiyan Hu; Qianqian Huang; Yongheng Zhang; Feng Zhou; Puwen Song; Yuanyuan Guan; Ruifang Bu; Ping Hu; Jianjun Hao; Chengwei Li (Australasian Plant Pathology, 2021)

Wnt5a up-regulates Periostin through CaMKII pathway to influence periodontal tissue destruction in early periodontitis - Liu Qian; Guo Shujuan; Huang Ping; Liu Li; Shi Weiwei; Wu Yafei; Tian Weidong (Journal of Molecular Histology, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Comparison of in Vascular Bioreactors and In Vivo Models of Degradation and Cellular Response of Mg–Zn–Mn Stents - Ningling Zhou; Ping Li; Hua Qiu; Jin Wang; Nan Huang; Ansha Zhao; Juan Wang (Annals of Biomedical Engineering, 2021)

Synthesis and antitumor evaluation of (aryl)methyl-amine derivatives of dehydroabietic acid-based B ring-fused-thiazole as potential PI3K/AKT/mTOR signaling pathway inhibitors - Nai-Yuan Chen; Yu-Lan Xie; Guo-Dong Lu; Fang Ye; Xin-Yu Li; Yu-Wen Huang; Ming-Li Huang; Tie-Yu Chen; Cui-Ping Li (Molecular Diversity, 2021)

Human β-Defensin 118 Attenuates Escherichia coli K88–Induced Inflammation and Intestinal Injury in Mice - Qian Lin; Qingqing Fu; Xiang Li; Yuheng Luo; Junqiu Luo; Daiwen Chen; Xiangbing Mao; Bing Yu; Ping Zheng; Zhiqing Huang; Jie Yu; Hui Yan; et al. (Probiotics and Antimicrobial Proteins, 2021)

New cytotoxic biflavones from Selaginella doederleinii - Li-Fei Liu; Hui-Hui Sun; Jian-Bing Tan; Qi Huang; Fei Cheng; Kang-Ping Xu; Zhen-Xing Zou; Gui-Shan Tan (Natural Product Research, 2021)

Quality analysis and improvement of polarimetric synthetic aperture radar (SAR) images from the GaoFen-3 satellite using the Amazon rainforest as an example - Guangde Sun; Zhen Li; Lei Huang; Quan Chen; Ping Zhang (International Journal of Remote Sensing, 2021)

Groundwater sources, flow patterns, and hydrochemistry of the Central Yinchuan Plain, China - Ying Li; Ping Wu; Xiao-Qin Huang; Bo Zhang; Zhao-Xiang Xu; Yang Li; Jie Li; Lu-Chen Wang; Yu-Fang Sun; Xu-Chen Meng; Cheng-Wen Wang; Zi-Zhao Cai (Hydrogeology Journal, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

The reproductive regulation of LPXRFa and its receptor in the hypothalamo-pituitary-gonadal axis of the spotted scat (Scatophagus argus) - Yi Zhai; Si-Ping Deng; Jian-Ye Liu; Dong-Neng Jiang; Yang Huang; Chun-Hua Zhu; Guang-Li Li; Ming-Hui Li (Fish Physiology and Biochemistry, 2021)

N2O Emissions Mitigation in Acidic Soil Following Biochar Application Under Different Moisture Regimes - Muhammad Aamer; Muhammad Shaaban; Muhammad Umair Hassan; Liu Ying; Tang Haiying; Ma Qiaoying; Hassan Munir; Adnan Rasheed; Li Xinmei; Li Ping; Huang Guoqin (Journal of Soil Science and Plant Nutrition, 2020)

Valine acts as a nutritional signal in brain to activate TORC1 and attenuate postprandial ammonia-N excretion in Chinese perch (Siniperca chuatsi) - Jie Wang; Xu-Fang Liang; Shan He; Yan-Peng Zhang; Jiao Li; Kang Huang; Lin-Jie Shi; Ping Ren (Fish Physiology and Biochemistry, 2020)

Effects of Extracellular Matrix Softening on Vascular Smooth Muscle Cell Dysfunction - Yihui Shao; Guoqi Li; Shan Huang; Zhenfeng Li; Bokang Qiao; Duanduan Chen; Yulin Li; Huirong Liu; Jie Du; Ping Li (Cardiovascular Toxicology, 2020)

Possible effects of leaf tissue characteristics of oilseed rape Brassica napus on probing and feeding behaviors of cabbage aphids Brevicoryne brassicae - Zhong-Ping Hao; Hai-Xia Zhan; Ling-Ling Gao; Fang Huang; Li-Ni Zhu; Shu-Min Hou (Arthropod-Plant Interactions, 2020)

Insights into the microbiota of larval and postlarval Pacific white shrimp (Penaeus vannamei) along early developmental stages: a case in pond level - Hailiang Wang; Jie Huang; Ping Wang; Ting Li (Molecular Genetics and Genomics, 2020)

Effects of Increased Carbon Supply on the Growth, Nitrogen Metabolism and Photosynthesis of Vallisneria natans Grown at Different Temperatures - Heng Jiang; Bing Huang; Zhan Qian; Yue Xu; Xiaohong Liao; Ping Song; Xichun Li (Wetlands, 2020)

Gnaq Protects PC12 Cells from Oxidative Damage by Activation of Nrf2 and Inhibition of NF-kB - Xin Sun; Guo-Ping Li; Pu Huang; Lu-Gang Wei; Jia-Zhi Guo; Li-Juan Ao; Di Lu; Shao-Chun Chen (NeuroMolecular Medicine, 2020)

Chopper Sugarcane Combine Harvester with Middle-Mounted Primary Extractor - Tao Wu; Xiao-Ling Liang; Qing-Ting Liu; Zeng-Xue Zhang; Hai Xu; Ji-Bai Huang; Jin-Xin Li; Xiao-Ping Zou (Sugar Tech, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

High throughput solid-phase screening of bacteria with cyclic amino alcohol deamination activity for enantioselective synthesis of chiral cyclic β-amino alcohols - Ya-Wen Chang; Jian-Dong Zhang; Xiao-Xiao Yang; Jing Li; Li-Li Gao; Shuang-Ping Huang; Xing-Mei Guo; Cao-Feng Zhang; Hong-Hong Chang; Jian-He Xu (Biotechnology Letters, 2020)

Biological Aerosol Particles in Polluted Regions - Wei Hu; Zihan Wang; Shu Huang; Lujie Ren; Siyao Yue; Ping Li; Qiaorong Xie; Wanyu Zhao; Lianfang Wei; Hong Ren; Libin Wu; Junjun Deng; et al. (Current Pollution Reports, 2020)

Pure qP-wave least-squares reverse time migration in vertically transverse isotropic media and its application to field data - Jian-Ping Huang; Xin-Ru Mu; Zhen-Chun Li; Qing-Yang Li; Shuang-Qi Yuan; Yun-Dong Guo (Applied Geophysics, 2020)

Predicting postmortem interval based on microbial community sequences and machine learning algorithms - Ruina Liu; Yuexi Gu; Mingwang Shen; Huan Li; Kai Zhang; Qi Wang; Xin Wei; Haohui Zhang; Di Wu; Kai Yu; Wumin Cai; Gongji Wang; et al. (Environmental Microbiology, 2020)
Summary Microbes play an essential role in the decomposition process but were poorly understood in their succession and behaviour. Previous researches have shown that microbes show predictable behaviour that starts at death and changes during the decomposition process. Research of such behaviour enhances the understanding of decomposition and benefits estimating the postmortem interval (PMI) in forensic investigations, which is critical but faces multiple challenges. In this study, we combined microbial community characterization, microbiome sequencing from different organs (i.e. brain, heart and cecum) and machine learning algorithms [random forest (RF), support vector machine (SVM) and artificial neural network (ANN)] to investigate microbial succession pattern during corpse decomposition and estimate PMI in a mouse corpse system. Microbial communities exhibited significant differences between the death point and advanced decay stages. Enterococcus faecalis , Anaerosalibacter bizertensis , Lactobacillus reuteri , and so forth were identified as the most informative species in the decomposition process. Furthermore, the ANN model combined with the postmortem microbial data set from the cecum, which was the best combination among all candidates, yielded a mean absolute error of 1.5 ± 0.8 h within 24‐h decomposition and 14.5 ± 4.4 h within 15‐day decomposition. This integrated model can serve as a reliable and accurate technology in PMI estimation.

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

NK cell reconstitution following unmanipulated HLA-mismatched/haploidentical transplantation compared with matched sibling transplantation - Li-Juan Hu; Xun-Hong Cao; Xing-Xing Yu; Xue-Fei Liu; Xiao-Su Zhao; Ying-Jun Chang; Xiao-Hui Zhang; Lan-Ping Xu; Yu Wang; Kai-Yan Liu; Xiao-Jun Huang; Xiang-Yu Zhao (Science China Life Sciences, 2020)

Outbreak of carp edema virus disease in cultured ornamental koi in a lower temperature in China - Ping Ouyang; Yaojia Zhou; Ruixue Yang; Zhuangzhi Yang; Kaiyu Wang; Yi Geng; Weiming Lai; Xiaoli Huang; Defang Chen; Jing Fang; Zhengli Chen; Li Tang; et al. (Aquaculture International, 2020)

Sparse constrained encoding multi-source full waveform inversion method based on K-SVD dictionary learning - Yun-dong Guo; Jian-Ping Huang; Cui Chao; Zhen-Chun Li; Qing-Yang Li; Wei Wei (Applied Geophysics, 2020)

Influence of Super-Critical CO2 on the Strength and Fracture Behavior of Brine-Saturated Sandstone Specimens - Yan-Hua Huang; Sheng-Qi Yang; Wen-Ping Li; Matthew R. Hall (Rock Mechanics and Rock Engineering, 2020)

Soil types differentiated their responses of aggregate stability to hydrological stresses at the riparian zones of the Three Gorges Reservoir - Yiguo Ran; Shengjun Wu; Kai Zhu; Wenjuan Li; Zhimei Liu; Ping Huang (Journal of Soils and Sediments, 2020)

Front Cover - Wei Wang; Jie Wang; Francis M. P. Choi; Ping Ding; Xiao‐xu Li; Guo‐dong Han; Meng‐wen Ding; Minquan Guo; Xiong‐wei Huang; Wei‐xiang Duan; Zhi‐yuan Cheng; Zhi‐yuan Chen; et al. (Global Ecology and Biogeography, 2020)

Global warming and artificial shorelines reshape seashore biogeography - Wei Wang; Jie Wang; Francis M. P. Choi; Ping Ding; Xiao‐xu Li; Guo‐dong Han; Meng‐wen Ding; Minquan Guo; Xiong‐wei Huang; Wei‐xiang Duan; Zhi‐yuan Cheng; Zhi‐yuan Chen; et al. (Global Ecology and Biogeography, 2020)
Aim Rapid anthropogenic warming coupled with changes in land use is altering the distributions of species, with consequences for ecosystem functioning and services. It is crucial to evaluate species range shifts based on understanding of the interaction of temperature with non‐climatic factors such as habitat availability and dispersal potential. Here, we aim to investigate roles of environmental temperature, habitat availability and population connectivity on the distributions of hard‐shore intertidal animals. We further examine potential roles of extensive artificial seawall construction in enabling poleward expansion of species in China, thus reshaping coastal biogeography. Location Chinese coast. Time period 2013–2017. Major taxa studied Intertidal invertebrates. Methods We took an integrative approach encompassing distributional ecology, thermal physiology, molecular genetics, heat budget modelling and larval dispersal to elucidate how interacting multiple drivers, including temperature, habitat availability and larval dispersal, determine distributions of hard‐shore invertebrates, focusing on what sets their range edges at a boundary between biogeographic provinces. Results Our results untangle the complex interactions of global climate change with the impacts of regional scale coastal development. Temperature, larval transport and habitat availability are the major proximate factors controlling the range limits of coastal marine species. The artificial shorelines provide suitable habitats for hard‐shore species on the Yangtze River Delta, and minimum temperature in winter is an important factor setting the new northern range limit of these hard‐shore species along the Chinese coast. Main conclusions In the face of global warming and global sprawl of marine hard infrastructure, species distributions, community structures and biogeographic patterns are experiencing dramatic changes. The combined influence of multiple human stressors including climate change and artificial shorelines can be evaluated by using a multidisciplinary framework, including ecological distribution, physiological sensitivity of species to these stressors, and the role of dispersal in maintaining population connectivity.

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

In vitro antifungal activity of dimethyl trisulfide against Colletotrichum gloeosporioides from mango - Lihua Tang; Jianyou Mo; Tangxun Guo; Suiping Huang; Qili Li; Ping Ning; Tom Hsiang (World Journal of Microbiology and Biotechnology, 2020)

Comparative transcriptome analysis of male and female gonads reveals sex-biased genes in spotted scat (Scatophagus argus) - Fei-Xiang He; Dong-Neng Jiang; Yuan-Qing Huang; Umar Farouk Mustapha; Wei Yang; Xue-Fan Cui; Chang-Xu Tian; Hua-Pu Chen; Hong-Juan Shi; Si-Ping Deng; Guang-Li Li; Chun-Hua Zhu (Fish Physiology and Biochemistry, 2019)

Petrogenesis and Geodynamic Implications of the Carboniferous Granitoids in the Dananhu Belt, Eastern Tianshan Orogenic Belt - Long Du; Chao Yuan; Xu-Ping Li; Yunying Zhang; Zongying Huang; Xiaoping Long (Journal of Earth Science, 2019)

First report of sheath rot caused by Fusarium proliferatum on Pisang Awak Banana (Musa ABB) in China - Sui-Ping Huang; Ji-Guang Wei; Tang-Xun Guo; Qi-Li Li; Li-Hua Tang; Jian-You Mo; Ji-Feng Wei; Xiao-Bing Yang (Journal of Plant Pathology, 2019)

Three new labdane-type diterpenoids from Callicarpa macrophylla Vahl. - Zhen-Hui Wang; Huan-Jun Xu; Yang-Yang Zhai; Lan-Ping Yang; Qiang Li; Mei Huang; Xing-Ying Chen; Wen-Kui Zhang; Yue-Li Meng; Qing-Ling Zhang; Chao Niu; Yan-Ru Zhang (Natural Product Research, 2019)

Pharmacokinetic study of imrecoxib in patients with renal insufficiency - Qi Pei; Jin-lian Xie; Jie Huang; Wen-yu Liu; Xiao-yan Yang; Yan Wang; Wei Li; Hong-yi Tan; Hao Zhang; Guo-Ping Yang (European Journal of Clinical Pharmacology, 2019)

Excess copper effects on growth, uptake of water and nutrients, carbohydrates, and PSII photochemistry revealed by OJIP transients in Citrus seedlings - Qiang Li; Huan-Huan Chen; Yi-Ping Qi; Xin Ye; Lin-Tong Yang; Zeng-Rong Huang; Li-Song Chen (Environmental Science and Pollution Research, 2019)

Application of gradient structure tensor method in CBM fracture identification and sweet spot prediction - Chengqiang Zhao; Yubang Zhou; Yong Li; Ping Zhao; Lingling Huang (Arabian Journal of Geosciences, 2019)

Comparative effects of some extraction solvents on the antimicrobial activity of Eucalyptus camaldulensis leaf, bud, capsule and seed crude extracts - Alyaa Nasr; Xinxin Zhou; Shi-Ping Huang; Yuan Wang; Xiaoning Li; Guo-Ping Zhu (Natural Product Research, 2019)

Inhibition effect of natural flavonoids on red tide alga Phaeocystis globosa and its quantitative structure-activity relationship - Xi Xiao; Chao Li; Haomin Huang; Ying Ping Lee (Environmental Science and Pollution Research, 2019)

Temporal profile of illicit drug consumption in Guangzhou, China monitored by wastewater-based epidemiology - Xiaohan Zhang; Riheng Huang; Ping Li; Yuan Ren; Jianfa Gao; Jochen F. Mueller; Phong K Thai (Environmental Science and Pollution Research, 2019)

Association between sheath blight resistance and chitinase activity in transgenic rice plants expressing McCHIT1 from bitter melon - Changwei Zhang; Manyu Huang; Xianchun Sang; Ping Li; Yinghua Ling; Fangming Zhao; Dan Du; Yunfeng Li; Zhenglin Yang; Guanghua He (Transgenic Research, 2019)

Suppression of Fusarium wilt of banana by combining acid soil ameliorant with biofertilizer made from Bacillus velezensis H-6 - Jianfeng Huang; Yuwan Pang; Fabao Zhang; Qiaoyi Huang; Mu Zhang; Shuanhu Tang; Hongting Fu; Ping Li (European Journal of Plant Pathology, 2019)

Molecular properties and immunomodulatory activities of a water-soluble heteropolysaccharide isolated from Plantago asiatica L. leaves - Jun-Yi Yin; Xin-Yue Huang; Li Wang; Jian-Qi Guo; Ming-Yong Xie; Jian-Yong Wu; Shao-Ping Nie (Natural Product Research, 2019)

The role of MAPK signaling pathway in formation of EMT in oral squamous carcinoma cells induced by TNF-α - Xiao-Wei Zhao; Jing-Ping Zhou; Yu-Lan Bi; Jia-Ying Wang; Rui Yu; Chao Deng; Wei-Kang Wang; Xian-Zhen Li; Rui Huang; Jili Zhang; De-Tao Tao (Molecular Biology Reports, 2019)

Potential effects of exploiting the Yunfu pyrite mine (southern China) on soil: evidence from analyzing trace elements in surface soil - Zhi-hua Tang; Ting-ping Ouyang; Ming-kun Li; Ning-sheng Huang; Yao-qiu Kuang; Qiao Hu; Zhao-yu Zhu (Environmental Monitoring and Assessment, 2019)

Characterization of Cucurbita maxima Fruit Metabolomic Profiling and Transcriptome to Reveal Fruit Quality and Ripening Gene Expression Patterns - He-Xun Huang; Ting Yu; Jun-Xing Li; Shu-Ping Qu; Man-Man Wang; Ting-Quan Wu; Yu-Juan Zhong (Journal of Plant Biology, 2019)

Influence of permeation effect on the microfabric of the slip zone soils: A case study from the Huangtupo landslide - Fa-sheng Miao; Yi-ping Wu; Yuan-hua Xie; Lin-wei Li; Jie Li; Lei Huang (Journal of Mountain Science, 2019)

Suppression of miR-93-5p inhibits high-risk HPV-positive cervical cancer progression via targeting of BTG3 - Jie Li; Zhao-Ping Chu; Hua Han; Yuan Zhang; Fei Tian; Jun-Qin Zhang; Xiang-Hua Huang (Human Cell, 2019)

Habitat selection of wintering cranes (Gruidae) in typical lake wetland in the lower reaches of the Yangtze River, China - Cheng Wang; Bin Dong; Ming Zhu; Hui Huang; Yu-huang Cui; Xiang Gao; Li-ping Liu (Environmental Science and Pollution Research, 2019)

Correction to: Magnesium deficiency affects secondary lignification of the vascular system in Citrus sinensis seedlings - Jing-Hao Huang; Jing Xu; Xin Ye; Tu-Yan Luo; Li-Hua Ren; Guo-Cheng Fan; Yi-Ping Qi; Qiang Li; Rhuanito S. Ferrarezi; Li-Song Chen (Trees, 2019)

Magnesium deficiency affects secondary lignification of the vascular system in Citrus sinensis seedlings - Jing-Hao Huang; Jing Xu; Xin Ye; Tu-Yan Luo; Li-Hua Ren; Guo-Cheng Fan; Yi-Ping Qi; Qiang Li; Rhuanito S. Ferrarezi; Li-Song Chen (Trees, 2019)

Synthesis and biological evaluation of novel SIPI-7623 derivatives as farnesoid X receptor (FXR) antagonists - Si-Yun Nian; Guo-Ping Wang; Zheng-Li Jiang; Ying Xiao; Mo-Han Huang; Yi-Huan Zhou; Xiang-Duan Tan (Molecular Diversity, 2019)

Oral administration of Lactobacillus rhamnosus GG to newborn piglets augments gut barrier function in pre-weaning piglets - Yang Wang; Li Gong; Yan-ping Wu; Zhi-wen Cui; Yong-qiang Wang; Yi Huang; Xiao-ping Zhang; Wei-fen Li (Journal of Zhejiang University-SCIENCE B, 2019)

Daedaleanols A and B, two new sesquiterpenes from cultures of the basidiomycete Daedalea incana - Ying Huang; Shuai-Bing Zhang; He-Ping Chen; Zhen-Zhu Zhao; Zheng-Hui Li; Tao Feng; Ji-Kai Liu (Natural Product Research, 2019)

Trivalent Chromium Supplementation Ameliorates Oleic Acid-Induced Hepatic Steatosis in Mice - Song Wang; Jian Wang; Yajing Liu; Hui Li; Qiao Wang; Zhiwei Huang; Wenbin Liu; Ping Shi (Biological Trace Element Research, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

RETRACTED ARTICLE: Fluoxetine is Neuroprotective in Early Brain Injury via its Anti-inflammatory and Anti-apoptotic Effects in a Rat Experimental Subarachnoid Hemorrhage Model - Hui-Min Hu; Bin Li; Xiao-Dong Wang; Yun-Shan Guo; Hua Hui; Hai-Ping Zhang; Biao Wang; Da-Geng Huang; Ding-Jun Hao (Neuroscience Bulletin, 2018)

Decreased takeoff performance of aircraft due to climate change - Yuntao Zhou; Nan Zhang; Chao Li; Yong Liu; Ping Huang (Climatic Change, 2018)

Augmenter of liver regeneration promotes mitochondrial biogenesis in renal ischemia–reperfusion injury - Li-li Huang; Rui-ting Long; Gui-ping Jiang; Xiao Jiang; Hang Sun; Hui Guo; Xiao-hui Liao (Apoptosis, 2018)

Molecular characterization of two novel sub-sublineages of pigeon paramyxovirus type 1 in China - Tianchao Wei; Qiaomu Deng; Haiqiong Li; Chao Pan; Guosheng Zhai; Yadong Yuan; Ercai Cheng; Yuanqin Zhang; Meilan Mo; Teng Huang; Ping Wei (Archives of Virology, 2018)

Solvent effects on quantitative analysis of brominated flame retardants with Soxhlet extraction - Yin Zhong; Dan Li; Xifen Zhu; Weilin Huang; Ping’an Peng (Environmental Geochemistry and Health, 2018)

Pigmented microbial eukaryotes fuel the deep sea carbon pool in the tropical Western Pacific Ocean - Dapeng Xu; Ping Sun; Yizhe Zhang; Ran Li; Bangqin Huang; Nianzhi Jiao; Alan Warren; Lei Wang (Environmental Microbiology, 2018)
Summary Phototrophic microbial eukaryotes dominate primary production over large oceanic regions. Due to their small sizes and slow sinking rates, it is assumed they contribute relatively little to the downward export of organic carbon via the biological pump. Therefore, the community structure of phototrophic cells in the deep ocean has long been overlooked and remains largely unknown. In this study, we used an integrative approach, including epifluorescence microscopy, sequencing of 18S rRNA and photosystem‐II psbA gene transcripts, to investigate phototrophic microbial eukaryotes in samples collected from the tropical Western Pacific Ocean. It was found that: (i) pigmented nano‐sized eukaryotes (PNEs) are ubiquitous in the deep Western Pacific Ocean down to 5000 m depth; (ii) the PNE community is dominated by cells 2–5 μm in size; (iii) their abundance is significant, averaging 4 ± 1 (± s.e.) cells ml −1 in waters below 1000 m which is comparable to that of heterotrophic nanoflagellates; (iv) the active pigmented microbial eukaryotes in the deep waters are highly diverse and dominated by Haptophyta followed by Chlorophyta and Bacillariophyta; (v) PNEs in deep waters were likely transported from surface ocean by various fast‐sinking mechanisms, thus contributing to the biological pump and fuelling the deep‐sea communities by supplying fresh organic carbon.

Optimisation of extraction conditions for total saponins from Cynanchum wallichii using response surface methodology and its anti-tumour effects - Kun-jun Mao; Ping Huang; Li- Zhang; Hai-sheng Yu; Xing-zhuo Zhou; Xi-yong Ye (Natural Product Research, 2018)

Lappaconitine, a C18-diterpenoid alkaloid, exhibits antihypersensitivity in chronic pain through stimulation of spinal dynorphin A expression - Ming-Li Sun; Jun-Ping Ao; Yi-Rui Wang; Qian Huang; Teng-Fei Li; Xin-Yan Li; Yong-Xiang Wang (Psychopharmacology, 2018)

Forward modeling of ocean-bottom cable data and wave-mode separation in fluid–solid elastic media with irregular seabed - Ying-Ming Qu; Jun-Zhi Sun; Zhen-Chun Li; Jian-Ping Huang; Hai-Peng Li; Wen-Zhi Sun (Applied Geophysics, 2018)

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

BDNF/TrkB Pathway Mediates the Antidepressant-Like Role of H2S in CUMS-Exposed Rats by Inhibition of Hippocampal ER Stress - Le Wei; Li-Yuan Kan; Hai-Ying Zeng; Yi-Yun Tang; Hong-Lin Huang; Ming Xie; Wei Zou; Chun-Yan Wang; Ping Zhang; Xiao-Qing Tang (NeuroMolecular Medicine, 2018)

Early warning model for slope debris flow initiation - Ming-li Li; Yuan-jun Jiang; Tao Yang; Qiang-bing Huang; Jian-ping Qiao; Zong-ji Yang (Journal of Mountain Science, 2018)

Optimized staggered-grid finite-difference operators using window functions - Ying-Jun Ren; Jian-Ping Huang; Peng Yong; Meng-Li Liu; Chao Cui; Ming-Wei Yang (Applied Geophysics, 2018)

Geochemistry of uranium in Chinese coals and the emission inventory of coal-fired power plants in China - Jian Chen; Ping Chen; Duoxi Yao; Wenhui Huang; Shuheng Tang; Kejian Wang; Wenzhong Liu; Youbiao Hu; Qingguang Li; Ruwei Wang (International Geology Review, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Submarine landslide identified in DLW3102 core of the northern continental slope, South China Sea - Yuanqin Xu; Lejun Liu; Hang Zhou; Baoqi Huang; Ping Li; Xiudong Ma; Feiyin Dong (Journal of Ocean University of China, 2018)

Diversity and evolution analysis of glycoprotein GP85 from avian leukosis virus subgroup J isolates from chickens of different genetic backgrounds during 1989-2016: Coexistence of five extremely different clusters - Peikun Wang; Lulu Lin; Haijuan Li; Yongli Yang; Teng Huang; Ping Wei (Archives of Virology, 2018)

Xylastriasan A, a new cytochalasan from the fungus Xylaria striata - Chuan-Wen Lei; Zhi-Qin Yang; Yan-Ping Zeng; Yun Zhou; Yi Huang; Xin-Sheng He; Guo-You Li; Xiao-Hong Yuan (Natural Product Research, 2018)

Correction to: Molecular characterization of a genetically divergent equine pegivirus strain identified in China - Gang Lu; Cheng Fu; Ji Huang; Haibin Xu; Peixin Wu; Xiaokun Ping; Shoujun Li (Archives of Virology, 2018)

Molecular characterization of a genetically divergent equine pegivirus strain identified in China - Gang Lu; Cheng Fu; Ji Huang; Haibin Xu; Peixin Wu; Xiaokun Ping; Shoujun Li (Archives of Virology, 2018)

Full-length genome sequence analysis of four subgroup J avian leukosis virus strains isolated from chickens with clinical hemangioma - Lulu Lin; Peikun Wang; Yongli Yang; Haijuan Li; Teng Huang; Ping Wei (Virus Genes, 2017)

Rapid response to changing environments during biological invasions: DNA methylation perspectives - Xuena Huang; Shiguo Li; Ping Ni; Yangchun Gao; Bei Jiang; Zunchun Zhou; Aibin Zhan (Molecular Ecology, 2017)
Dissecting complex interactions between species and their environments has long been a research hot spot in the fields of ecology and evolutionary biology. The well‐recognized Darwinian evolution has well‐explained long‐term adaptation scenarios; however, “rapid” processes of biological responses to environmental changes remain largely unexplored, particularly molecular mechanisms such as DNA methylation that have recently been proposed to play crucial roles in rapid environmental adaptation. Invasive species, which have capacities to successfully survive rapidly changing environments during biological invasions, provide great opportunities to study molecular mechanisms of rapid environmental adaptation. Here, we used the methylation‐sensitive amplified polymorphism (MSAP) technique in an invasive model ascidian, Ciona savignyi , to investigate how species interact with rapidly changing environments at the whole‐genome level. We detected quite rapid DNA methylation response: significant changes of DNA methylation frequency and epigenetic differentiation between treatment and control groups occurred only after 1 hr of high‐temperature exposure or after 3 hr of low‐salinity challenge. In addition, we detected time‐dependent hemimethylation changes and increased intragroup epigenetic divergence induced by environmental stresses. Interestingly, we found evidence of DNA methylation resilience, as most stress‐induced DNA methylation variation maintained shortly (~48 hr) and quickly returned back to the control levels. Our findings clearly showed that invasive species could rapidly respond to acute environmental changes through DNA methylation modifications, and rapid environmental changes left significant epigenetic signatures at the whole‐genome level. All these results provide fundamental background to deeply investigate the contribution of DNA methylation mechanisms to rapid contemporary environmental adaptation.

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Genome-wide analysis of GDSL-type esterases/lipases in Arabidopsis - Chia-Ping Lai; Li-Min Huang; Long-Fang O. Chen; Ming-Tsair Chan; Jei-Fu Shaw (Plant Molecular Biology, 2017)

Reflection full-waveform inversion using a modified phase misfit function - Chao Cui; Jian-Ping Huang; Zhen-Chun Li; Wen-Yuan Liao; Zhe Guan (Applied Geophysics, 2017)

Carboniferous porphyry Cu (-Au) mineralization of the West Junggar region, NW China: the Shiwu example - ChangHao Li; Ping Shen; HongDi Pan; Wei Huang; Chong Cao (International Geology Review, 2017)

TGF-β1-miR-200a-PTEN induces epithelial–mesenchymal transition and fibrosis of pancreatic stellate cells - Min Xu; Guoying Wang; Hailang Zhou; Jing Cai; Ping Li; Meng Zhou; Ying Lu; Xiaomeng Jiang; Hongmei Huang; Youli Zhang; Aihua Gong (Molecular and Cellular Biochemistry, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Detecting the Changes of Water Qualities and Fluorescent DOM in a Constructed Rapid Infiltration System - Ping-ping Gao; Yun-zhen Li; Xu-jing Guo; Tao Huang; Dong-hai Yuan; Xian-dong Tan (Wetlands, 2017)

Spontaneous Remission of Subcutaneous Scedosporiosis Caused by Scedosporium dehoogii in a Psoriatic Patient - Fang-Gu Li; Yan-Ping Yang; Wei Li; Ping Sheng; Wen Li; Wen-Ming Huang; Yi-Ming Fan (Mycopathologia, 2017)

Improving the resolution of seismic traces based on the secondary time–frequency spectrum - De-Ying Wang; Jian-Ping Huang; Xue Kong; Zhen-Chun Li; Jiao Wang (Applied Geophysics, 2017)

Carboniferous Alaskan-type complex along the Sino–Mongolian boundary, southern margin of the Central Asian Orogenic Belt - Yuruo Shi; Linlin Li; Alfred Kröner; Jing Ding; Wei Zhang; Zengbao Huang; Ping Jian (Acta Geochimica, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Oxidation of indometacin by ferrate (VI): kinetics, degradation pathways, and toxicity assessment - Junlei Huang; Yahui Wang; Guoguang Liu; Ping Chen; Fengliang Wang; Jingshuai Ma; Fuhua Li; Haijin Liu; Wenying Lv (Environmental Science and Pollution Research, 2017)

Preconditioned prestack plane-wave least squares reverse time migration with singular spectrum constraint - Chuang Li; Jian-Ping Huang; Zhen-Chun Li; Rong-Rong Wang (Applied Geophysics, 2017)

Assessment of different route choice on commuters’ exposure to air pollution in Taipei, Taiwan - Hsien-Chih Li; Pei-Te Chiueh; Shi-Ping Liu; Yu-Yang Huang (Environmental Science and Pollution Research, 2017)

Analgesic Effects of Danggui-Shaoyao-San on Various “Phenotypes” of Nociception and Inflammation in a Formalin Pain Model - Jun-Bin Yin; Ke-Cheng Zhou; Huang-Hui Wu; Wei Hu; Tan Ding; Ting Zhang; Li-Ying Wang; Jun-Ping Kou; Alan David Kaye; Wen Wang (Molecular Neurobiology, 2016)

Risk assessment and vertical distribution of thallium in paddy soils and uptake in rice plants irrigated with acid mine drainage - Xuexia Huang; Ning Li; Qihang Wu; Jianyou Long; Dinggui Luo; Ping Zhang; Yan Yao; Xiaowu Huang; Dongmei Li; Yayin Lu; Jianfeng Liang (Environmental Science and Pollution Research, 2016)

Development of chloroplast genomic resources for Akebia quinata (Lardizabalaceae) - Bin Li; Yanda Li; Qifei Cai; Furong Lin; Ping Huang; Yongqi Zheng (Conservation Genetics Resources, 2016)

The destruction box is involved in the degradation of the NTE family proteins by the proteasome - Fei-Fei Huang; Ping-An Chang; Lan-Xi Sun; Wen-Zhen Qin; Li-Ping Han; Rui Chen (Molecular Biology Reports, 2016)

Changes in subcellular distribution and antioxidant compounds involved in Pb accumulation and detoxification in Neyraudia reynaudiana - Chuifan Zhou; Meiying Huang; Ying Li; Jiewen Luo; Li ping Cai (Environmental Science and Pollution Research, 2016)

Surgical treatment of hepato-pancreato-biliary disease in China: the Tongji experience - Binhao Zhang; Wei Dong; Hongping Luo; Xuanru Zhu; Lin Chen; Changhai Li; Peng Zhu; Wei Zhang; Shuai Xiang; Wanguang Zhang; Zhiyong Huang; Xiao-Ping Chen (Science China Life Sciences, 2016)

Characterization and expression analysis of cDNAs encoding abscisic acid 8′-hydroxylase during mulberry fruit maturation and under stress conditions - Yuxiang Cai; Panpan Zhu; Changying Liu; Aichun Zhao; Jian Yu; Chuanhong Wang; Zhengang Li; Ping Huang; Maode Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2016)

Prismatic and full-waveform joint inversion - Ying-Ming Qu; Zhen-Chun Li; Jian-Ping Huang; Jin-Li Li (Applied Geophysics, 2016)

Kerion and Tinea Corporis Caused by Rabbit-Derived Trichophyton interdigitale in Three Siblings and One Consulting Doctor Using β-Tubulin Gene to Identify the Pathogen - Yan-Ping Yang; Ping Sheng; Zhong Liu; Wen Li; Jie-Di Wang; Wen-Ming Huang; Yi-Ming Fan (Mycopathologia, 2016)

A new flavane acid from the fruits of Illicium verum - Liang-Deng Wu; Chun-Lan Xiong; Zi-Zhan Chen; Rui-Jie He; Yan-Jun Zhang; Yan Huang; Sheng-Ping Deng; Rui-Yun Yang; Jun Li (Natural Product Research, 2016)

STAT3 signal that mediates the neural plasticity is involved in willed-movement training in focal ischemic rats - Qing-ping Tang; Qin Shen; Li-xiang Wu; Xiang-ling Feng; Hui Liu; Bei Wu; Xiao-song Huang; Gai-qing Wang; Zhong-hao Li; Zun-jing Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Cholangiocarcinoma-derived exosomes inhibit the antitumor activity of cytokine-induced killer cells by down-regulating the secretion of tumor necrosis factor-α and perforin - Jiong-huang Chen; Jian-yang Xiang; Guo-ping Ding; Li-ping Cao (Journal of Zhejiang University-SCIENCE B, 2016)

Identification of loci contributing to maize drought tolerance in a genome-wide association study - Nan Wang; Zhen-ping Wang; Xiao-ling Liang; Jian-feng Weng; Xiang-ling Lv; De-gui Zhang; Jie Yang; Hong-jun Yong; Ming-shun Li; Feng-hai Li; Li-yan Jiang; Shi-huang Zhang; et al. (Euphytica, 2016)

Empirical calibration of the clinopyroxene–garnet magnesium isotope geothermometer and implications - Wang-Ye Li; Fang-Zhen Teng; Yilin Xiao; Hai-Ou Gu; Xiang-Ping Zha; Jian Huang (Contributions to Mineralogy and Petrology, 2016)

Changes and characteristics of dissolved organic matter in a constructed wetland system using fluorescence spectroscopy - Yuan Yao; Yun-zhen Li; Xu-jing Guo; Tao Huang; Ping-ping Gao; Ying-pei Zhang; Feng Yuan (Environmental Science and Pollution Research, 2016)

A new phenolic compound with antioxidant activity from the branches and leaves of Pyrus pashia - Zhen-Jie Li; Xi Zheng; Chun-Ping Wan; Le Cai; Ying Li; Lin Huang; Zhong-Tao Ding (Natural Product Research, 2016)

Calpain-Dependent ErbB4 Cleavage Is Involved in Brain Ischemia-Induced Neuronal Death - Ying-mei Lu; Yin-ping Gao; Rong-rong Tao; Mei-hua Liao; Ji-yun Huang; Gang Wu; Feng Han; Xiao-ming Li (Molecular Neurobiology, 2016)

Retraction Note: RGD peptide-pegylated PLLA nanoparticles containing epirubicin hydrochloride exhibit receptor-dependent tumor trafficking in vitro and in vivo - Ping Huang; Jun Wu; Ximeng Li; Xiaozheng Liu; Yinghuan Li; Guohui Cui (Pharmaceutical Research, 2016)

The pseudorabies virus DNA polymerase processivity factor UL42 exists as a monomer in vitro and in vivo - Yi-Ping Wang; Li-Ping Huang; Wen-Juan Du; Yan-Wu Wei; De-Li Xia; Hong-Li Wu; Li Feng; Chang-Ming Liu (Archives of Virology, 2016)

Risk Assessment for Ecological Planning of Arid Inland River Basins Under Hydrological and Management Uncertainties - Jinjin Gu; Mo Li; Ping Guo; Guohe Huang (Water Resources Management, 2016)

Impacts of snow disaster on meat production and adaptation: an empirical analysis in the yellow river source region - Yi-ping Fang; Chen Zhao; Yong-jian Ding; Da-he Qin; Jia-li Huang (Sustainability Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The application study on the multi-scales integrated prediction method to fractured reservoir description - Shuang-Quan Chen; Lian-Bo Zeng; Ping Huang; Shao-Han Sun; Wan-Lu Zhang; Xiang-Yang Li (Applied Geophysics, 2016)

Global patterns and climate drivers of water‐use efficiency in terrestrial ecosystems deduced from satellite‐based datasets and carbon cycle models - Yan Sun; Shilong Piao; Mengtian Huang; Philippe Ciais; Zhenzhong Zeng; Lei Cheng; Xiran Li; Xinping Zhang; Jiafu Mao; Shushi Peng; Benjamin Poulter; Xiaoying Shi; et al. (Global Ecology and Biogeography, 2016)
Aim To investigate how ecosystem water‐use efficiency ( WUE ) varies spatially under different climate conditions, and how spatial variations in WUE differ from those of transpiration‐based water‐use efficiency ( WUE t ) and transpiration‐based inherent water‐use efficiency ( IWUE t ). Location Global terrestrial ecosystems. Methods We investigated spatial patterns of WUE using two datasets of gross primary productivity ( GPP ) and evapotranspiration ( ET ) and four biosphere model estimates of GPP and ET . Spatial relationships between WUE and climate variables were further explored through regression analyses. Results Global WUE estimated by two satellite‐based datasets is 1.9 ± 0.1 and 1.8 ± 0.6 g C m −2 mm −1 lower than the simulations from four process‐based models (2.0 ± 0.3 g C m −2 mm −1 ) but comparable within the uncertainty of both approaches. In both satellite‐based datasets and process models, precipitation is more strongly associated with spatial gradients of WUE for temperate and tropical regions, but temperature dominates north of 50° N . WUE also increases with increasing solar radiation at high latitudes. The values of WUE from datasets and process‐based models are systematically higher in wet regions (with higher GPP ) than in dry regions. WUE t shows a lower precipitation sensitivity than WUE , which is contrary to leaf‐ and plant‐level observations. IWUE t , the product of WUE t and water vapour deficit, is found to be rather conservative with spatially increasing precipitation, in agreement with leaf‐ and plant‐level measurements. Main conclusions WUE , WUE t and IWUE t produce different spatial relationships with climate variables. In dry ecosystems, water losses from evaporation from bare soil, uncorrelated with productivity, tend to make WUE lower than in wetter regions. Yet canopy conductance is intrinsically efficient in those ecosystems and maintains a higher IWUE t . This suggests that the responses of each component flux of evapotranspiration should be analysed separately when investigating regional gradients in WUE , its temporal variability and its trends.

Canonical and non-canonical Wnt signaling control the regeneration of amputated rodent vibrissae follicles - Yan-Ping Yuan; Keng Huang; Yan-Min Xu; Xian-Cai Chen; Hai-Hong Li; Bo-Zhi Cai; Yang Liu; Huan Zhang; Yu Li; Chang-Min Lin (Journal of Molecular Histology, 2016)

Different Responses of an Invasive Clonal Plant Wedelia trilobata and its Native Congener to Gibberellin: Implications for Biological Invasion - Zhi-Cong Dai; Wei Fu; Shan-Shan Qi; De-Li Zhai; Si-Chong Chen; Ling-Yun Wan; Ping Huang; Dao-Lin Du (Journal of Chemical Ecology, 2016)

Fatal pneumonia cases caused by human adenovirus 55 in immunocompetent adults - Shu-Yan Zhang; Yan-Ping Luo; Dou-Dou Huang; Hang Fan; Qing-Bin Lu; Ying Wo; Gang Chen; Xiao-Ai Zhang; Yan Li; Yi-Gang Tong; Wu-Chun Cao; Wei Liu (Infectious Diseases, 2016)

Neuroprotective Effects of β-Asarone Against 6-Hydroxy Dopamine-Induced Parkinsonism via JNK/Bcl-2/Beclin-1 Pathway - Sheng Zhang; Xue-Hong Gui; Li-Ping Huang; Min-Zhen Deng; Ruo-Ming Fang; Xue-Hong Ke; Yu-Ping He; Ling Li; Yong-Qi Fang (Molecular Neurobiology, 2016)

Effects of sialidase NEU1 siRNA on proliferation, apoptosis, and invasion in human ovarian cancer - Li-rong Ren; Li-ping Zhang; Shu-ying Huang; Yuan-fang Zhu; Wen-juan Li; Shan-yu Fang; Li Shen; Yan-ling Gao (Molecular and Cellular Biochemistry, 2016)

Therapeutic Retrobulbar Inhibition of STAT3 Protects Ischemic Retina Ganglion Cells - Mansin Wong; Ying Li; Shang Li; Shaodan Zhang; Weiyi Li; Pei Zhang; Chaoran Chen; Colin J. Barnstable; Samuel S. Zhang; Chun Zhang; Ping Huang (Molecular Neurobiology, 2015)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

Up-regulation of SPOCK1 induces epithelial–mesenchymal transition and promotes migration and invasion in esophageal squamous cell carcinoma - Xiaopeng Song; Ping Han; Jingmei Liu; Yunwu Wang; Dongxiao Li; Jiayi He; Jin Gong; Mengke Li; Wei Tu; Wei Yan; Mei Liu; Huanjun Huang; et al. (Journal of Molecular Histology, 2015)

Soil stability characteristics of mulberry lands at hydro-fluctuation belt in the Three Gorges Reservoir area, China - Ping Jiang; Dongmei Shi; Xueqin Hu; Xianzhi Huang; Yexin Li; Tianlei Guo (Environmental Monitoring and Assessment, 2015)

Bacterial growth efficiency in a partly eutrophicated bay of South China Sea: Implication for anthropogenic impacts and potential hypoxia events - Xing-Yu Song; Hua-Xue Liu; Yu Zhong; Ye-Hui Tan; Geng Qin; Kai-Zhi Li; Ping-Ping Shen; Liang-Min Huang; You-Shao Wang (Ecotoxicology, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Prestack forward modeling of tight reservoirs based on the Xu–White model - Chao Zhu; Qing-Xin Guo; Qing-Shun Gong; Zhan-Guo Liu; Sen-Ming Li; Ge-Ping Huang (Applied Geophysics, 2015)

Isolation of a new flavanone from Daidai fruit and hypolipidemic activity of total flavonoids extracts - Ling-Jun Zeng; Dan Chen; Qing-De Huang; Qun Huang; Yun-Fang Lian; Wei-Wei Cai; Hua-Ping Zeng; Yi-Li Lin (Natural Product Research, 2015)

GRY79 encoding a putative metallo-β-lactamase-trihelix chimera is involved in chloroplast development at early seedling stage of rice - Chunmei Wan; Chunmei Li; Xiaozhi Ma; Yang Wang; Changhui Sun; Rui Huang; Ping Zhong; Zhiyan Gao; Dan Chen; Zhengjun Xu; Jianqing Zhu; Xiaoling Gao; et al. (Plant Cell Reports, 2015)

Cutaneous Chromoblastomycosis Caused by Veronaea botryosa in a Patient with Pemphigus Vulgaris and Review of Published Reports - Cheng-Yao Zhu; Yan-Ping Yang; Ping Sheng; Wen Li; Wen-Ming Huang; Yi-Ming Fan (Mycopathologia, 2015)

TGF-β1 and TIMP-4 regulate atrial fibrosis in atrial fibrillation secondary to rheumatic heart disease - Yu Sun; Zi-Yang Huang; Zhen-Hua Wang; Cui-Ping Li; Xian-Liang Meng; Yun-Jiao Zhang; Feng Su; Nan Ma (Molecular and Cellular Biochemistry, 2015)

Screening for simple sequence repeat markers in Puccinia striiformis tritici based on genomic sequence - Gang-ming Zhan; Fu-ping Wang; Huai-yong Luo; Shu-chang Jiang; Wen-ming Zheng; Li-li Huang; Zhen-sheng Kang (Journal of Zhejiang University-SCIENCE B, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

RETRACTED ARTICLE: RGD Peptide-Pegylated PLLA Nanoparticles Containing Epirubicin Hydrochloride Exhibit Receptor-Dependent Tumor Trafficking In Vitro and In Vivo - Ping Huang; Jun Wu; Ximeng Li; Xiaozheng Liu; Yinghuan Li; Guohui Cui (Pharmaceutical Research, 2015)

Elevated Serum Homocysteine (Hcy) Levels May Contribute to the Pathogenesis of Cerebral Infarction - Hong-Juan Fu; Li-Bo Zhao; Ju-Jun Xue; Zhi-Xuan Wu; Yue-Ping Huang; Wei Liu; Zhan Gao (Journal of Molecular Neuroscience, 2015)

Expression of Wnt/β-catenin signaling, stem-cell markers and proliferating cell markers in rat whisker hair follicles - Chang-min Lin; Yan-ping Yuan; Xian-cai Chen; Hai-hong Li; Bo-zhi Cai; Yang Liu; Huan Zhang; Yu Li; Keng Huang (Journal of Molecular Histology, 2015)

Characterization of 26 deletion CNVs reveals the frequent occurrence of micro-mutations within the breakpoint-flanking regions and frequent repair of double-strand breaks by templated insertions derived from remote genomic regions - Ye Wang; Peiqiang Su; Bin Hu; Wenjuan Zhu; Qibin Li; Ping Yuan; Jiangchao Li; Xinyuan Guan; Fucheng Li; Xiangyi Jing; Ru Li; Yongling Zhang; et al. (Human Genetics, 2015)

Simulation of stable water isotopic composition in the atmosphere using an isotopic Atmospheric Water Balance Model - Xin‐Ping Zhang; Hua‐De Guan; Xin‐Zhu Zhang; Hua‐Wu Wu; Guang Li; Yi‐Min Huang (International Journal of Climatology, 2015)
In this article, we present a simplified isotopic Atmospheric Water Balance Model ( iAWBM ), to simulate spatial distribution and temporal variations of δ 18 O in atmospheric vapour and in precipitation, and the correlations of δ 18 O in precipitation with precipitation amount and with temperature. This method overcomes deficiencies of the Global Network of Isotopes in Precipitation ( GNIP ) due to its limitation in space and time resolution and those of the isotope‐enabled General Circulation Models ( iGCM s) due to its complexity. The simulated results reproduce well the latitude effect, continent effect and seasonality of δ 18 O in global precipitation. The simulation suggests that the precipitation amount effect occurs mainly in the low‐mid latitude oceans and monsoon areas, and the simulated temperature effect occurs mainly in the mid‐high latitude continents. However, the simulation results also indicate some temperature effect in some low‐latitude areas where the precipitation amount effect is strong. The modelled precipitation isotopic composition is compared to 3‐year observations in Changsha, China (2010–2012). The simulations reproduce the observed seasonal variations of δ 18 O in precipitation. The basic characteristics that stable isotopes in precipitation are depleted during the rainy season and enriched during the dry season, and the observed amount effect is well simulated under daily time scale. The simulated weighted average δ 18 O (−6.58‰) in precipitation during the prevailing winter monsoon season (October–March) is almost the same as the observed δ 18 O in the same period (−6.56‰), but the simulated δ 18 O (−9.58‰) during the prevailing summer monsoon season (April–September) is lower than the observed δ 18 O (−7.66‰). The simulation result also shows temporal variations of vapour isotopic composition in the atmosphere, and the proportional contributions from horizontal vapour exchange, precipitation and evaporation.

The ctnG gene encodes carbonic anhydrase involved in mycotoxin citrinin biosynthesis from Monascus aurantiacus - Yan-Ping Li; Xiao Tang; Wei Wu; Yang Xu; Zhi-Bing Huang; Qing-Hua He (Food Additives & Contaminants: Part A, 2015)

Impact of LPS-Induced Cardiomyoblast Cell Apoptosis Inhibited by Earthworm Extracts - Ping-Chun Li; Yun-Chen Tien; Cecilia Hsuan Day; Peiying Pai; Wei-Wen Kuo; Tung-Sheng Chen; Chia-Hua Kuo; Chang-Hai Tsai; Da-Tong Ju; Chih-Yang Huang (Cardiovascular Toxicology, 2015)

Photodegradation of Ibuprofen Under UV–Vis Irradiation: Mechanism and Toxicity of Photolysis Products - Fu Hua Li; Kun Yao; Wen Ying Lv; Guo Guang Liu; Ping Chen; Hao Ping Huang; Ya Pu Kang (Bulletin of Environmental Contamination and Toxicology, 2015)

Phylogenetic and recombination analysis of rice black-streaked dwarf virus segment 9 in China - Yu Zhou; Jian-Feng Weng; Yan-Ping Chen; Chang-Lin Liu; Xiao-Hua Han; Zhuan-Fang Hao; Ming-Shun Li; Hong-Jun Yong; De-Gui Zhang; Shi-Huang Zhang; Xin-Hai Li (Archives of Virology, 2015)

Liver Stiffness Measurement, Better than APRI, Fibroindex, Fib-4, and NBI Gastroscopy, Predicts Portal Hypertension in Patients with Cirrhosis - Wei Zhang; Liqiong Wang; Lei Wang; Gang Li; Aoshuang Huang; Ping Yin; Zhenhua Yang; Changquan Ling; Lingtai Wang (Cell Biochemistry and Biophysics, 2015)

Brittleness index and seismic rock physics model for anisotropic tight-oil sandstone reservoirs - Xin-Rui Huang; Jian-Ping Huang; Zhen-Chun Li; Qin-Yong Yang; Qi-Xing Sun; Wei Cui (Applied Geophysics, 2015)

Variable-coordinate forward modeling of irregular surface based on dual-variable grid - Jian-Ping Huang; Ying-Ming Qu; Qing-Yang Li; Zhen-Chun Li; Guo-Lei Li; Chang-Cheng Bu; Hou-Hua Teng (Applied Geophysics, 2015)

Influence of PTGS1, PTGFR, and MRP4 genetic variants on intraocular pressure response to latanoprost in Chinese primary open-angle glaucoma patients - Li-chen Gao; Di Wang; Fang-qun Liu; Zheng-yu Huang; Hong-guang Huang; Gui-hua Wang; Xi Chen; Qun-zhi Shi; Li Hong; Li-ping Wu; Jie Tang (European Journal of Clinical Pharmacology, 2015)

β1-Adrenoceptor Autoantibodies Affect Action Potential Duration and Delayed Rectifier Potassium Currents in Guinea Pigs - Yuhui Zhao; Haixia Huang; Yunhui Du; Xiao Li; Tingting Lv; Suli Zhang; Hua Wei; Jianyu Shang; Ping Liu; Huirong Liu (Cardiovascular Toxicology, 2015)

Different secondary metabolic responses to MeJA treatment in shikonin-proficient and shikonin-deficient cell lines from Arnebia euchroma (Royle) Johnst - Sheng Wang; Lan Ping Guo; Teng Xie; Jian Yang; Jin Fu Tang; Xuan Li; Xiao Wang; Lu Qi Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Unsupervised change detection based on robust chi-squared transform for bitemporal remotely sensed images - Aiye Shi; Du Q. Huynh; Feng Chen Huang; Shao Hong Shen; Wen Ping Lu; Zhen Li Ma (International Journal of Remote Sensing, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

The rescuable function and mechanism of resveratrol on As2O3-induced hERG K+ channel deficiency - Xin Zhao; Kai-ping Zhang; Ting Huang; Cai-Chuan Yan; Li-Rong Liu; Qi-Lei Zhu; Feng-Feng Guo; Chen Liu; Bao-Xin Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Erratum to: Identification of a novel mutation in a Chinese family with Nance-Horan syndrome by whole exome sequencing - Nan Hong; Yan-hua Chen; Chen Xie; Bai-sheng Xu; Hui Huang; Xin Li; Yue-qing Yang; Ying-ping Huang; Jian-lian Deng; Ming Qi; Yang-shun Gu (Journal of Zhejiang University-SCIENCE B, 2014)

Effect of two-linked mutations of the FMO3 gene on itopride metabolism in Chinese healthy volunteers - Li-Ping Zhou; Zhi-Rong Tan; Hao Chen; Dong Guo; Yao Chen; Wei-Hua Huang; Lian-Sheng Wang; Guo-Gang Zhang (European Journal of Clinical Pharmacology, 2014)

Local adaptation and phenotypic plasticity both occurred in Wedelia trilobata invasion across a tropical island - Chun-Can Si; Zhi-Cong Dai; Ying Lin; Shan-Shan Qi; Ping Huang; Shi-Li Miao; Dao-Lin Du (Biological Invasions, 2014)

The phosphorylation of an actin depolymerizing factor by a calcium-dependent protein kinase regulates cotton fiber elongation - Quan-Sheng Huang; Xun-Ji Chen; Jian-Ping Li; Xiao-Yan Hao; Guo Chen; Zumuremu; Lin Shao (Acta Physiologiae Plantarum, 2014)

Indian Ocean variability in the CMIP5 multi-model ensemble: the zonal dipole mode - Lin Liu; Shang-Ping Xie; Xiao-Tong Zheng; Tim Li; Yan Du; Gang Huang; Wei-Dong Yu (Climate Dynamics, 2014)

Mutations in Ralstonia solanacearum loci involved in lipopolysaccharide biogenesis, phospholipid trafficking and peptidoglycan recycling render bacteriophage infection - Yu-Hau Hong; Chi Huang; Kuan-Chung Wang; Tai-Hsiang Chu; Chien-Hui Li; Yu-Ju Chu; Chiu-Ping Cheng (Archives of Microbiology, 2014)

Comparative genetic mapping and genomic region collinearity analysis of the powdery mildew resistance gene Pm41 - Zhenzhong Wang; Yu Cui; Yongxing Chen; Deyun Zhang; Yong Liang; Dong Zhang; Qiuhong Wu; Jingzhong Xie; Shuhong Ouyang; Delin Li; Yinlian Huang; Ping Lu; et al. (Theoretical and Applied Genetics, 2014)

Identification of a novel mutation in a Chinese family with Nance-Horan syndrome by whole exome sequencing - Nan Hong; Yan-hua Chen; Chen Xie; Bai-sheng Xu; Hui Huang; Xin Li; Yue-qing Yang; Ying-ping Huang; Jian-lian Deng; Ming Qi; Yang-shun Gu (Journal of Zhejiang University-SCIENCE B, 2014)

Urinary metabolites of di(2-ethylhexyl) phthalate relation to sperm motility, reactive oxygen species generation, and apoptosis in polyvinyl chloride workers - Li-Ping Huang; Ching-Chang Lee; Jer-Pei Fan; Po-Hsiu Kuo; Tung-Sheng Shih; Ping-Chi Hsu (International Archives of Occupational and Environmental Health, 2014)

Advances in preimplantation genetic diagnosis/screening - LiYing Yan; Yuan Wei; Jin Huang; XiaoHui Zhu; XiaoDan Shi; Xi Xia; Jie Yan; CuiLing Lu; Ying Lian; Rong Li; Ping Liu; Jie Qiao (Science China Life Sciences, 2014)

Different mechanism of LPS-induced calcium increase in human lung epithelial cell and microvascular endothelial cell: a cell culture study in a model for ARDS - Kejing Zhang; Ping Wang; Shuaishuai Huang; Xue Wang; Taohong Li; Yuhong Jin; Michael Hehir; Chiyi Xu (Molecular Biology Reports, 2014)

siRNA Combinations Mediate Greater Suppression of Hepatitis B virus Replication in Mice - Guiqiu Li; Lu Fu; Jinghong Jiang; Yuzhuo Ping; Yanjun Huang; Yongchen Wang (Cell Biochemistry and Biophysics, 2014)

Profiles, sources, and transport of polycyclic aromatic hydrocarbons in soils affected by electronic waste recycling in Longtang, south China - De-Yin Huang; Chuan-Ping Liu; Fang-Bai Li; Tong-Xu Liu; Cheng-Shuai Liu; Liang Tao; Yan Wang (Environmental Monitoring and Assessment, 2014)

Bayesian uncertainty analysis in hydrological modeling associated with watershed subdivision level: a case study of SLURP model applied to the Xiangxi River watershed, China - Jing-Cheng Han; Guo-He Huang; Hua Zhang; Zhong Li; Yong-Ping Li (Stochastic Environmental Research and Risk Assessment, 2014)

Stripe rust resistance and genes in Chinese wheat cultivars and breeding lines - Qing-Dong Zeng; De-Jun Han; Qi-Lin Wang; Feng-Ping Yuan; Jian-Hui Wu; Li Zhang; Xiao-Jie Wang; Li-Li Huang; Xian-Ming Chen; Zhen-Sheng Kang (Euphytica, 2014)
Stripe rust, caused by Puccinia striiformis f. sp. tritici ( Pst ), is one of the most important diseases on wheat in China. To assess resistance in wheat cultivars and breeding lines in China, 330 leading cultivars and 164 advanced breeding lines were evaluated with stripe rust. In the greenhouse tests, seedlings of the entries were inoculated separately with several Pst pathotypes. In the field tests, the entries were evaluated for stripe rust resistance in Yangling, Shaanxi Province artificially inoculated and in Tianshui, Gansu Province under natural infection of Pst . The oversummering/wintering and spring epidemic zones of resistance genes were postulated using molecular markers for Yr5 , Yr9 , Yr10 , Yr15 , Yr17 , Yr18 , and Yr26 , in combination with resistance spectra. Out of the 494 wheat entries, 16 (3.24 %) entries had all-stage resistance (ASR) in all race tests, 99 (20.04 %) had adult-plant resistance (APR), 28 (5.67 %) were considered to have slow-rusting (SR), and 351 (71.05 %) were susceptible to one or more races in both seedling and adult-plant stages. Advanced breeding lines had a higher percentage (37.2 %) of resistant entries (The sum of ASR, APR and SR) than leading cultivars (24.85 %). Among the epidemic regions, southern Gansu had a higher percentage of resistant entries than any other regions. Based on stripe rust reactions and molecular markers, two cultivars were found to possibly have Yr5 while no entries have Yr10 or Yr15 . Resistance genes Yr9 , Yr17 , Yr18 , and Yr26 were found in 134 (29.4 %), 45 (9.1 %), 10 (2 %), and 15 (3 %) entries, respectively.

miRNAs expression profile in bast of ramie elongation phase and cell wall thickening and end wall dissolving phase - Jun Wang; Jing-shu Huang; Xin-yan Hao; Yan-ping Feng; Ya-Jun Cai; Li-qin Sun (Molecular Biology Reports, 2014)

Growth differentiation factor 9 of Megalobrama amblycephala: molecular characterization and expression analysis during the development of early embryos and growing ovaries - Chun Xiao Huang; Xin Lan Wei; Nan Chen; Jie Zhang; Li Ping Chen; Wei Min Wang; Jun Yan Li; Huan Ling Wang (Fish Physiology and Biochemistry, 2014)

Coal-burning endemic fluorosis is associated with reduced activity in antioxidative enzymes and Cu/Zn-SOD gene expression - Qi Wang; Kang-ping Cui; Yuan-yuan Xu; Yan-ling Gao; Jing Zhao; Da-sheng Li; Xiao-lei Li; Hou-jin Huang (Environmental Geochemistry and Health, 2014)

Effects of watershed subdivision level on semi-distributed hydrological simulations: case study of the SLURP model applied to the Xiangxi River watershed, China - Jing-Cheng Han; Guo-He Huang; Hua Zhang; Zhong Li; Yong-Ping Li (Hydrological Sciences Journal, 2014)

Cell-penetrating fusion peptides OD1 and OD2 interact with Bcr–Abl and influence the growth and apoptosis of K562 cells - Hai-xia Wang; Heng Xiao; Liang Zhong; Kun Tao; Ya-juan Li; Shi-feng Huang; Jian-ping Wen; Wen-li Feng (Molecular and Cellular Biochemistry, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Morin Inhibits Sortase A and Subsequent Biofilm Formation in Streptococcus mutans - Ping Huang; Ping Hu; Su Yun Zhou; Qian Li; Wei Min Chen (Current Microbiology, 2014)

Comparative Study of Different Latent Infections of Herpes Simplex Virus Type I in a Murine Model - Wen Huang; Ping Zhao; Xiao Chen; Ping Li; Gaonian Zhao; Mingming Xu; Xiuying Chen; Peng Xie (Cell Biochemistry and Biophysics, 2014)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Genetic variability and evolution of rice stripe virus - Ling-zhe Huang; Li-xia Rao; Xue-ping Zhou; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2013)

Antiarrhythmic effects and ionic mechanisms of allicin on myocardial injury of diabetic rats induced by streptozotocin - Wei Huang; Ye Wang; Yong-Gang Cao; Han-Ping Qi; Lei Li; Bing Bai; Yang Liu; Hong-Li Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Up-regulation of Slc39A2(Zip2) mRNA in peripheral blood mononuclear cells from patients with pulmonary tuberculosis - Yan-ting Tao; Qing Huang; Ya-li Jiang; Xiao-lei Wang; Ping Sun; Yuanyuan Tian; Hai-liang Wu; Min Zhang; Si-bo Meng; Yu-shu Wang; Qing Sun; Lian-ying Zhang (Molecular Biology Reports, 2013)

RNA interference mediated pten knock-down inhibit the formation of polycystic ovary - Jie-Xiu Ouyang; Tao Luo; Hui-Yun Sun; Jian Huang; Dan-Feng Tang; Lei Wu; Yue-Hui Zheng; Li-Ping Zheng (Molecular and Cellular Biochemistry, 2013)

Continuous evolution of avian infectious bronchitis virus resulting in different variants co-circulating in southern China - Meng Li; Mei-Lan Mo; Bai-Cheng Huang; Wen-Sheng Fan; Zheng-Ji Wei; Tian-Chao Wei; Kang-Ran Li; Ping Wei (Archives of Virology, 2013)

Polycyclic aromatic hydrocarbons in soils from Urumqi, China: distribution, source contributions, and potential health risks - Min Chen; Ping Huang; Li Chen (Environmental Monitoring and Assessment, 2013)

A consensus envelope protein domain III can induce neutralizing antibody responses against serotype 2 of dengue virus in non-human primates - Hsin-Wei Chen; Shih-Jen Liu; Yi-Shiuan Li; Hsueh-Hung Liu; Jy-Ping Tsai; Chen-Yi Chiang; Mei-Yu Chen; Chyi-Sing Hwang; Chin-Cheng Huang; Hui-Mei Hu; Han-Hsuan Chung; Sze-Hsien Wu; et al. (Archives of Virology, 2013)

Erratum to: Synergistic effect and mechanism of vitamin A and vitamin D on inducing apoptosis of prostate cancer cells - Jianjun Sha; Jiahua Pan; Ping Ping; Hanqing Xuan; Dong Li; Juanjie Bo; Dongming Liu; Yiran Huang (Molecular Biology Reports, 2013)

Occurrence, distribution, and sources of six phenolic endocrine disrupting chemicals in the 22 river estuaries around Dianchi Lake in China - Bin Wang; Bin Huang; Wei Jin; Shimin Zhao; Farong Li; Ping Hu; Xuejun Pan (Environmental Science and Pollution Research, 2013)

Arbuscular mycorrhizal symbiosis and active ingredients of medicinal plants: current research status and prospectives - Yan Zeng; Lan-Ping Guo; Bao-Dong Chen; Zhi-Peng Hao; Ji-Yong Wang; Lu-Qi Huang; Guang Yang; Xiu-Ming Cui; Li Yang; Zhao-Xiang Wu; Mei-Lan Chen; Yan Zhang (Mycorrhiza, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Synergistic effect and mechanism of vitamin A and vitamin D on inducing apoptosis of prostate cancer cells - Jianjun Sha; Jiahua Pan; Ping Ping; Hanqing Xuan; Dong Li; Juanjie Bo; Dongming Liu; Yiran Huang (Molecular Biology Reports, 2013)

Adjuvant PIKA protects hepatoma cells from dengue virus infection by promoting a TBK-1-dependent innate immune response - Ping Zhang; Siyu Wu; Lietao Li; Zhaoduan Liang; Yuye Li; Lianqiang Feng; Xi Huang (Archives of Virology, 2013)

Increasing phosphorus limitation along three successional forests in southern China - Wenjuan Huang; Juxiu Liu; Ying Ping Wang; Guoyi Zhou; Tianfeng Han; Yin Li (Plant and Soil, 2013)

Sugar starvation- and GA-inducible calcium-dependent protein kinase 1 feedback regulates GA biosynthesis and activates a 14-3-3 protein to confer drought tolerance in rice seedlings - Shin-Lon Ho; Li-Fen Huang; Chung-An Lu; Siou-Luan He; Chun-Chin Wang; Sheng-Ping Yu; Jychian Chen; Su-May Yu (Plant Molecular Biology, 2013)

The active alkaloids of Gelsemium elegans Benth. are potent anxiolytics - Ming Liu; Hui-Hui Huang; Jian Yang; Yan-Ping Su; Hong-Wei Lin; Li-Qing Lin; Wei-Jian Liao; Chang-Xi Yu (Psychopharmacology, 2013)

Involvement of large conductance Ca2+-activated K+ channel in laminar shear stress-induced inhibition of vascular smooth muscle cell proliferation - Xiaoling Jia; Jingyun Yang; Wei Song; Ping Li; Xia Wang; Changdong Guan; Liu Yang; Yan Huang; Xianghui Gong; Meili Liu; Lisha Zheng; Yubo Fan (Pflügers Archiv - European Journal of Physiology, 2013)

Wnt/β-catenin signaling induces the aging of mesenchymal stem cells through promoting the ROS production - Da-yong Zhang; Yu Pan; Chong Zhang; Bing-xi Yan; Shan-shan Yu; Dong-ling Wu; Meng-meng Shi; Kai Shi; Xin-xiao Cai; Shuang-shuang Zhou; Jun-bo Wang; Jian-ping Pan; et al. (Molecular and Cellular Biochemistry, 2013)

STAT1 activation by venous malformations mutant Tie2-R849W antagonizes VEGF-A-mediated angiogenic response partly via reduced bFGF production - Yi-Hsien Huang; Ming-Ping Wu; Shin-Chen Pan; Wu-Chou Su; Yi-Wen Chen; Li-Wha Wu (Angiogenesis, 2013)

Regulatory long non-coding RNA and its functions - Yong Huang; Ning Liu; Jian Ping Wang; Yu Qin Wang; Xue Li Yu; Zhan Bin Wang; Xiang Chao Cheng; Quan Zou (Journal of Physiology and Biochemistry, 2012)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

Genome characterization of a novel porcine bocavirus - Wan-zhu Yang; Jie-mei Yu; Jin-song Li; Wei-xia Cheng; Can-ping Huang; Zhao-jun Duan (Archives of Virology, 2012)

Comparative analysis of essential oil components of Evodia rutaecarpa (Juss.) Benth. var. officinalis (Dode) Huang and Evodia rutaecarpa (Juss.) Benth. - Guang-Xian Cai; Dan Huang; Shun-Xiang Li; Fei Xu; Lu Wang; Yan-Hui Lu; Liang Cao; Bao-Yang Wei; Ya Li; Ping Cai (Natural Product Research, 2012)

A new benzodioxocinone from the leaves of Cinnamomum tenuifolium - Hsin-Liang Chen; Soong-Yu Kuo; Yun-Ping Li; Ya-Fei Kang; Yu-Ting Yeh; Jin-Cherng Huang; Chung-Yi Chen (Natural Product Research, 2012)

Physical-Mechanical Properties and Microstructure Features of Cohesive Soil in the Central South Yellow Sea - Ping Li; Yuan-Qin Xu; Pei-Ying Li; Wei Wei; Wei Huang (Marine Georesources & Geotechnology, 2012)

A Highly Sensitive Fluorescent Probe for HClO and Its Application in Live Cell Imaging - Qing-Ping Zuo; Zuo-Jun Li; Yong-Hua Hu; Bin Li; Li-Hua Huang; Chun-Jiang Wang; Shi-Kun Liu; Hai-Qiang Liao (Journal of Fluorescence, 2012)

Genetic characterization of Aleutian mink disease viruses isolated in China - Yanwu Li; Juan Huang; Yun Jia; Yijun Du; Ping Jiang; Rui Zhang (Virus Genes, 2012)

Association of the microRNA-499 variants with susceptibility to hepatocellular carcinoma in a Chinese population - Yu Xiang; Song Fan; Ju Cao; Shifeng Huang; Li-ping Zhang (Molecular Biology Reports, 2012)

Dysregulation of the β3 integrin-VEGFR2 complex in Hantaan virus–directed hyperpermeability upon treatment with VEGF - Wei Wang; Ye Zhang; Yu Li; Lei Pan; Lu Bai; Yan Zhuang; Chang-Xing Huang; Jiu-Ping Wang; Hai-Tao Yu; Xin Wei; Wei Jiang; Ya-Yun Nan; et al. (Archives of Virology, 2012)

Determination of Geometrical and Structural Representative Volume Elements at the Baihetan Dam Site - Wen Zhang; Jian-ping Chen; Chang Liu; Rui Huang; Ming Li; Ying Zhang (Rock Mechanics and Rock Engineering, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

Proteomic Analysis of Osmotic Stress-Responsive Proteins in Sugarcane Leaves - Gui Zhou; Li-Tao Yang; Yang-Rui Li; Cheng-Lin Zou; Li-Ping Huang; Li-Hang Qiu; Xing Huang; Manoj Kumar Srivastava (Plant Molecular Biology Reporter, 2012)

The different expression of immune-related cytokine genes in response to velogenic and lentogenic Newcastle disease viruses infection in chicken peripheral blood - Wen-Quan Liu; Ming-Xing Tian; Yuan-Ping Wang; Yang Zhao; Nian-Li Zou; Fang-Fang Zhao; San-Jie Cao; Xin-Tian Wen; Ping Liu; Yong Huang (Molecular Biology Reports, 2012)

Chemical and pharmacological studies of Oplopanax horridus, a North American botanical - Tyler Calway; Guang-Jian Du; Chong-Zhi Wang; Wei-Hua Huang; Jing Zhao; Shao-Ping Li; Chun-Su Yuan (Journal of Natural Medicines, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Begomovirus–whitefly mutualism is achieved through repression of plant defences by a virus pathogenicity factor - TONG ZHANG; JUN‐BO LUAN; JIN‐FENG QI; CHANG‐JUN HUANG; MENG LI; XUE‐PING ZHOU; SHU‐SHENG LIU (Molecular Ecology, 2012)
Plant‐mediated interactions between herbivorous arthropods and pathogens transmitted by herbivores are important determinants of the population dynamics of both types of organisms in the field. The role of plant defence in mediating these types of tripartite interactions have been recognized but rarely examined especially at the physiological and molecular levels. Our previous work shows that a worldwide invasive whitefly can establish mutualism with the begomovirus Tomato yellow leaf curl China virus (TYLCCNV) via crop plants. Here, we show that TYLCCNV and betasatellite co‐infection suppresses jasmonic acid defences in the plant. Impairing or enhancing defences mediated by jasmonic acid in the plant enhances or depresses the performance of the whitefly. We further demonstrate that the pathogenicity factor βC1 encoded in the betasatellite is responsible for the initiation of suppression on plant defences and contributes to the realization of the virus–vector mutualism. By integrating ecological, mechanistic and molecular approaches, our study reveals a major mechanism of the plant‐mediated mutualism between a virus and its vector. As the test plant is an important economic crop, the results also have substantial implications for developing novel strategies for management of crop viruses and the insect vectors associated with them.

Signal transduction during cold, salt, and drought stresses in plants - Guo-Tao Huang; Shi-Liang Ma; Li-Ping Bai; Li Zhang; Hui Ma; Ping Jia; Jun Liu; Ming Zhong; Zhi-Fu Guo (Molecular Biology Reports, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Effects of insulin-like growth factor-1 on the properties of mesenchymal stem cells in vitro - Yu-li Huang; Ruo-feng Qiu; Wei-yi Mai; Jian Kuang; Xiao-yan Cai; Yu-gang Dong; Yun-zhao Hu; Yuan-bin Song; An-ping Cai; Zhi-gao Jiang (Journal of Zhejiang University-SCIENCE B, 2012)

Inhibition of Intercellular Adhesion in Herpex Simplex Virus Infection by Glycyrrhizin - Wen Huang; Xiao Chen; Qi Li; Ping Li; Gaonian Zhao; Mingming Xu; Peng Xie (Cell Biochemistry and Biophysics, 2012)

Isolation and characterization of the citrinin biosynthetic gene cluster from Monascus aurantiacus - Yan-Ping Li; Yang Xu; Zhi-Bing Huang (Biotechnology Letters, 2012)

Modeling methane emissions from irrigated rice cultivation in C hina from 1960 to 2050 - Wen Zhang; Yongqiang Yu; Yao Huang; Tingting Li; Ping Wang (Global Change Biology, 2011)
Rice paddy is a major source of anthropogenic terrestrial methane ( CH 4 ). C hina has the second‐largest area of rice cultivation in the world, accounting for ca. 19% of the world's rice‐producing area. Recognizing the significance of C hina's rice cultivation in the global CH 4 budget, we estimated the CH 4 emissions resulting from irrigated rice cultivation in C hina from 1960 to 2050 using a CH 4 MOD model. The model estimates suggest that the annual CH 4 emissions decreased from 5.62 Tg yr −1 in 1960 to 4.13 Tg yr −1 in 1970, and this decrease was attributed to changes in water management from continuous flooding to mid‐season drainage irrigation. Since the early 1970s, the amount of CH 4 emissions gradually increased to 6.85 Tg yr −1 by 2009 because of significant improvements in crop production that led to high‐crop residue retention. Higher levels of CH 4 emissions occurred in southern C hina, where double rice cropping systems are most common. For the A1B and B1 scenarios of the IPCC Special Report on Emissions Scenarios ( SRES ), the amount of CH 4 emissions from 2010 to 2050 is predicted to increase at an average rate of 1.2 kg ha −1 yr −1 in response to global warming. Compared to 2009, the CH 4 flux is predicted to increase by ca. 14% by the late 2040s, and the increase in these emissions in northeastern C hina is estimated to become more significant than in the other rice‐growing regions of the country. Under the assumptions that the rice‐producing land area will remain the same, decrease by 25% or increase by 38% by the late 2040s, the CH 4 emissions are projected to be 7.8, 5.6 or 11.7 Tg yr −1 , respectively.

Experimental Pathogenicity of a Clinical Isolate of Trichosporon dermatis in a Murine Model - Ying-Ping Lin; Yan-Ping Yang; Wen-Ming Huang; Yong-Hua Chen; Shun-Fan Li; Yi-Ming Fan (Mycopathologia, 2011)

Antithrombotic lipids from Semen Persicae - Nian-Yun Yang; Li Liu; Wei-Wei Tao; Jin-Ao Duan; Xun-Hong Liu; Su-Ping Huang (Natural Product Research, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Identification and expression analysis of two growth hormone receptors in zanzibar tilapia (Oreochromis hornorum) - Feng-Ying Gao; Mai-Xin Lu; Xing Ye; Zhang-Han Huang; Huan Wang; Hua-Ping Zhu; Li-Ping Yang (Fish Physiology and Biochemistry, 2011)

The Influence of Stress Factors on the Reactivation of Latent Herpes Simplex Virus Type 1 in Infected Mice - Wen Huang; Peng Xie; Mingming Xu; Ping Li; Gaonian Zao (Cell Biochemistry and Biophysics, 2011)

Dominant Contribution of Northern Chinese to the Paternal Genetic Structure of Chaoshanese in South China - Sheng-Ping Hu; Hui Li; Feng-Huan Zhang; Li-Qun Huang; Yan Lu (Biochemical Genetics, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

PzsS3a, a novel endosperm specific promoter from maize (Zea mays L.) induced by ABA - Yu-Feng Hu; Yang-ping Li; Junjie Zhang; Hanmei Liu; Zhiyu Chen; Yubi Huang (Biotechnology Letters, 2011)

Saccharopolyspora lacisalsi sp. nov., a novel halophilic actinomycete isolated from a salt lake in Xinjiang, China - Tong-Wei Guan; Nan Wu; Zhan-Feng Xia; Ji-Sheng Ruan; Xiao-Ping Zhang; Ying Huang; Li-Li Zhang (Extremophiles, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Expression and tissue and subcellular localization of anthocyanidin synthase (ANS) in grapevine - Huiling Wang; Wei Wang; Hui Li; Ping Zhang; Jicheng Zhan; Weidong Huang (Protoplasma, 2011)

Micropropagation of bromeliad Aechmea fasciata via floral organ segments and effects of acclimatization on plantlet growth - Ping-Lung Huang; Li-Jen Liao; Chi-Chu Tsai; Zin-Huang Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Gα13 is closely related to hematopoiesis in zebrafish - Ding Ye; Qiwen Yang; Yang Li; Xinyun Huang; Jiarui Hu; Shiguang Qian; Zheng Tan; Ping Song (Molecular Biology Reports, 2011)

Efficacy of a novel endotoxin adsorber polyvinylidene fluoride fiber immobilized with L-serine ligand on septic pigs - Jian-ping Gao; Man Huang; Ning Li; Peng-fei Wang; Huan-lin Chen; Qiu-ping Xu (Journal of Zhejiang University-SCIENCE B, 2011)

Minimally-invasive treatment of communicating hydrocephalus using a percutaneous lumboperitoneal shunt - Lu Jia; Zhong-xin Zhao; Chao You; Jia-gang Liu; Si-qing Huang; Min He; Pei-gang Ji; Jie Duan; Yi-jun Zeng; Guo-ping Li (Journal of Zhejiang University-SCIENCE B, 2011)

Trichodermanin A, a novel diterpenoid from endophytic fungus culture - Pei-Xin Sun; Cheng-Jian Zheng; Wen-Chao Li; Gui-Lin Jin; Fang Huang; Lu-Ping Qin (Journal of Natural Medicines, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

β-Actin is a downstream effector of the PI3K/AKT signaling pathway in myeloma cells - Yen-Peng Ho; Chi-Wei Kuo; Yuan-Tong Hsu; Yu-Shan Huang; Li-Ping Yew; Wei-Feng Huang; Kuo-Chih Lin; Jung-Hsin Hsu (Molecular and Cellular Biochemistry, 2011)

Development and application of an efficient virus-induced gene silencing system in Nicotiana tabacum using geminivirus alphasatellite - Chang-jun Huang; Tong Zhang; Fang-fang Li; Xin-yue Zhang; Xue-ping Zhou (Journal of Zhejiang University-SCIENCE B, 2011)

The Evolution of Environmental Management Philosophy Under Rapid Economic Development in China - Ping Li; Zhongliang Huang; Hai Ren; Hongxiao Liu; Quan Wang (Ambio, 2011)

Determination of Trace Deoxyribonucleic Acid by Using Fluorescein Isothiocyanate-Phenosafranine as a Double-Luminescent Phosphorescence Probe - Jia-Ming Liu; Xiao-Mei Huang; Zhen-Bo Liu; Fei-Ming Li; Li-Ping Lin; Xin-Xing Wang; Chang-Qing Lin; Ya-Hong Huang; Zhi-Ming Li; Shao-Qin Lin (Journal of Fluorescence, 2011)

Water quality of a tributary of the Pearl River, the Beijiang, Southern China: implications from multivariate statistical analyses - Ming W. Song; Ping Huang; Feng Li; Hui Zhang; Kai Z. Xie; Xi H. Wang; Guo X. He (Environmental Monitoring and Assessment, 2011)

Effect of high glucose levels on the calcification of vascular smooth muscle cells by inducing osteoblastic differentiation and intracellular calcium deposition via BMP-2/Cbfα-1 pathway - Fang Liu; Hui Zhong; Jing-yuan Liang; Ping Fu; Zhi-juan Luo; Li Zhou; Rong Gou; Jun Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Amino acid sequence analysis and identification of mutations under positive selection in hemagglutinin of 2009 influenza A (H1N1) isolates - Xiaofan Ding; Lifang Jiang; Changwen Ke; Zhan Yang; Chunliang Lei; Kaiyuan Cao; Jun Xu; Lin Xu; Xingfen Yang; Yonghui Zhang; Ping Huang; Weijun Huang; et al. (Virus Genes, 2010)

Construction and characterization of a full-length infectious clone from a fast-replicating, X4-tropic HIV-1 subtype B′ isolate - Shou-li Wu; Yan-sheng Yan; Ping-ping Yan; Hai-long Huang; Hui-rong Wang (Archives of Virology, 2010)

Inhibition of phosphodiesterase-4 reverses memory deficits produced by Aβ25–35 or Aβ1–40 peptide in rats - Yu-Fang Cheng; Chuang Wang; Huan-Bing Lin; Yun-Feng Li; Ying Huang; Jiang-Ping Xu; Han-Ting Zhang (Psychopharmacology, 2010)

A proteomic approach for plasma biomarker discovery with 8-plex iTRAQ labeling and SCX-LC-MS/MS - Haige Ye; Li Sun; Xiaojun Huang; Ping Zhang; Xiaoshu Zhao (Molecular and Cellular Biochemistry, 2010)

Genetic analysis revealed LX4 genotype strains of avian infectious bronchitis virus became predominant in recent years in Sichuan area, China - Nian-Li Zou; Fang-Fang Zhao; Yuan-Ping Wang; Ping Liu; San-Jie Cao; Xin-Tian Wen; Yong Huang (Virus Genes, 2010)

Genetic evolution of equine influenza viruses isolated in China - Ting Qi; Wei Guo; Wen-Qiang Huang; Hong-Mei Li; Li-Ping Zhao; Ling-Li Dai; Na He; Xiao-Fang Hao; Wen-Hua Xiang (Archives of Virology, 2010)

Chromosomal localization of rDNA genes and genomic organization of 5S rDNA in Oreochromis mossambicus, O. urolepis hornorum and their hybrid - Hua Ping Zhu; Mai Xin Lu; Feng Ying Gao; Zhang Han Huang; Li Ping Yang; Jian Fang Gui (Journal of Genetics, 2010)

Sensitive Phosphorimetric Determination of Bumetanide in Human Urine with Its Inhibition Effect on the Formation of [Fe-morin] 3+ Complex - Li-Qing Zeng; Jia-Ming Liu; Fei-Ming Li; Xiao-Mei Huang; Li-Ping Lin; Xin-Xing Wang; Li-Hong Zhang; Chang-Qing Lin (Journal of Fluorescence, 2010)

Lead and Other Elemental Content of Normal and Erwinia carotovora Infected Amorphallus konjac Corms - Tao Li; Wen-Guo Wei; Wei Shao; Bai-Ling Chen; Ying-Ping Huang (Bulletin of Environmental Contamination and Toxicology, 2010)

Involvement of anion exchanger-2 in apoptosis of endothelial cells induced by high glucose through an mPTP-ROS-Caspase-3 dependent pathway - Qi-Ren Huang; Qing Li; Yuan-Hong Chen; Li Li; Li-Li Liu; Shui-Hong Lei; He-Ping Chen; Wei-Jie Peng; Ming He (Apoptosis, 2010)

Erratum to: RegIV expression showing specificity to gastrointestinal tract and its potential role in diagnosing digestive tract neuroendocrine tumor - Feng-ying Li; Xiao-bin Ren; En-ping Xu; Qiong Huang; Hong-qiang Sheng; Bing-jian Lv; Mao-de Lai (Journal of Zhejiang University-SCIENCE B, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Spatial and seasonal characterization of net primary productivity and climate variables in southeastern China using MODIS data - Dai-liang Peng; Jing-feng Huang; Alfredo R. Huete; Tai-ming Yang; Ping Gao; Yan-chun Chen; Hui Chen; Jun Li; Zhan-yu Liu (Journal of Zhejiang University-SCIENCE B, 2010)

RegIV expression showing specificity to gastrointestinal tract and its potential role in diagnosing digestive tract neuroendocrine tumor - Feng-ying Li; Xiao-bin Ren; En-ping Xu; Qiong Huang; Hong-qiang Sheng; Bing-jian Lv; Mao-de Lai (Journal of Zhejiang University-SCIENCE B, 2010)

A Mediated Glucose Biosensor Incorporated with Reverse Iontophoresis Function for Noninvasive Glucose Monitoring - Congo Tak-Shing Ching; Tai-Ping Sun; Su-Hua Huang; Hsiu-Li Shieh; Chung-Yuan Chen (Annals of Biomedical Engineering, 2010)

Viral infection of tobacco plants improves performance of Bemisia tabaci but more so for an invasive than for an indigenous biotype of the whitefly - Jian Liu; Meng Li; Jun-min Li; Chang-jun Huang; Xue-ping Zhou; Fang-cheng Xu; Shu-sheng Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Genetic mapping of quantitative trait loci associated with β-amylase and limit dextrinase activities and β-glucan and protein fraction contents in barley - Kang Wei; Da-wei Xue; You-zong Huang; Xiao-li Jin; Fei-bo Wu; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2009)

A novel triple-regulated oncolytic adenovirus carrying PDCD5 gene exerts potent antitumor efficacy on common human leukemic cell lines - Min Xie; Ji-Hong Niu; Yan Chang; Qi-Jun Qian; Hong-Ping Wu; Lin-Fang Li; Yao Zhang; Jin-Lan Li; Xiao-Jun Huang; Guo-Rui Ruan (Apoptosis, 2009)

Spatial Filtering Improves EMG Classification Accuracy Following Targeted Muscle Reinnervation - He Huang; Ping Zhou; Guanglin Li; Todd Kuiken (Annals of Biomedical Engineering, 2009)

Intercellular adhesion molecule-1 gene K469E polymorphism and ischemic stroke: a case-control study in a Chinese population - Xiao Xia Li; Jian Ping Liu; Jin Quan Cheng; Sheng Hong Han; Yi Jie Geng; Sheng Wei; Shi Tong Gao; Da Na Huang; Shao Fa Nie (Molecular Biology Reports, 2009)

A new screening method based on yeast-expressed human dipeptidyl peptidase IV and discovery of novel inhibitors - Chen-Xi Hu; Hui Huang; Li Zhang; You Huang; Zhu-Fang Shen; Ke-Di Cheng; Guan-Hua Du; Ping Zhu (Biotechnology Letters, 2009)

A value chain approach to crisis response system: the case of Qingdao - Jian Hua Li; Zheng Ping Zhang; Rui Huan Jing; Chong Fu Huang (Stochastic Environmental Research and Risk Assessment, 2009)

Differential belowground allelopathic effects of leaf and root of Mikania micrantha - Ai-Ping Wu; Hua Yu; Shu-Qin Gao; Zhen-Ying Huang; Wei-Ming He; Shi-Li Miao; Ming Dong (Trees, 2009)

Isolation and characterization of microsatellite loci in Pedicularis verticillata L. using PCR-based isolation of microsatellite arrays (PIMA) - Tsurng-Juhn Huang; Yi-Yen Chen; Yen-Ping Li; Cheng-Yu Hung; Tzen-Yuh Chiang; Chang-Hung Chou (Conservation Genetics, 2008)

Complete genome analysis of a highly pathogenic H5N1 influenza A virus isolated from a tiger in China - Muhammad Hassan Mushtaq; Huang Juan; Ping Jiang; Yufeng Li; TianXian Li; Yijun Du; Muhammad Mahmood Mukhtar (Archives of Virology, 2008)

Micropropagation of Dendrobium densiflorum Lindl. ex Wall. through protocorm-like bodies: effects of plant growth regulators and lanthanoids - Jian-Ping Luo; Ying Wang; Xue-Qiang Zha; Li Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

Human tau protein forms complex with PrP and some GSS- and fCJD-related PrP mutants possess stronger binding activities with tau in vitro - Xiao-Fan Wang; Chen-Fang Dong; Jin Zhang; Yan-Zhen Wan; Feng Li; Yin-Xia Huang; Lu Han; Bing Shan; Chen Gao; Jun Han; Xiao-Ping Dong (Molecular and Cellular Biochemistry, 2008)

Suppression of porcine reproductive and respiratory syndrome virus replication in MARC-145 cells by shRNA targeting ORF1 region - Guanming Li; Juan Huang; Ping Jiang; Yufeng Li; Wenming Jiang; Xianwei Wang (Virus Genes, 2007)

Nonadditive effects of litter mixtures on decomposition and correlation with initial litter N and P concentrations in grassland plant species of northern China - Ping Liu; Osbert J. Sun; Jianhui Huang; Linghao Li; Xingguo Han (Biology and Fertility of Soils, 2007)

Generation of genetic engineering monoclonal antibodies against prion protein - Yin-Xia Huang; Jun Han; Chen-Fang Dong; Li Sun; Chen Gao; Xiao-Fan Wang; Lu Han; Wei Zhou; Bao-Yun Zhang; Hui-Ying Jiang; Mi-Fang Liang; Xiao-Ping Dong (Medical Microbiology and Immunology, 2007)

Overexpression of the Na+/H+ antiporter gene from Suaeda salsa confers cold and salt tolerance to transgenic Arabidopsis thaliana - Jinyao Li; Gangqiang Jiang; Ping Huang; Ji Ma; Fuchun Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Adaptive Evolution of the First Extra Exon in the Murid Rodent Prolactin Gene Family - Ying Li; Jing-Fei Huang; Ya-Ping Zhang (Biochemical Genetics, 2007)

Fibrarecisin, a novel triterpenoid from Fibraurea recisa with antitumor activity - Jiao-Long Fu; Chang-Heng Tan; Li-Ping Lin; Ji Huang; Da-Yuan Zhu (Natural Product Research, 2007)

Apelin suppresses apoptosis of human osteoblasts - Hui Xie; Ling-Qing Yuan; Xiang-Hang Luo; Jiao Huang; Rong-Rong Cui; Li-Juan Guo; Hou-De Zhou; Xian-Ping Wu; Er-Yuan Liao (Apoptosis, 2007)

Receptor-mediated gene delivery using polyethylenimine (PEI) coupled with polypeptides targeting FGF receptors on cells surface - Da Li; Qing-qing Wang; Gu-ping Tang; Hong-liang Huang; Fen-ping Shen; Jing-zhong Li; Hai Yu (Journal of Zhejiang University-SCIENCE B, 2006)

Determination of Trace Mercury by Solid Substrate-Room Temperature Phosphorimetry Quenching Method Based on Catalytic Effect of Hg2+on Formation of the Ion Association Complex [Sn(XO)6]4+·[(Fin)4] - Jia-Ming Liu; Ruo-Hong Wu; De-Chang Li; Ping Zhou; Min-Min Zheng; Xiao-Yi Zeng; Dong-Xia Liu; Xiao-Mei Huang; Guo-Hui Zhu (Journal of Fluorescence, 2006)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Spatial variability of Soil Nutrients and Influencing Factors in a Vegetable Production Area of Hebei Province in China - Shao-Wen Huang; Ji-Yun Jin; Li-Ping Yang; You-Lu Bai (Nutrient Cycling in Agroecosystems, 2006)

Synthesis of Site-Specifically Dimethylated and Trimethylated Peptides Derived from Histone H3 N-Terminal Tail - Zhi-Ping Huang; Jin-Tang Du; Yu-Fen Zhao; Yan-Mei Li (International Journal of Peptide Research and Therapeutics, 2006)

Studies on the Interaction of Tricyclazole with β-cyclodextrin and human Serum Albumin by Spectroscopy - Hua-Xin Zhang; Xing Huang; Ping Mei; Ke-Hua Li; Cheng-Nong Yan (Journal of Fluorescence, 2006)

Study on the expression and mutation of human telomeric repeat binding factor (hTRF1) in 10 malignant hematopoietic cell lines - Jie Sun; He Huang; Yuan-yuan Zhu; Jian-ping Lan; Jing-yuan Li; Xiao-yu Lai; Jian Yu (Journal of Zhejiang University-SCIENCE B, 2005)

Fast screening target sites for RNA interference using a cell-free system - Huang Mei; Jia Fang-Jun; Li Chong-Yong; Li Yi-Ping; Guo Li-He (Biotechnology Letters, 2005)

Cloning and Characterization of the First Cnidarian ADP-Ribosylation Factor, and Its Involvement in the Aiptasia-Symbiodinum Endosymbiosis - Ming-Chyuan Chen; Ying-Min Cheng; Li-Hsueh Wang; Chorng-Horng Lin; Xing-Yan Huang; Ming-Chin Liu; Ping-Jyun Sung; Lee-Shing Fang (Marine Biotechnology, 2004)

Mapping of quantitative trait loci (QTLs) for rice protein and fat content using doubled haploid lines - Zhong-Li Hu; Ping Li; Ming-Quan Zhou; Zhi-Hong Zhang; Ling-Xia Wang; Li-Huang Zhu; Ying-Guo Zhu (Euphytica, 2004)

Minimizing phenol pollution in sugarcane stem apical meristem culture - Cheng-Mei Huang; Yang-Rui Li; Yan-Ping Ye (Sugar Tech, 2003)

Rhizopus arrhizus – a producer for simultaneous saccharification and fermentation of starch waste materials to l(+)-lactic acid - Bo Jin; Li Ping Huang; Paul Lant (Biotechnology Letters, 2003)

Identification of quantitative trait loci (QTLs) for the characters of vascular bundles in peduncle related to indica-japonica differentiation in rice (Oryza sativa L.) - Zhi-Hong Zhang; Ping Li; Ling-Xia Wang; Chang-Jun Tan; Zhong-Li Hu; Ying-Guo Zhu; Li-Huang Zhu (Euphytica, 2002)

Molecular characterization of germline mutations in the BRCA1 and BRCA2 genes from breast cancer families in Taiwan - Steven Shoei-Lung Li; H.-M. Tseng; Tsui-Ping Yang; Chia-Han Liu; Shiuh-Jen Teng; Hung-Wen Huang; L.-M. Chen; Hsiao-Wei Kao; Jimmy H. Chen; Jau-Neng Tseng; Angela Chen; Ming-Feng Hou; et al. (Human Genetics, 1999)